Development of a simple assay protocol for high-throughput screening of mycobacterium tuberculosis glutamine synthetase for the identification of novel inhibitors - Singh, U; Panchanadikar, V; Sarkar, Dhiman (Journal of Biomolecular Screening, 2005)
Mycobacterium tuberculosis glutamine synthetase (GS) is an essential enzyme involved in the pathogenicity of the organism. The screening of a compound library using a robust high-throughput screening (HTS) assay is currently thought to be the most efficient way of getting lead molecules, which are potent inhibitors for this enzyme. The authors have purified the enzyme to a > 90% level from the recombinant Escherichia coli strain YMC21E, and it was used for partial characterization as well as standardization experiments. The results indicated that the K-m of the enzyme for L-glutamine and hydroxylamine were 60 mM and 8.3 mM, respectively. The K-m for ADP, arsenate, and Mn2+, were 2 mu M, 5 mu M, and 25 mu M, respectively. When the components were adjusted according to their K-m values, the activity remained constant for at least 3 h at both 25 degrees C and 37 degrees C. The Z' factor determined in microplate format indicated robustness of the assay. When the signal/noise ratios were determined for different assay volumes, it was observed that the 200-mu l volume was found to be optimum. The DMSO tolerance of the enzyme was checked up to 10%, with minimal inhibition. The IC50 value determined for L-methionine S-sulfoximine on the enzyme activity was 3 mM. Approximately 18,000 small molecules could be screened per day using this protocol by a Beckman Coulter HTS setup.
Keywords: Beckman Coulter; Glutamine synthetase; high-throughput screening; Mycobacterium tuberculosis

Development of a simple high-throughput screening protocol based on biosynthetic activity of Mycobacterium tuberculosis glutamine synthetase for the identification of novel inhibitors - Singh, Upasana; Sarkar, Dhiman (Journal of Biomolecular Screening, 2006)
A high-throughput screening protocol has been developed for Mycobacterium tuberculosis glutamine synthetase by quantitative estimation of inorganic phosphate. The K., values determined at pH 6.8 are 22 mM for L-glutamic acid, 0.75 mM for NH4Cl, 3.25 mM for MgCl2, and 2.5 mM for adenosine triphosphate. The K-m value for glutamine is affected significantly by the increase in pH of assay buffer. At the saturating level of the substrate, the enzyme activity at pH 6.8 and 25 degrees C is found to be linear up to 3 h. The reduction of enzyme activity is negligible even in presence of 10% DMSO. The Z' factor and signal-to-noise ratio are found to be 0.75 and 6.18, respectively, when the enzyme is used at 62.5 mu g/ml concentration. The IC50 values obtained at pH 6.8 for both L-methionine S-sulfoximine and DL-phosphothriacin are 500 mu M and 30 pM, respectively, which is lowest compared to the values obtained at other pH levels. The Beckman Coulter high-throughput screening platform was found to take 5 h 9 min to complete the screening of 60 plates. For each assay plate, a replica plate is used to normalize the data. Screening of 1164 natural product fractions/extracts and synthetic molecules from an in-house library was able to identify 12 samples as confirmed hits. Altogether, the validation data from screening of a small set of an in-house library coupled with Z' and signal-to-noise values indicate that the protocol is robust for high-throughput screening of a diverse chemical library.
Keywords: Beckman Coulter; biosynthetic activity; Glutamine synthetase; high-throughput screening; Mycobacterium tuberculosis

High-throughput screening of RNA polymerase inhibitors using a fluorescent UTP analog - Bhat, Jyothi; Rane, Rajendra; Solapure, Suresh M.; Sarkar, Dhiman; Sharma, Umender; Harish, M. N.; Lamb, Sarah; Plant, Darren; Alcock, Peter; Peters, Steve; Barde, Shubhada; Roy, Raman K. (Journal of Biomolecular Screening, 2006)
RNA polymerase (RNAP) is a well-validated target for the development of antibacterial and antituberculosis agents. Because the purification of large quantities of native RNA polymerase from pathogenic mycobacteria is hazardous and cumbersome, the primary screening was carried out using Escherichia coli RNAP. The authors have developed a high-throughput screening (HTS) assay to screen for novel inhibitors of RNAP. In this assay, a fluorescent analog of UTP, gamma-amino naphthalene sulfonic acid (gamma-AmNS) UTP, was used as one of the nucleotide substrates. Incorporation of UMP in RNA results in the release of gamma-AmNS-PPi, which has higher intrinsic fluorescence than (gamma-AmNS) UTP. The assay was optimized in a 384-well format and used to screen 670,000 compounds at a concentration of 10 mu M. About 0.1% of the compounds showed more than 60% inhibition in the primary HTS. All the primary actives tested for dose response using the same assay had an EC50 below 100 mu M. Eighty percent of the primary HTS actives obtained using E. coli RNAP showed comparable activity against Mycobacterium smegmatis RNAP in the conventional radioactive assay. Activity of hits selected for the hit-to-lead optimization was also confirmed against Mycobacterium bovis RNAP which has > 99% sequence identity with Mycobacterium tuberculosis RNAP subunits.

Identification of a respiratory-type nitrate reductase and its role for survival of mycobacterium smegmatis in wayne model - Khan, Arshad; Sarkar, Dhiman (Microbial Pathogenesis, 2006)
Nitrate reductase (NR) is found to be expressed in certain mycobacterium sp. whose link with the development of persistence is yet to be resolved. The present study demonstrates the action of selective inhibitors on NR as well as in the survival of Mycobacterium smegmatis using Wayne's model. During gradual shift down to anaerobic stage in Wayne's model, conversion of nitrate to nitrite became apparent in M. smegmatis. More than 97 percent inhibition was observed for the conversion of nitrate to nitrite by azide (0.05 mM) and thiocyanate (20 mM) in both whole-cell as well as its cell-free lysate, respectively. Under identical condition, chlorate (20 mM) inhibited nitrate reduction by 67 and 10 percent, respectively. At these concentrations, neither of azide, thiocyanate nor chlorate had any significant effect on cell growth under aerobic condition. In Wayne's culture model, thiocyanate and chlorate inhibited the growth of M. smegmatis by almost 2 logs at the same concentrations whereas azide inhibited by almost 1.75 log when added at the time of inoculation. Exposure of same culture at 96 h after inoculation in Wayne's model to these inhibitors showed 1.74, 1.95 and 2.37 log inhibition of viable cells with respect to azide, thiocyanate and chlorate. These findings further indicated that NR inhibitors kill the bacilli at anaerobic stage under the experimental condition mentioned. Metronidazole (MTZ) (2 mM) and Nitrofurantoin (NIT) (0.3 mM) reduced the cell number at both stages by < 0.7log. They did not have any effect on NR. Altogether, the results clearly indicate that NR-specific inhibitors could become more promising in killing the bacilli at anaerobic stage than the available conventional drugs. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: Mycobacterium smegmatis; nitrate reductase; Wayne model

Bactericidal activity of 2-nitroimidazole against the active replicating stage of mycobacterium bovis BCG and mycobacterium tuberculosis with intracellular efficacy in THP-1 macrophages - Khan, Arshad; Sarkar, Sampa; Sarkar, Dhiman (International Journal of Antimicrobial Agents, 2008)
This study evaluated the antituberculous potential of 2-nitroimidazole under in vitro conditions. Minimal bactericidal concentrations of the compound against actively replicating Mycobacterium bovis BCG and Mycobacterium tuberculosis H37Ra were found to be 0.226 mu g/mL and 0.556 mu g/mL in enriched and minimal medium, respectively. Minimal inhibitory concentrations were > 100 times lower than reported antituberculous nitroimidazoles such as nitrofurantoin and furaltadone, indicating the greater potential of 2-nitroimidazole. No discernible effect of 2-nitroimidazole was seen on saprophytic Mycobacterium smegmatis and the representative bacterial strain Escherichia coli DH5 alpha, indicating the specificity of the molecule against tuberculous mycobacteria. The compound was also found to be effective against M. tuberculosis in the intracellular environment of the human monocytic cell line THP-1, with a reduction in viability of bacilli by 2.5 log after 144 h of incubation at a concentration of 0.113 mu g/mL. A five-fold higher concentration (0.565 mu g/mL) of 2-nitroimidazole sterilised the macrophages of intracellular pathogens within 192 h, without affecting the host. However, 2-nitroimidazole was unable to affect significantly the viability of dormant non-replicating bacilli of M. bovis BCG and M. tuberculosis in Wayne's in vitro model. Overall, the results indicate that 2-nitroimidazole is a potent antituberculous agent active against the organism's active replicating stage, with promising intracellular efficacy as well. (c) 2008 Elsevier B.V. and the International Society of Chemotherapy. All rights reserved.
Keywords: 2-nitroimidazole; antimycobacterial agents; nitroimidazoles; THP-1 macrophage; tuberculosis

Presence of a functional nitrate assimilation pathway in mycobacterium smegmatis - Khan, Arshad; Akhtar, Shamim; Ahmad, Jawid N.; Sarkar, Dhiman (Microbial Pathogenesis, 2008)
Ability of Mycobacterium smegmatis to assimilate nitrate was evaluated in its active and dormant phase. Nitrate (10 mM), nitrite (0.5 mM) and ammonia (10 mM)allowed growth of M. smegmatis concomitant with their complete depletion from the culture in 144, 120 and 96 h, respectively, when used as sole nitrogen Source. Azide (50 mu M) stopped the growth of M. smegmatis when nitrate was used as sole nitrogen source. L-methionine-S-sulfoximine (L-MSO), which is a well-known inhibitor of glutamine synthetase, an enzyme also involved in nitrogen metabolic pathway, when applied at 10 mu g/ml concentration, completely inhibited the growth of the organism when nitrate or nitrite was used as sole nitrogen source. There was no effect of either azide or L-MSO at above concentrations on the growth of the organism when asparagine or ammonia was used as sole nitrogen source. More significantly, utilization of nitrate, nitrite and ammonia continued even in oxygen depletion induced dormant culture at the rates of 289, 25 and 354 mu M/day, respectively. These rates were 5-8 times slower than the rates of 1966, 127 and 2890 mu M/day, respectively, in active replicating phase. In the presence of azide (50 mu M) and L-MSO (10 mu g/ml), 2.1 and 1.51 logs reduction in viability of dormant M. smegmatis was observed using nitrate and nitrite, respectively, as sole nitrogen source. Altogether, the results indicated the presence of nitrate assimilation pathway operating in both active and dormant stage of M. smegmatis. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: Dormant bacilli; Glutamine synthetase; L-methionine-S-sulfoximine; Mycobacterium smegmatis; Nitrate assimilation

Simple whole cell based high throughput screening protocol using Mycobacterium bovis BCG for inhibitors against dormant and active tubercle bacilli - Khan, Arshad; Sarkar, Dhiman (Journal of Microbiological Methods, 2008)
This study aimed at developing a whole cell based high throughput screening protocol to identify inhibitors against both active and dormant tubercle bacilli. A respiratory type of nitrate reductase (NarGHJI), which was induced during dormancy, could reflect the viability of dormant bacilli of Mycobacterium bovis BCG in microplate adopted model of in vitro dormancy. Correlation between reduction in viability and nitrate reductase activity was seen clearly when dormant stage inhibitor metronidazole and itaconic anhydride were applied in this in vitro microplate model. Active replicating stage could also be monitored in the same assay by measuring the A(620) of the culture. MIC values of 0.08, 0.075, 0.3 and 3.0 mu g/ml, determined through monitoring A(620) in this assay for rifampin, isoniazid, streptomycin and ethambutol respectively, were well in agreement with previously reported by BACTEC and Bio-Siv assays. S/N ratio and Z' factor for the assay were 8.5 and 0.81 respectively which indicated the robustness of the protocol. Altogether the assay provides an easy, inexpensive, rapid, robust and high content screening too] to search novel antitubercular molecules against both active and dormant bacilli. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: high throughput screening; tuberculosis; Wayne's dormancy model; whole cell based assay

Production, purification, and characterization of taxol and 10-DABIII from a new endophytic fungus gliocladium sp isolated from the Indian yew tree, taxus baccata - Sreekanth, D.; Syed, A.; Sarkar, S.; Sarkar, Dhiman; Santhakumari, B.; Ahmad, Absar; Khan, Mohammad Islam (Journal of Microbiology and Biotechnology, 2009)
We have isolated endophytic fungi from the Indian yew tree, Taxus baccata, and then screened for taxol production. Out of the 40 fungal cultures screened, one fungus Gliocladium sp. was found to produce taxol and 10-DABIII (10-deacetyl baccatin III). These compounds were purified by TLC and HPLC and characterized using UV-spectroscopy, ESI-MS, MS/MS, and proton NMR. One liter of Gliocladium sp. culture yielded 10 mu g of taxol and 65 mu g of 10-DABIII. The purified taxol from the fungus showed cytotoxicity towards cancer lines HL-60 (leukemia), A431 (epidermal carcinoma), and MCF-7 (breast cancer).
Keywords: 10 DAB III; Endophytic fungi; Gliocladium sp.; Taxol; Taxus baccata

Method to extract intact and pure RNA from mycobacteria - Akhtar, Shamim; Sarkar, Sampa; Mishra, Abhishek; Sarkar, Dhiman (Analytical Biochemistry, 2011)
We describe a high-yielding, simple, and aerosol-free protocol for the isolation of RNA from mycobacteria that does not require sophisticated instruments. The method yielded 50 mu g of RNA from 10(7) cells, 50 times more than a recently reported method. Our method can extract total RNA from aerobically grown bacteria and from in vitro hypoxia-induced dormant bacilli and mycobacteria residing within infected macrophages. (C) 2011 Elsevier Inc. All rights reserved.
Keywords: Dormant; Hypoxia; Mycobacteria; RNA isolation; Spheroplast; Trizol

Novel screening method based on menadione mediated rapid reduction of tetrazolium salt for testing of anti-mycobacterial agents - Singh, Upasana; Akhtar, Shamim; Mishra, Abhishek; Sarkar, Dhiman (Journal of Microbiological Methods, 2011)
A microplate-based rapid, inexpensive and robust technique is developed by using tetrazolium salt 2, 3-bis [2-methyloxy-4-nitro-5-sulfophenyl]-2H-tetrazolium-5-carboxanilide (XTT) and menadione to determine the viability of Mycobacterium tuberculosis, Mycobacterium bovis BCG and Mycobacterium smegmatis bacilli in microplate format. In general, XTT reduction is an extremely slow process which takes almost 24 h to produce a detectable signal. Menadione could drastically induce this reduction to an almost equal extent within a few minutes in a dose dependent manner. The reduction of XTT is directly proportional to the cell concentration in the presence of menadione. The standardized protocol used 200 mu M of XTT and 60 mu M of menadione in 250 mu l of cell suspension grown either in aerobic or anaerobic conditions. The cell suspension of M. bovis BCG and M. tuberculosis were incubated for 40 min before reading the optical density at 470 nm whereas M. smegmatis was incubated for 20 min. Calculated Signal/Noise (S/N) ratios obtained by applying this protocol were 5.4, 6.4 and 9.4 using M. bovis BCG. M. tuberculosis and M. smegmatis respectively. The calculated Z' factors were > 0.8 for all mycobacterium bacilli indicating the robustness of the XTT Reduction Menadione Assay (XRMA) for rapid screening of inhibitors. The assay protocol was validated by applying 10 standard anti-tubercular agents on M. tuberculosis, M. bovis BCG and M. smegmatis. The Minimum Inhibitory Concentration (MIC) values were found to be similar to reported values from Colony Forming Unit (CFU) and REMA (resazurin microplate assay) assays. Altogether. XRMA is providing a novel anti-tubercular screening protocol which could be useful in high throughput screening programs against different physiological stages of the bacilli. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Menadione; Mycobacterium tuberculosis; Tetrazolium salt; XRMA

Nitrate reduction pathways in mycobacteria and their implications during latency - Khan, Arshad; Sarkar, Dhiman (Microbiology-SGM, 2012)
Mycobacterial persistence has gained a lot of attention with respect to developing novel antitubercular drugs, which could drastically reduce the duration of tuberculosis (TB) therapy. A better understanding of the physiology of Mycobacterium tuberculosis, and of the metabolic state of the bacillus during the latent period, is a primary need in finding drug targets against persistent TB. Recent biochemical and genetic studies of nitrate reduction in mycobacteria have revealed the roles of distinct proteins and enzymes involved in the pathway. The differential degree of nitrate reduction among pathogenic and non-pathogenic mycobacterial species, and its regulation during oxygen and nutrient limitation, suggest a link between nitrate reduction pathways and latency. The respiratory and assimilatory reduction of nitrate in mycobacteria may be interconnected to facilitate rapid adaptation to changing oxygen and/or nitrogen conditions, increasing metabolic flexibility for survival in the hostile host environment. This review summarizes the nitrate metabolic pathways operative in mycobacteria to provide an insight into the mechanisms that M. tuberculosis has evolved to adapt successfully to the host environment.

Phyllocladane diterpenes from anisomeles heyneana - Kulkarni, Roshan R.; Shurpali, Ketaki; Gawade, Rupesh L.; Sarkar, Dhiman; Puranik, Vedavati G.; Joshi, Swati P. (Journal of Asian Natural Products Research, 2012)
New phyllocladane diterpene, phyllocladan-16 alpha,17-dihydroxy-19-oic acid (1), together with known phyllocladane diterpene, phyllocladan-16 alpha,19-diol (2), cembrane diterpene ovatodiolide (3), sitosteryl-3-O-beta-D-glucoside (4), and verbascoside (5), were isolated from aerial parts of Anisomeles heyneana. The structure of compound 1 was elucidated by 1D and 2D NMR analyses which included HSQC, HMBC, and nuclear overhauser effect spectroscopy (NOESY) experiments as well as X-ray crystallography. This is the first report of phyllocladane diterpenes from genus Anisomeles. Compounds 1, 3, 4, and 5 were evaluated for inhibition of Mycobacterium tuberculosis and 3 was found to exhibit anti-mycobacterial activity with IC90 6.53 mu g/ml. Compounds 1, 3, and 5, at 100 mu g/ml, were also evaluated for inhibition of Thp-1 cell lines, and compounds 1 and 3 showed 59.02% and 96.4% inhibitions, respectively.
Keywords: Anisomeles heyneana; Lamiaceae; Mycobacterium tuberculosis; phyllocladane diterpenes

Potential use of nitrate reductase as a biomarker for the identification of active and dormant inhibitors of mycobacterium tuberculosis in a THP1 infection model - Sarkar, Sampa; Sarkar, Dhiman (Journal of Biomolecular Screening, 2012)
The development of a macrophage-based, antitubercular high-throughput screening system could expedite discovery programs for identifying novel inhibitors. In this study, the kinetics of nitrate reduction (NR) by Mycobacterium tuberculosis during growth in Thp1 macrophages was found to be almost parallel to viable bacilli count. NR in the culture medium containing 50 mM of nitrate was found to be optimum on the fifth day after infection with M. tuberculosis. The signal-to-noise (S/N) ratio and Z-factor obtained from this macrophage-based assay were 5.4 and 0.965, respectively, which confirms the robustness of the assay protocol. The protocol was further validated by using standard antitubercular inhibitors such as rifampicin, isoniazid, streptomycin, ethambutol, and pyrazinamide, added at their IC90 value, on the day of infection. These inhibitors were not able to kill the bacilli when added to the culture on the fifth day after infection. Interestingly, pentachlorophenol and rifampicin killed the bacilli immediately after addition on the fifth day of infection. Altogether, this assay protocol using M. tuberculosis-infected Thp-1 macrophages provides a novel, cost-efficient, robust, and easy-to-perform screening platform for the identification of both active and hypoxic stage-specific inhibitors against tuberculosis.
Keywords: high-throughput screening; inhibitor; Mycobacterium tuberculosis; nitrate reductase; THP1

Self–assembled histidine acid phosphate nanocapsules as templates for multifunctional hollow platinum nanospheres in ionic liquid [BMIM][BF 4 ] for drug delivery - Soni, Sarvesh Kumar; Sarkar, Sampa; Sarkar, Dhiman; Coloe, Peter J.; Bhargava, Suresh Kumar; Bansal, Vipul (Proceedings of Chemeca, 2012)
During the past few decades, the design and fabrication of nano drug delivery vehicle has received considerable attention for incorporating multi-functionality, emphasizing transportation of anticancer drugs to tumour sites. Protein-based nanoparticles hold significant promise in the development of anticancer drug delivery systems since they have remarkable superiority in biocompatibility, biodegradability and natural metabolism in physiologic systems. Ionic liquids (ILs) are a class of solvents that are composed solely of ions (ILs – commonly referred as room temperature molten salts or room temperature ionic liquids). They have recently emerged as green solvents or green reaction media, because of their reported unique physico-chemical properties. We report for the first time the controlled self-assembly of Histidine Acid phosphatase (HAP) enzyme in the IL 1-butyl-3-methylimidazolium tetrafluoroborate [BMIM][BF 4 ], leading to the formation of HAP nanocapsules as template for synthesis of platinum nanospheres. These HAP nano-containers were loaded with an anticancer drug curcumin. We further demonstrated in vitro drug release and synergistic anticancer effect of these systems on three different cell lines viz. hepatocellular carcinoma (HepG2), breast cancer (MCF-7) and human acute monocytes (THP-1). The present work can extend our theoretical understanding on nano-bio interfacial molecular self assembly and will facilitate the motivated insights of inorganic/organic hybrid nano-materials/ nano-particles/ nano-objects and ionic liquids based multi functional drug delivery vehicles with synergistic combination chemotherapy for potential application in tumor targeting. INTRODUCTION During the past few decades, the design and fabrication of drug delivery vehicle has received considerable attention for incorporating multi-functionality emphasizing transportation of anticancer drugs to tumour sites. These nano drug delivery vehicles have many advantages including prolonged circulation time of the drugs (Duncan, 2003, Kiick, 2007) , improved drug targeting and solubility (Duncan, 2003, Kiick, 2007), higher payloads (Duncan, 2003) and controlled release of the therapeutics into the blood stream or the targeted tumour tissues (Uhrich et al. 1999, Duncan, 2003).

Antimycobacterial labdane diterpenes from leucas stelligera - Kulkarni, Roshan R.; Shurpali, Ketaki; Puranik, Vedavati G.; Sarkar, Dhiman; Joshi, Swati P. (Journal of Natural Products, 2013)
Phytochemical investigation of the acetone extract of the aerial parts of Leucas stelligera afforded four new compounds (1-4) belonging to the labdane diterpene series as well as two known flavones, velutin (5) and chrysoeriol (6). Structure elucidation of the new compounds was carried out using ID and 2D NMR spectroscopic data and single-crystal X-ray crystallography of compound 1. Compounds 1-4 exhibited selective antimycobacterial activity against Mycobacterium tuberculosis with IC50 values in the range 5.02-9.80 mu g/mL.

Nitrite reductase NirBD is induced and plays an important role during in vitro dormancy of mycobacterium tuberculosis - Akhtar, Shamim; Khan, Arshad; Sohaskey, Charles D.; Jagannath, Chinnaswamy; Sarkar, Dhiman (Journal of Bacteriology, 2013)
Mycobacterium tuberculosis is one of the strongest reducers of nitrate among all mycobacteria. Reduction of nitrate to nitrite, mediated by nitrate reductase (NarGHJI) of M. tuberculosis, is induced during the dormant stage, and the enzyme has a respiratory function in the absence of oxygen. Nitrite reductase (NirBD) is also functional during aerobic growth when nitrite is the sole nitrogen source. However, the role of NirBD-mediated nitrite reduction during the dormancy is not yet characterized. Here, we analyzed nitrite reduction during aerobic growth as well as in a hypoxic dormancy model of M. tuberculosis in vitro. When nitrite was used as the sole nitrogen source in the medium, the organism grew and the reduction of nitrite was evident in both hypoxic and aerobic cultures of M. tuberculosis. Remarkably, the hypoxic culture of M. tuberculosis, compared to the aerobic culture, showed 32- and 4-fold-increased expression of nitrite reductase (NirBD) at the transcription and protein levels, respectively. More importantly, a nirBD mutant of M. tuberculosis was unable to reduce nitrite and compared to the wild-type (WT) strain had a >2-log reduction in viability after 240 h in the Wayne model of hypoxic dormancy. Dependence of M. tuberculosis on nitrite reductase (NirBD) was also seen in a human macrophage-based dormancy model where the nirBD mutant was impaired for survival compared to the WT strain. Overall, the increased expression and essentiality of nitrite reductase in the in vitro dormancy models suggested that NirBD-mediated nitrite reduction could be critical during the persistent stage of M. tuberculosis.

One pot solvent free synthesis and in vitro antitubercular screening of 3-aracylphthalides against mycobacterium tuberculosis - Limaye, Rohan A.; Kumbhar, Virendra B.; Natu, Arun D.; Paradkar, Madhusudan V.; Honmore, Varsha S.; Chauhan, Rubia R.; Gample, Suvarna P.; Sarkar, Dhiman (Bioorganic & Medicinal Chemistry Letters, 2013)
One pot synthesis of 3-Aracylphthalide was accomplished in good yield by reacting 2-carboxy benzaldehyde with various aromatic methyl ketones in presence of methane sulphonic acid. Various phthalides thus obtained were characterized with spectral techniques. These phthalides were subjected to in vitro antitubercular screening against Mycobacterium tuberculosis H37Ra (MTB) by using XRMA protocol. Among the phthalides screened, four exhibited half maximal inhibitory concentration (IC50) in the range of 0.81-1.24 mu g/ml thereby providing potential lead compounds for future drug discovery studies. (c) 2012 Elsevier Ltd. All rights reserved.
Keywords: 3-Aracylphthalide; Antitubercular activity; Methane sulphonic acid; One pot synthesis

Advanced cell-based high-throughput screening assays targeting active and latent Mycobacterium tuberculosis - Shurpali, Ketaki Dilip; Singh, Upasana; Sarkar, Shamim Akhtar Sampa; Mishra, Abhishek; Kulkarni, Roshan; Joshi, Swati P.; Sarkar, Dhiman (Journal of Biotechnology, 2014)

Antifungal dimeric chalcone derivative kamalachalcone E from Mallotus philippinensis - Kulkarni, Roshan R.; Tupe, Santosh G.; Gample, Suvarna P.; Chandgude, Macchindra G.; Sarkar, Dhiman; Deshpande, Mukund V.; Joshi, Swati P. (Natural Product Research, 2014)
From the red coloured extract (Kamala) prepared through acetone extraction of the fresh whole uncrushed fruits of Mallotus philippinensis, one new dimeric chalcone (1) along with three known compounds 1-(5,7-dihydroxy-2,2,6-trimethyl-2H-1-benzopyran-8-yl)-3-phenyl-2-propen -1-one (2), rottlerin (3) and 4 `-hydroxyrottlerin (4) were isolated. The structure of compound 1 was elucidated by 1D and 2D NMR analyses that included HSQC, HMBC, COSY and ROESY experiments along with the literature comparison. Compounds 1-4 were evaluated for antifungal activity against different human pathogenic yeasts and filamentous fungi. The antiproliferative activity of the compounds was evaluated against Thp-1 cell lines. Compounds 1 and 2 both exhibited IC50 of 8, 4 and 16 mu g/mL against Cryptococcus neoformans PRL518, C. neoformans ATCC32045 and Aspergillus fumigatus, respectively. Compound 4, at 100 mu g/mL, showed 54% growth inhibition of Thp-1 cell lines.
Keywords: 4 `-hydroxyrottlerin; antifungal; dimeric chalcone; kamalachalcone E; Mallotus philippinensis; rottlerin

Aptamer functionalized multifunctional fluorescent nanotheranostic platform for pancreatic cancer - Nigam, Preeti; Waghmode, Shobha A.; Yeware, Amar M.; Nawale, Laxman U.; Dagde, Priyanka; Dudhane, Amol; Sarkar, Dhiman (Journal of Nanopharm Drug Delivery, 2014)
This study explores the potential of aptamer functionalized and fluorescent silver nanoparticles (AgNPs) labeled human serum albumin nanoparticles for drug delivery and bioimaging. Nanotechnology is certainly the most promising research arena in recent years and different fields of biotechnology, medicine and agricultural have been deeply benefited by the enormous advantages of nanotechnology. In recent years, synthesis of nanoparticles via eco-friendly methods has attained a lot of interest and silver nanoparticles are synthesized extensively due to their size tunable properties and vast applicability in different areas. In this study we have explored green synthesized fluorescent silver nanoparticles as a novel bioimaging agent for pancreatic cancer. Capsaicin, a plant phytochemical found in red chilli pepper was encapsulated in aptamer MUC-1 coupled albumin nanoparticles and it was observed that the nanoformulation significantly enhanced the bioavailability and sustained release property of the drug to pancreatic cancer cells in-vitro. Meanwhile AgNPs mediated excellent bioimaging has enhanced the efficacy of our system as drug delivery vehicle.

Graphene quantum dots conjugated albumin nanoparticles for targeted drug delivery and imaging of pancreatic cancer - Nigam, Preeti; Waghmode, Shobha; Louis, Michelle; Wangnoo, Shishanka; Chavan, Pooja; Sarkar, Dhiman (Journal of Materials Chemistry B, 2014)
Pancreatic cancer is considered to be the deadliest of all cancers due to its poor prognosis and resistance to conventional therapies. In this study, the potential of hyaluronic acid functionalized and green fluorescent graphene quantum dot (GQD)-labeled human serum albumin nanoparticles for pancreatic cancer specific drug delivery and bioimaging was explored. GQDs with tunable fluorescence properties and biocompatibility have attracted much more interest in recent years as compared to their metal semiconductor counterparts. We adopted lawsone (2-hydroxy-1,4-naphthoquinone) as a novel reducing agent for the synthesis of quantum dots and, in addition to excellent fluorescence of the synthesized GQDs, a good quantum yield of similar to 14% was also obtained. Gemcitabine, the most preferred drug for pancreatic cancer treatment, was encapsulated in albumin nanoparticles, and it was observed that our nanoformulation significantly enhanced the bioavailability and sustained release property of the drug to pancreatic cancer cells in vitro. Moreover, the GQD-mediated bioimaging was excellent and enhanced the efficacy of our system as a drug delivery vehicle.

Highly efficient one-pot multi-component synthesis of alpha-aminophosphonates and bis-alpha-aminophosphonates catalyzed by heterogeneous reusable silica supported dodecatungstophosphoric acid (DTP/SiO2) at ambient temperature and their antitubercular eval - Mulla, Shafeek Abdul Rashid; Pathan, Mohsinkhan Y.; Chavan, Santosh S.; Gample, Suvarna P.; Sarkar, Dhiman (RSC Advances, 2014)
A highly efficient one-pot multi-component reaction (MCR) protocol over DTP/SiO2 has been developed for the synthesis of alpha-aminophosphonate derivatives (4a-x) in excellent yields. The alpha-aminophosphonate derivatives were for the first time evaluated for their antitubercular activity against the M. tuberculosis H37Ra (MTB) strain. An evaluation of the data on the cytotoxicity and antimicrobial activity shows that 4n and 4v are promising antitubercular agents.

1,2,3-Triazole derivatives as antitubercular agents: synthesis, biological evaluation and molecular docking study - Shaikh, Mubarak H.; Subhedar, Dnyaneshwar D.; Nawale, Laxman; Sarkar, Dhiman; Khan, Firoz A. Kalam; Sangshetti, Jaiprakash N.; Shingate, Bapurao B. (MedChemComm, 2015)
Searching for new active molecules against Mycobacterium tuberculosis (MTB) H37Ra, a small focused library of 1,2,3-triazoles has been efficiently prepared via a click chemistry approach. The newly synthesized compounds were tested against drug-sensitive MTB. Several derivatives were found to be promising inhibitors of MTB characterized by lower MIC values (5.8-29.9 mu g mL(-1)). Among all the synthesized 31 compounds, 15e was the most active compound against MTB. Based on the results from the antitubercular activity, SAR for the synthesized series has been developed. The active compounds from the anti-tubercular study were further tested for anti-proliferative activity against THP-1, A549 and PANC-1 cell lines using MTT assay and showed no significant cytotoxic activity against these three cell lines except THP-1 at the maximum concentration evaluated. Further, the synthesized compounds were found to have potential antioxidant activities with an IC50 range of 10.1-37.3 mu g mL(-1). The molecular docking study of the synthesized compounds was performed against the DprE1 enzyme of MTB to understand the binding interactions. Moreover, the synthesized compounds were also analysed for ADME properties and all the experimental results promote us to consider this series as a starting point for the development of novel and more potent anti-tubercular agents in the future.

Analyzing different acetyl co-a metabolizing enzymes as potential drug targets against mycobacterium tuberculosis - Akhtar, Shamim; Singh, Sheetal; Kumar, Santosh; Sarkar, Dhiman (British Microbiology Research Journal, 2015)
Mycobacterium tuberculosis, the causative agent of tuberculosis, is responsible for the deaths of million people around the globe. The scenario is worse than ever due to the emergence of drug resistant strains which are widely spread throughout the globe in much faster ways. To control this worst situation, we need to speed up the search for novel drugs which can specifically kill drug resistant bacteria in collaborative ways amongst academic, clinician and industry. Among different metabolic pathways, fatty acid synthesis pathway has always been a very attractive area for the drug target because of its crucial role during the infection and further in long term survival of pathogen inside the human host. In this review article, we analyzed the role of important and crucial enzymes, which are responsible for the influx and efflux of acetyl co-A substrate, a central hub of metabolites, as potential drug targets against M. tuberculosis.

Antimycobacterium activity of coumarins from fruit pulp of aegle marmelos (L.) correa - Chinchansure, Ashish A.; Shamnani, Neelam; Arkile, Manisha A.; Sarkar, Dhiman; Joshi, Swati P. (International Journal of Basic and Applied Chemical Sciences, 2015)
Phytochemical investigation of n-butanol fraction of acetone extract of Aegle marmelos fruit has afforded four compounds coumarins marmelosin (1), marmin (2) and xanthotoxol (3) and flavonoid kaempferol 3- O-rhamnoside, afzelin (4). All the isolated compounds were evaluated for their antimycobacterium activity against Mycobacterium tuberculosis H37Ra and Mycobacterium bovis. Compounds 1 and 2 exhibited antimycobacterium activity against M. tuberculosis H37Ra with an IC50 12.46 µg/mL and 4.31 µg/mL respectively whereas, at 100 µg/mL, 62.5% and 82.4% growth inhibition of M. bovis was observed respectively. Compounds 1 and 2 were also evaluated against two gram positive bacteria Staphylococcus aureus, Bacillus subtilis and one gram negative bacteria Escherichia coli. Compound 1 at 100 µg/mL, showed growth inhibition, 64.6% and 74.9% of E. coli and B. subtilis respectively.

Chemical and biological metal nanoparticles as antimycobacterial agents: a comparative study - Singh, Richa; Nawale, Laxman U.; Arkile, Manisha A.; Shedbalkar, Utkarsha U.; Wadhwani, Sweety A.; Sarkar, Dhiman; Chopade, Balu Ananda (International Journal of Antimicrobial Agents, 2015)
Resistance among mycobacteria leading to multidrug-resistant and extensively drug-resistant tuberculosis is a major threat. However, nanotechnology has provided new insights in drug delivery and medicine development. This is the first comparative report to determine the activity of chemically and biologically synthesised silver nanoparticles (AgNPs) and gold nanoparticles (AuNPs) against mycobacteria. Screening data revealed the high mycobactericidal efficiency of AgNPs, with minimum inhibitory concentrations (MICs) of <3 mu g/mL, whereas no such activity was exhibited by AuNPs at concentrations up to 100 mu g/mL. Moreover, in vitro and ex vivo THP-1 infection model assays showed greater efficacy of chemical AgNPs compared with biogenic AgNPs to inhibit active and dormant stage mycobacterial growth. Up to 40% cytotoxicity against human cell lines was observed at a AgNP concentration of 10 x MIC (30 mu g/mL) after 48 h. AgNPs were shown to have more specificity towards mycobacteria than towards other Gram-negative and Gram-positive pathogenic bacteria. The selectivity index was found to be in the range of 11-23, indicating the potential of these nanoparticles for use in developing new therapeutics for tuberculosis. (C) 2015 Elsevier B.V. and the International Society of Chemotherapy. All rights reserved.
Keywords: Antibiotic resistance; Antimycobacterial agent; Cytotoxicity; Mycobacteria; Nanoparticles; tuberculosis

Design and synthesis of 11 alpha-substituted bile acid derivatives as potential anti-tuberculosis agents - Pore, Vandana S.; Divse, Jaisingh M.; Charolkar, Chaitanya R.; Nawale, Laxman U.; Khedkar, Vijay M.; Sarkar, Dhiman (Bioorganic & Medicinal Chemistry Letters, 2015)
We have synthesized a series of novel 11 alpha-triazoyl bile acid derivatives. In addition, we also have synthesized N-alkyl and N-acyl derivatives of C-11 amino bile acid esters. All the compounds were evaluated for the inhibitory activity against Mycobacterium tuberculosis H37Ra (MTB) at 30 mu g/mL level. Four lead compounds (2b, 3, 7 and 8) were further confirmed from their dose dependent effect against MTB. These compounds were found to be active against Dormant and active stage MTB under both in vitro as well as within THP1 host macrophages. The most promising compound 2b showed strong antitubercular activities against MTB under in vitro and ex vivo (IC90 value of similar to 3 mu g/mL) conditions and almost insignificant cytotoxicity up to 100 mu g/mL against THP-1, A549 and PANC-1 human cancer cell lines. Inactivity of all these compounds against Gram positive and Gram negative bacteria indicates their specificity. Molecular docking studies of these compounds into the active site of DprE1 enzyme revealed a similar binding mode to native ligands in the crystal structure thereby helping to establish a structural basis of inhibition of MTB. The synthesized compounds were analyzed for ADME properties and showed potential to develop good oral drug candidates. Our results clearly indicate the identification of some novel, selective and specific inhibitors against MTB that can be explored further for potential antitubercular drug. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Antituberculosis; Bile acids; Cycloaddition; Docking study; In silico ADME

Design and synthesis of a focused library of diamino triazines as potential mycobacterium tuberculosis DHFR inhibitors - Lele, Arundhati C.; Raju, Archana; Khambete, Mihir P.; Ray, M. K.; Rajan, M. G. R.; Arkile, Manisha A.; Jadhav, Nandadeep J.; Sarkar, Dhiman; Degani, Mariam S. (ACS Medicinal Chemistry Letters, 2015)
We report design of a series of 2,4-diamino triazines as Mycobacterium tuberculosis (Mtb) dihydrofolate reductase inhibitors. The synthesized compounds were evaluated against Mtb (H(37)Rv and Dormant stage H37Ra), their cytotoxicity was assessed (HepG2 and A549 cell lines), and selectivity toward Mtb was evaluated by testing against other bacterial strains. Some derivatives showed promising activity along with low cytotoxicity. The most potent compound in the whole cell assay (MIC 0.325 mu M against H(37)Rv) showed selectivity in the enzyme assay and exhibited synergy with second line anti-TB agent p-amino salicylic acid. This study therefore provides promising molecules for further development as antituberculosis DHFR inhibitors.
Keywords: Diamino triazine; dihydrofolate reductase; enzyme assay; molecular modeling; Mycobacterium tuberculosis; selectivity; synergy

Discovery of new chemical entities against diseases of national importance :an HTS approach - Nawale, Laxman; Sarkar, Dhiman (National Science Day, At CSIR-NCL, 2015)

Efficacy study of potential anti-tubercular molecules: in-vitro and ex-vivo - Nawale, Laxman; Sarkar, Dhiman (National Science Day, 2015)
Tuberculosis: Infectious disease caused by the bacillus Mycobacterium tuberculosis Second leading infectious killer after HIV/AIDS In 2013, 8.6 million TB cases were reported out of which 1.3 million died Emergence of Multi-drug resistant TB (MDR-TB) and extremely drug resistant TB (XDR) for which no drugs are available. Latency being a cause of recurring TB infection is a major problem in eradication of TB

High throughput screening of inhibitors for tuberculosis at NCL : a novel drug discovery initiative from CSIR - Manek, Hardik; Nawale, Laxman; Jadhav, Nandadeep J.; Sarkar, Dhiman (73rd CSIR Foundation Day, at CSIR-National Chemical Laboratory, Pune, 2015)
Discover and develop novel drugs that are effective at curing latent, drug sensitive and drug resistant TB Study the biology of tuberculosis bacilli in great detail to identify new metabolic pathways that may be vulnerable to drugs Test thousands of potential drugs in our screening facility to find new compounds or new compound classes that kill TB bacteria Increase throughput up to 20,000 compounds at a time Develop novel screens using conditions that mimic those the TB bacteria encounters in the human body Utilize medical chemistry to optimize the structures of compounds so that they kill TB bacteria in a more potent fashion and are non-toxic Meet the challenges from industry

Intrinsic therapeutic and biocatalytic roles of ionic liquid mediated self-assembled platinum-phytase nanospheres - Soni, Sarvesh K.; Sarkar, Sampa; Selvakannan, P. R.; Sarkar, Dhiman; Bhargava, Suresh Kumar (RSC Advances, 2015)
We herein report the inherent antitumor efficiency of self-assembled phytase enzyme nanospheres and enhance their efficiency by decorating with platinum nanoparticles and with the anticancer drug curcumin. Firstly, controlled self-assembly of phytase enzyme in an Ionic Liquid 1-butyl-3-methylimidazolium tetrafluoroborate [Bmim][BF4], led to the formation of therapeutically active phytase nanospheres. These nanospheres were further decorated with platinum nanoparticles by adding the platinum ions to these spheres and the nanoparticles formation was mediated by the specific interaction between the histidine residue (in active site of phytase enzymes) and the platinum ions and subsequent reduction of the ions into nanoparticles. The enzyme spheres act as a functional soft template for the as-formed platinum nanoparticles. These Platinum decorated hybrid biomacromolecular phytase nanospheres were loaded with the anticancer drug curcumin and all the different kinds of nanospheres were subjected to in vitro cytotoxicity for their anticancer effect on three different kinds of cancer cell lines i.e. MCF-7, Hep-G2 and THP-1 derived human macrophages. We observed a gradual increase in the anticancer effect caused by only phytase nanospheres (25%), platinum-phytase nanospheres (37%), phytase-curcumin (78%) and platinum-phytase-curcumin nanospheres (90%) that establishes this protein based system as a robust combinatorial drug delivery vehicle. The platinum-phytase spheres also proved their usability as a highly efficient green and reusable biocatalytic system for phytate degradation. The present work facilitates our understanding of ionic liquid based synthesis for multifunctional protein based drug delivery vehicles incorporating combinatorial chemotherapy for potential application as biopharmaceutical agents for tumor treatment and bio-catalysis.

Leucas mollissima, a source of bioactive compounds with antimalarial and antimycobacterium activities - Chinchansure, Ashish A.; Arkile, Manisha A.; Shukla, Anurag; Shanmugam, Dhanasekaran; Sarkar, Dhiman; Joshi, Swati P. (Planta Medica Letter, 2015)
A phytochemical investigation of the acetone extract from the aerial parts of Leucas mollissima afforded one new (−)epi-marmelo lactone, (2 S, 4R, 6 S)-2,6-dimethyl-6 hydroxy-7-ene-4-olide (1), along with five known compounds, schensianol A (2), vanillin (3), β-hydroxy propiovanillone (4), lanost-9(11),25-diene-3β,24β-diol (5), and lanost-9(11),23E(24)-diene-3β,25-diol (6). Similarly, an investigation of the methanol extract of the aerial parts of L. mollissima resulted in the isolation of three known compounds, (+)-syringaresinol (7), anisofolin A (8), and apigenin 7-O-β-D(− 6′′-p-E-coumaroyl)-glucoside (9). Structure elucidation of the isolated compounds was carried out using detailed analysis of 1D and 2D nuclear magnetic resonance. All compounds were evaluated for antimalarial activity against Plasmodium falciparum (3D7) and for antimycobacterium activity against Mycobacterium tuberculosis H37Ra and Mycobacterium bovis. Compound 8 was found to have promising antimalarial activity (IC50 4.39 ± 0.25 µM), promising antimycobacterium activity [IC50 4.50 ± 0.75 µM (3.31 µg/mL)] against M. tuberculosis H37Ra and at 100 µg/mL, showed 55.6 % inhibition of M. bovis. Compound 9 showed moderate inhibition of P. falciparum growth (35 % inhibition at 10 µM) with respect to the positive control atovaquone and 67.4 % inhibition against M. bovis at 100 µg/mL with respect to the positive control rifampicin.

Mechanistic understanding of rapid gelation of silk fibroin using a biosurfactant – sophorolipid - Dubey, Parul; Nawale, Laxman; Sarkar, Dhiman; Nisal, Anuya; Prabhune, Asmita (National Science Day, At CSIR-NCL, 2015)
3D polymeric hydrogels find use in biomedical applications as scaffolds and drug delivery vehicle • Silk fibroin a structural protein is a promising candidate (excellent thermo-mechanicals, biocompatibility, biodegradability) • Sophorolipid (SL)-a biosurfactant is known to exhibit antimicrobial, anti cancerous and cell differentiating. • Use of SL as gelling agent can enhance the applicability of SF hydrogels • SF-SL scaffolds obtained by lyophilization of hydrogels can find application in tissue regeneration

Multifunctional silica nanoparticles for pancreatic cancer specific drug delivery and bioimaging - Nigam, Preeti; Sarkar, Dhiman (Journal of Chemistry & Applied Biochemistry, 2015)
Mesoporous silica nanoparticles (MSN) have attracted increasing interest as drug carriers due to their biocompatibility and robustness. In this analysis we explored the potential of MSN as nanotheranostic platform for pancreatic cancer specific drug delivery and bioimaging. Pancreatic cancer is the most fatal cancer and due to its high mortality and low prognosis it is imperative to develop new methods for early diagnosis and therapy of this cancer. Though traditionally organic dyes, quantum dots and fluorescent agents are used for bioimaging but here we have utilized graphene quantum dots (GQDs) for bioimaging due to their superior biocompatibility and fluorescence properties. MSN were loaded with gemcitabine; the most preferred drug for pancreatic cancer. MSN and GQDs were characterized by SEM, TEM, FT-IR etc and the efficacy of nanoformulation was determined by MTT assay.

New butenolide cinnamate and other biological active chemical constituents from Polygonum glabrum - Said, Madhukar S.; Chinchansure, Ashish A.; Nawale, Laxman; Durge, Ankita; Wadhwani, Ashish; Kulkarni, Smita S.; Sarkar, Dhiman; Joshi, Swati P. (Natural Product Research, 2015)
Phytochemical investigation of the methanol extract of the aerial parts of Polygonum glabrum afforded one new natural product (-)-2-methoxy-2-butenolide-3-cinnamate (1) along with six known compounds, -hydroxyfriedalanol (2), 3-hydroxy-5-methoxystilbene (3), (-) pinocembrin (4), sitosterol-(6-O-palmitoyl)-3-O–d-glucopyranoside (5), (-) pinocembrin-5-methyl ether (6) and sitosterol-3-O–d-glucopyranoside (7). Compound 1 showed promising in vitro anti-HIV-1 activity against primary isolates HIV-1(UG070) (X4, subtype D) and HIV-1(VB59) (R5, subtype C) assayed using TZM-bl cell line with IC50 in the range of 15.68-22.43g/mL. The extract showed TI in the range of 19.19-27.37 with IC50 in the range of 10.90-15.55g/mL. Compounds 1, 3 and 4 exhibited in vitro anti-mycobacterium activity against Mycobacterium tuberculosis H37Ra with IC50 values of 1.43, 3.33 and 1.11g/mL in dormant phase and 2.27, 3.33 and 1.21g/mL in active phase, respectively. Compound 4 was found to be the most active antiproliferative with IC50 values of 1.88-11.00g/mL against THP-1, A549, Panc-1, HeLa and MCF7 cell lines.
Keywords: anti-HIV-1; anti-mycobacterium; antiproliferative; phytochemicals; Polygonaceae; Polygonum glabrum

Qualitative and quantitative proteomic analysis of vitamin C induced changes in mycobacterium smegmatis - Mishra, Abhishek; Sarkar, Dhiman (Frontiers in Microbiology, 2015)
Vitamin C is a critical dietary nutrient in human which has a wide range of regulatory effects on gene expression and physiology of Mycobacterium tuberculosis that leads to a dormant drug-tolerant phenotype. In the presence of iron, vitamin C shows a high bactericidal activity even in the drug resistant phenotype of M. tuberculosis. The regulatory mechanisms underlying vitamin C induced adaptations are largely unknown due to lack of functional genomics data in this field. In this study, we attempt to characterize the direct effect of vitamin C treatment on the physiology of actively growing Mycobacterium smegmatis. The study chose M. smegmatis as it is a fast-growing bacterium and a non-pathogenic model system which shares many physiological features with the pathogenic M. tuberculosis including dormancy and its regulation. The proteomic adaptation of M. smegmatis on vitamin C treatment demonstrates the important changes in cellular and metabolic process such as reversal of tricarboxylic acid cycle, decrease in ATP synthesis, decrease in iron acquisition and storage, and induction of dormancy regulators WhiB3, PhoP, and Lsr2.
Keywords: dormancy; Mycobacterium smegmatis; proteomics; tuberculosis; vitamin C

Quantitative, automated, high content screening assay approach to anti-angiogenicdrug discovery - Nawale, Laxman; Sarkar, Dhiman (National Science Day, At CSIR-NCL, 2015)
Angiogenesisenhancescancer,maculardegeneration,etc.. Currentangiogenicassays--indirect,manual,timeconsuming,laborintensive,difficulttoquantify,andexpensive. Wedevelopedanautomated,quantitative,HighContentScreeningangiogenictubeformationassaywouldbenefitdrugdiscoveryforseveraltherapeuticareas. Humanendothelialcellswereseededwithpro-oranti-angiogeniccompoundsonaMatrigelTMlayerina96-wellplate.Afterangiogenictubesformation,thepositivecontrolsandthetestsampleswerefixed,fluorescentlylabeled,automaticallyimagedonCellomics’ArrayScan®HCSReader,andquantitativelyanalyzedon-the-flybytheTubeFormationBioApplicationsoftwaremodule. Multiplefeaturesrelevantforangiogenesisandangiogenictubeformationwereautomaticallymeasured. Thisrobustandreliableassaythusenabledthelarge-scale,quantitative,screeningandcharacterizationofcompoundsaffectingbothpro-andanti-angiogenicpathways.

Rational drug design, synthesis and biological evaluation of dihydrofolate reductase inhibitors as antituberculosis agents - Tawari, Nilesh R.; Bag, Seema; Raju, Archana; Lele, Arundhati C.; Bairwa, Ranjeet; Ray, Mukti Kanta; Rajan, M. G. R.; Nawale, Laxman U.; Sarkar, Dhiman; Degani, Mariam S. (Future Medicinal Chemistry, 2015)
Background: A series of 2,4-diamino-s-triazines was designed, with potential for activity against Mycobacterium tuberculosis (Mtb) dihydrofolate reductase enzyme, on the basis of virtual screening results and structure-based drug design. Results: The compounds were evaluated against Mtb (H(37)Rv) and their cytotoxicity was assessed using VERO cell lines. Of particular note, two compounds were found to have the most promising antituberculosis activity (6b minimum inhibitory concentration: 1.76 mu M and 6i minimum inhibitory concentration: 1.57 mu M) along with low cytotoxicity (CC50 : > 300 mu M). The enzyme assay results of these two indicated significant inhibition of Mtb dihydrofolate reductase along with selectivity. Selected derivatives were tested against dormant tubercle bacilli in vivo and ex vivo indicating potential inhibition. Conclusion: This study provides promising antituberculosis dihydrofolate reductase inhibitors that can act as potential leads for further development.

Rottlerin derivatives and other compounds from mallotus philippinensis fruits and their potential antimycobactrial activity - Bhardwaj, Rima; Chinchansure, Ashish A.; Kulkarni, Roshan R.; Arkile, Manisha A.; Sarkar, Dhiman; Joshi, Swati P. (Planta Medica Letters, 2015)
The methanolic extract of the fruits of Mallotus philippinensis afforded 13 compounds, 7,11-diketo-lanost-3-ol (1, as acetate), lanosta-8-ene-3β-ol (2, as acetate), pregnenolone (3, as acetate), trans-chalcone (4), kamalachalcone E (5), oleanolic acid (6), gallic acid (7), kaempferol (8), myricetin (9), 1-(5,7-dihydroxy-2,2,6-trimethyl-2 H-1-benzopyran-8-yl)-3-phenyl-2-propen-1-one (10), 4′-hydroxyisorottlerin (11), rottlerin (12), and shikimic acid (13). Compound 1 was isolated as a new natural product and its structure was elucidated by 1D and 2D nuclear magnetic resonance analyses including heteronuclear single quantum correlation, heteronuclear multiple-bond correlation, correlation spectroscopy, and nuclear Overhauser effect spectroscopy experiments. All of the isolated compounds were evaluated for their antimycobacterium activity against Mycobacterium tuberculosis H37Ra. Compounds 11 and 12 exhibited promising inhibitory activity with IC50 values of 0.89 ± 0.33 µg/mL (MIC 2.06 ± 0.41 µg/mL) and 7.59 ± 0.42 µg/mL (MIC 11.56 ± 0.35 µg/mL), respectively.

Sophorolipid assisted tunable and rapid gelation of silk fibroin to form porous biomedical scaffolds - Dubey, Parul; Nawale, Laxman; Sarkar, Dhiman; Nisal, Anuya; Prabhune, Asmita (RSC Advances, 2015)
Three dimensional polymer hydrogels, based on both natural and synthetic polymers, are increasingly being used as scaffolds and drug delivery vehicles for biomedical applications. Fibrous protein, silk fibroin (SF), obtained from the Bombyx mori silkworm is a promising candidate in this area. However, SF has a long gelation time of about a few weeks that can only be reduced by non-physiological treatments (e. g. high temperature, ultrasonication and low pH) or by addition of a chemical and non-biodegradable polymer and/or surfactant. We report here accelerated gelation of SF under physiological conditions using a biosurfactant, sophorolipid (SL) as a gelling agent. SL and SF are completely miscible and form a very clear solution upon mixing. Hence it is interesting to see that this clear solution gels in a time span of just a few hours. The hydrogels so formed have pore architecture, porosities and mechanical stability ideally suited for tissue culture applications. Here we also demonstrate that mouse fibroblast cells not only adhere to but also extensively proliferate on these SF-SL scaffolds.

Synthesis and evaluation of thieno[2,3-d]pyrimidin-4(3H)-ones as potential antitubercular agents - Borate, Hanumant B.; Annadate, Ritesh A.; Vagh, Sandip S.; Pisal, Mahesh M.; Deokate, Sagar B.; Arkile, Manisha A.; Jadhav, Nandadeep J.; Nawale, Laxman U.; Sarkar, Dhiman (MedChemComm, 2015)
A number of thieno[2,3-d]pyrimidin-4(3H)-ones were designed, synthesized and screened against Mycobacteria as a part of our program to develop new antitubercular agents. It was observed that some of the compounds have significant antimycobacterial activity against Mycobacterium tuberculosis H37Ra (ATCC 25177) and Mycobacterium bovis BCG (ATCC 35743). The active compounds were studied for cytotoxicity against four cell lines and were found to be non-cytotoxic. The results showed that compounds 13b and 29e were found to exhibit very good antimycobacterial activity (MIC in the range of 6-8 mu M) and the thienopyrimidinones as a class have potential to be developed as antitubercular agents.

Targeting dormant tuberculosis bacilli: results for molecules with a novel pyrimidone scaffold - Joshi, Rohit R.; Barchha, Avinash; Khedkar, Vijay M.; Pissurlenkar, Raghuvir R. S.; Sarkar, Sampa; Sarkar, Dhiman; Joshi, Rohini R.; Joshi, Ramesh A.; Shah, Anamik K.; Coutinho, Evans C. (Chemical Biology & Drug Design, 2015)
Our inability to completely control TB has been due in part to the presence of dormant mycobacteria. This also renders drug regimens ineffective and is the prime cause of the appearance of drug-resistant strains. In continuation of our efforts to develop novel antitubercular agents that especially target dormant mycobacteria, a set of 55 new compounds belonging to the pyrimidone class were designed on the basis of CoMFA and CoMSIA studies, and these were synthesized and subsequently tested against both the dormant and virulent BCG strain of M.tuberculosis. Some novel compounds have been identified which selectively inhibit the dormant tuberculosis bacilli with significantly low IC50 values. This study reports the second molecule after TMC-207, having the ability to inhibit tuberculosis bacilli exclusively in its dormant phase. The synthesis was accomplished by a modified multicomponent Biginelli reaction. A classification model was generated using the binary QSAR approach - recursive partitioning (RP) to identify structural characteristics related to the activity. Physicochemical, structural, topological, connectivity indices, and E-state key descriptors were used for generation of the decision tree. The decision tree could provide insights into structure-activity relationships that will guide the design of more potent inhibitors.
Keywords: Antitubercular activity; dormant tuberculosis bacilli; pyrimidones; recursive partitioning

Design, synthesis and biological evaluation of novel azaspiro analogs of linezolid as antibacterial and antitubercular agents - Gadekar, Pradip K.; Roychowdhury, Abhijit; Kharkar, Prashant S.; Khedkar, Vijay M.; Arkile, Manisha A.; Manek, Hardik; Sarkar, Dhiman; Sharma, Rajiv; Vijayakumar, V.; Sarveswari, S. (European Journal of Medicinal Chemistry, 2016)
The design, synthesis and antimicrobial evaluation of a novel series of azaspiro analogues of linezolid (1) have been described. Linezolid comprises of a morpholine ring which is known for its metabolism related liabilities. Therefore, the key modification made in the linezolid structure was the replacement of morpholine moiety with its bioisostere, 2-oxa-6-azaspiro[3.3]heptane. Furthermore, the replacement of N-acetyl terminal of 1 with various aromatic or aliphatic functionalities was carried out. The title compounds were evaluated against a panel of Gram-positive and Gram-negative bacteria and Mycobacterium tuberculosis. Subsequent structure-activity relationship (SAR) studies identified several compounds with mixed antibacterial and antitubercular profiles. Compound 22 (IC50 0.72, 0.51, 0.88, 0.49 mu g/mL for Escherichia coli, Pseudomonas aeruginosa, Staphylococcus aureus, Bacillus subtilis, respectively) exhibited similar antibacterial profile as I. The N-acetyl derivative 18 was similar to 1 in antitubercular profile. Thus, the present study successfully demonstrated the use of azaspiro substructure in the medicinal chemistry of antibacterial and antitubercular agents. (C) 2016 Elsevier Masson SAS. All rights reserved.

[Et3NH][HSO4] catalyzed efficient synthesis of 5-arylidene-rhodanine conjugates and their antitubercular activity - Subhedar, Dnyaneshwar D.; Shaikh, Mubarak H.; Nawale, Laxman; Yeware, Amar; Sarkar, Dhiman; Shingate, Bapurao B. (Research on Chemical Intermediates, 2016)
We have described a highly efficient, safer protocol for the synthesis of 5-arylidene-rhodanine conjugates catalyzed by Bronsted acidic ionic liquid [Et3NH][HSO4] in excellent yields. The protocol offers cost-effective, environmentally benign, solvent-free conditions and recycle-reuse of the catalyst. The synthesized 5-arylidene-rhodanine conjugates were characterized on the basis of (1) H NMR, C-13 NMR and HRMS spectral data. A series of 5-arylidene-rhodanine derivatives 3a-h, 4a-h were synthesized and evaluated for their in vitro antitubercular activity against dormant Mycobacterium tuberculosis H37Ra and M. bovis BCG strains. Moreover, compounds 3a, 3b, 3e, 3f, 3g, 3h and 4f exhibited good antitubercular activity and were also evaluated for anti-proliferative activity against MCF-7, A549 and HCT116 cell lines using modified MTT assay and found to be noncytotoxic. Compounds 3a-h and 4f were further screened for their antibacterial activity against four bacteria strains to assess their selectivity towards M. tuberculosis. Furthermore, in silico ADME prediction of all the tested compounds followed the criteria for orally active drug and, therefore, these compounds may have a good potential for eventual development as oral agents.

Facile synthesis of 1,3-thiazolidin-4-ones as antitubercular agents - Subhedar, Dnyaneshwar D.; Shaikh, Mubarak H.; Arkile, Manisha A.; Yeware, Amar; Sarkar, Dhiman; Shingate, Bapurao B. (Bioorganic & Medicinal Chemistry Letters, 2016)
We have developed, highly efficient, one-pot, solvent-free, [Et3NH][HSO4] catalyzed multicomponent reaction protocol for the synthesis of 1,3-thiazolidin-4-ones in excellent yields. For the first time, the 1,3-thiazolidin-4-ones were evaluated in vitro for their antimycobacterial activity against Mycobacterium tuberculosis dormant MTB H37Ra and Mycobacterium bovis BCG strains. Among the synthesized basic 1,3-thiazolidin-4-ones, particularly the compounds 4c, 4d, 4e, 4f, 4h, 4i and 4j displays promising antitubercular activity along with no significant cytotoxicity against the cell lines MCF-7, A549 and HCT-116. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Antitubercular; Cytotoxicity; Green protocol; Multicomponent reaction

Graphene quantum dots - from emergence to nanotheranostic applications - Joshi, Preeti Nigam; Kundu, Subir; Sanghi, Sunil K.; Sarkar, Dhiman (Smart Drug Delivery System, 2016)

GSH Induced controlled release of levofloxacin from a purpose-built prodrug: luminescence response for probing the drug release in escherichia coli and staphylococcus aureus - Pal, Suman; Ramu, Vadde; Taye, Nandaraj; Mogare, Devraj G.; Yeware, Amar M.; Sarkar, Dhiman; Reddy, D. Srinivasa; Chattopadhyay, Samit; Das, Amitava (Bioconjugate Chemistry, 2016)
Fluoroquinolones are third-generation broad spectrum bactericidal antibiotics and work against both Gram-positive and Gram-negative bacteria. Levofloxacin (L), a fluoroquinolone, is widely used in anti-infective chemotherapy and treatment of urinary tract infection and pneumonia. The main pathogen for urinary tract infections is Escherichia colt, and Streptococcus pneumoniae is responsible for pneumonia, predominantly a lower respiratory tract infection. Poor permeability of L leads to the use of higher dose of this drug and excess drug in the outer cellular fluid leads to central nervous system (CNS) abnormality. One way to counter this is to improve the lipophilicity of the drug molecule, and accordingly, we have synthesized two new Levofloxacin derivatives, which participated in the spatiotemporal release of drug via disulfide bond cleavage induced by glutathione (GSH). Recent studies with Streptococcus mutants suggest that it is localized in epithelial lining fluid (ELF) of the normal lower respiratory tract and the effective [GSH] in ELF is similar to 430 mu M. E. coli typically cause urinary tract infections and the concentration of GSH in porcine bladder epithelium is reported as 0.6 mM for a healthy human. Thus, for the present study we have chosen two important bacteria (Gram + ve and Gram - ve), which are operational in regions having high extracellular GSH concentration. Interestingly, this supports our design of new lipophilic Levofloxacin based prodrugs, which released effective drug on reaction with GSH. Higher lipophilicity favored improved uptake of the prodrugs. Site specific release of the drug (L) could be achieved following a glutathione mediated biochemical transformation process through cleavage of a disulfide bond of these purpose-built prodrugs. Further, appropriate design helped us to demonstrate that it is possible also to control the kinetics of the drug release from respective prodrugs. Associated luminescence enhancement helps in probing the release of the drug from the prodrug in bacteria and helps in elucidating the mechanistic pathway of the transformation. Such an example is scarce in the contemporary literature.

In vitro and ex vivo antitubercular activity of diarylheptanoids from the rhizomes of alpinia officinarum hance - Honmore, Varsha S.; Rojatkar, Supada R.; Nawale, Laxman U.; Arkile, Manisha A.; Khedkar, Vijay M.; Natu, Arun D.; Sarkar, Dhiman (Natural Product Research, 2016)
Phytochemical investigation of methanol extract of the rhizomes of Alpinia officinarum Hance afforded four known diarylheptanoids 1,7-diphenylhept-4-en-3-one (1), 5-hydroxy-1,7-diphenyl-3-heptanone (2), 5-hydroxy-7-(4 ''-hydroxy-3 ''-methoxyphenyl)-1-phenyl-3-heptanone (3), and 7-(4 ''-hydroxy-3 ''-methoxyphenyl)-1-phenyl heptan-3-one (4).The acetate derivative of (4), 7-(4 ''-actetate-3 ''-methoxy phenyl)-1-phenyl heptan-3-one (5), was prepared. These diarylheptanoids exhibited promising in vitro and ex vivo antitubercular activity for the first time against dormant Mycobacterium tuberculosis H37Ra with the IC50 values between 0.3447.69 and 0.1322.91 mu M, respectively. All compounds showed comparable activity against Mycobacterium bovis BCG (dormant phage) and did not show any activity against two gram + ve and two gram -ve bacterial strains. These compounds were also weakly cytotoxic up to 300 mu M against three human cancer cell lines THP-1, Panc-1 and A549.

Isolates of alpinia officinarum hance as COX-2 inhibitors: evidence from anti-inflammatory, antioxidant and molecular docking studies - Honmore, Varsha S.; Kandhare, Amit D.; Kadam, Parag P.; Khedkar, Vijay M.; Sarkar, Dhiman; Bodhankar, Subhash L.; Zanwar, Anand A.; Rojatkar, Supada R.; Natu, Arun D. (International Immunopharmacology, 2016)
Background: Inflammation triggered by oxidative stress can cause various ailments, such as cancer, rheumatoid arthritis, asthma, diabetes etc. In the last few years, there has been a renewed interest in studying the antioxidant and anti-inflammatory action of plant constituents such as flavonoids and diarylheptanoids. Aim: To evaluate the antioxidant, anti-inflammatory activity and the total phenolic content of isolated compounds from Alpinia officinarum rhizomes. Furthermore, molecular docking was performed to study the binding mode of these compounds into the active site of cyclooxygenase-2 (COX -2). Methods: A. officinarum rhizomes were extracted by maceration, using methanol. This extract was further fractionated by partitioning with hexane, chloroform and ethyl acetate and these fractions on further purification resulted in isolation of five pure compounds. Characterization was carried out by using H-1 NMR, C-13 NMR and MS. They were further evaluated for antioxidant and anti-inflammatory activity using carrageenan-induced paw edema model in rats. Molecular docking study was performed using Glide module integrated in Schrodinger molecular modeling software. Results: The compounds were identified as 1,7-diphenylhept-4-en-3-one (1), 5-hydroxy-1,7-diphenyl-3-heptanone (2), 3,5,7-trihydroxyflavone (Galangin, 3), 3,5,7-trihydroxy-4'-methoxyflavone (Kaempferide, 4) and 5-hydroxy-7-(4 `'-hydroxy-3 `'-methoxyphenyl)-1-phenyl-3-heptanone (5). The compound-3 and compound-5 (10 mg/kg) showed significant (p < 0.001) antioxidant and anti-inflammatory potential. Moreover, total phenolic content was detected as 72.96 mg and 51.18 mg gallic acid equivalent respectively. All the five isolates were found to be good binders with COX-2 (average docking score -9.03). Conclusions: Galangin and 5-hydroxy-7-(4 `'-hydroxy-3 `'-methoxyphenyl)-1-phenyl-3-heptanone exhibited anti-inflammatory and in-vitro antioxidant activity which may be due to presence of phenolic content in it. The molecular docking study revealed that these compounds have affinity towards COX-2 active site which can further be explored as selective COX-2 inhibitors. The results obtained in this work justify the use of A. officinarum in the treatment of inflammatory disorders like rheumatoid arthritis and inflammatory bowel diseases. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: 5-Hydroxy-7-(4 `'-hydroxy-3 `'-methoxyphenyl)-1-phenyl-3-heptanone; Alpinia officinarum; Anti-inflammatory; Antioxidant; COX-2 inhibitors; Galangin

Naturally occurring anti-TB agents: isolation, chemical transformations and in vitro antitubercular activities of secondary metabolites of rhizomes of alpinia galanga - Valkute, Tushar R.; Arkile, Manisha A.; Sarkar, Dhiman; Bhattacharya, Asish K. (Planta Medica International Open, 2016)
A bioactivity-guided chemical examination of the acetone extract of the rhizomes of Alpinia galanga led to the isolation of six sec-ondary metabolites, eucalyptol derivative (1)andphenylpropa-noids (2–6). The structures of all of the isolated compounds (1–6)wereelucidatedonthebasisoftheirspectraldata.Theisolatedcompounds (1–6)werein vitro assayed against active and dor-mant phenotypes of Mycobacterium tuberculosis H37Ra, respec-tively. Interestingly, 1′S-1′-acetoxychavicol acetate (2)showedgood antitubercular activities against both active and dormantphenotypes of M. tuberculosis with IC50 values of 1.04 µM and2.69 µM, respectively. Tsuji-Trost and homodimerization reac-tions of the active compound (2)respectivelyresultedinthefor-mation of two analogues, 7and 8.Bothofthesesynthesizedana-logues were also found to be active in vitro against active [IC50 sof3.24 and 3.87 µM, respectively, for compounds 7and 8]anddor-mant [IC50 sof8.33and2.41µM,respectively,forcompounds7and 8]phenotypesofM. tuberculosis H37Ra, respectively.

New dinor-cis-labdane diterpene and flavonoids with antimycobacterium activity from colebrookea oppositifolia - Chinchansure, Ashish A.; Arkile, Manisha A.; Shinde, Dinesh R.; Sarkar, Dhiman; Joshi, Swati P. (Planta Medica Letters, 2016)
The new 14,15-dinor-cis-labdane diterpene, named (+)-14,15-dinor-9α-hydroxy-cis-labd-11(E)-en-13-one (1), was isolated from the acetone extract of the aerial parts of Colebrookea oppositifolia, along with the known compounds alnustin (2), mosloflavone (3), flindulatin (4), 5,6,7-trimethoxy baicalein (5), tanetin (6), scutellarein 4′-methyl ether (7), apigenin (8), caffeic acid (9), anisofolin A (10), apigetrin (11), and forsythoside A (12). Structures of the new and known compounds were established by detailed analysis of 1D and 2D nuclear magnetic resonance studies. The isolated compounds 1–12 were evaluated for their antimycobacterium activity against Mycobacterium tuberculosis H37Ra and Mycobacterium bovis in both dormant and active phases. Compounds 1, 7, and 8 exhibited inhibitory activity against M. tuberculosis with IC50 values in the range of 8.1–55.0 µM (MIC 14.4–119.7 µM) in the active phase and 7.4–43.5 µM (MIC 11.5–123.3 µM) in the dormant phase. Similarly 1, 7, and 8 exhibited inhibitory activity against M. bovis with IC50 values in the range of 4.1–98.5 µM (MIC 13.7–161.0 µM) in the active phase and 4.1–111.1 µM (MIC 13.0–166.4 µM) in the dormant phase.

New pimarane diterpenes and other antimycobacterial metabolites from anisochilus verticillatus - Kulkarni, Roshan R.; Shurpali, Ketaki; Khedkar, Vijay M.; Puranik, Vedavati G.; Sarkar, Dhiman; Joshi, Swati P. (Natural Product Research, 2016)
Phytochemical investigation of the acetone extract of the aerial parts of Anisochilus verticillatus afforded a new 8,9-secopimarane diterpene (1), two new isopimarane diterpenes (2, 3) and the known ursolic acid (4), beta-amyrin (5), -amyrin (6), stigmast-5-en-3-one (7) and hydroxychavicol (8). Structures of the new compounds were elucidated with the help of 1D and 2D nuclear magnetic resonance spectroscopic data, and single crystal X-ray crystallography of compound 3. Compounds 2 and 8 inhibited Mycobacterium tuberculosis H37Ra with an IC50 of 11.3 (IC90 of 20.0g/mL) and 12.5g/mL, respectively. Correspondingly, molecular docking studies with Extra Precision Glide revealed a correlation between score and biological activity for these compounds to describe the molecular basis for the most significant SAR results.
Keywords: alanine racemase; Anisochilus verticillatus; antimycobacterial activity; diterpenes; Lamiaceae

Novel tetrazoloquinoline-rhodanine conjugates: highly efficient synthesis and biological evaluation - Subhedar, Dnyaneshwar D.; Shaikh, Mubarak H.; Nawale, Laxman; Yeware, Amar; Sarkar, Dhiman; Khan, Firoz A. Kalam; Sangshetti, Jaiprakash N.; Shingate, Bapurao B. (Bioorganic & Medicinal Chemistry Letters, 2016)
In search of new active molecules against Mycobacterium tuberculosis (MTB) H37Ra and Mycobacterium bovis BCG, a small focused library of rhodanine incorporated tetrazoloquinoline has been efficiently synthesized by using [HDBU][HSO4] acidic ionic liquid. The compound 3c found to be promising inhibitor of MTB H37Ra and M. bovis BCG characterized by lower MIC values 4.5 and 2.0 mu g/mL, respectively. The active compounds were further tested for cytotoxicity against HeLa, THP-1, A549 and PANC-1 cell lines using MTT assay and showed no significant cytotoxic activity at the maximum concentration evaluated. Again, the synthesized compounds were found to have potential antifungal activity. Furthermore, to rationalize the observed biological activity data, the molecular docking study also been carried out against a potential target Zmp1 enzyme of MTB H37Ra, which revealed a significant correlation between the binding score and biological activity for these compounds. The results of in vitro and in silico study suggest that these compounds possess ideal structural requirement for the further development of novel therapeutic agents. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: antifungal; Antitubercular; Cytotoxicity; Docking study; Rhodanine derivatives

Novel tetrazoloquinoline-thiazolidinone conjugates as possible antitubercular agents: synthesis and molecular docking - Subhedar, Dnyaneshwar D.; Shaikh, Mubarak H.; Shingate, Bapurao B.; Nawale, Laxman; Sarkar, Dhiman; Khedkar, Vijay M. (Medchemcomm, 2016)
A novel approach for the synthesis of a new 4-thiazolidinone scaffold was developed by a one-pot three-component cyclocondensation of various tetrazolo quinoline aldehydes 1a-f, acid hydrazide 2a-c, and thioglycolic acid 3 in the presence of [DBUH].OAc] as a catalyst in high yields. All the conjugates were screened for their antimycobacterial activity against MTB H37Ra and M. bovis BCG strains, with the MIC values ranging from 0.99-13.55 mu mol mL(-1) and 0.14-20.11 mu mol mL(-1), respectively. The 4-thiazolidinone-incorporated tetrazoloquinoline derivatives 4a, 4d, 4g, 4j, 4m, and 4p were highly potent against MTB H37Ra and M. bovis BCG strains. The most active compounds were also evaluated for their cytotoxicity against MCF-7, A549, and HCT 116 cell lines and were found to be non-cytotoxic. Further, molecular docking studies into the active site of the InhA enzyme revealed a similar binding mode to the native ligand in the crystal structure, thereby helping us to understand the ligand-protein binding interaction and establish a structural basis for the inhibition of mycobacterium tuberculosis. The results suggest that the tetrazoloquinoline-thiazolidinone conjugates 4a, 4d, 4g, 4j, 4m, and 4p are promising antitubercular agents.

Phytogenic silver, gold, and bimetallic nanoparticles as novel antitubercular agents - Singh, Richa; Nawale, Laxman; Arkile, Manisha A.; Wadhwani, Sweety; Shedbalkar, Utkarsha; Chopade, Snehal; Sarkar, Dhiman; Chopade, Balu Ananda (International Journal of Nanomedicine, 2016)
Purpose: Multi- and extensively drug-resistant tuberculosis (TB) is a global threat to human health. It requires immediate action to seek new antitubercular compounds and devise alternate strategies. Nanomaterials, in the present scenario, have opened new avenues in medicine, diagnosis, and therapeutics. In view of this, the current study aims to determine the efficacy of phytogenic metal nanoparticles to inhibit mycobacteria. Methods: Silver (AgNPs), gold (AuNPs), and gold-silver bimetallic (Au-AgNPs) nanoparticles synthesized from medicinal plants, such as Barleria prionitis, Plumbago zeylanica, and Syzygium cumini, were tested against Mycobacterium tuberculosis and M. bovis BCG. In vitro and ex vivo macrophage infection model assays were designed to determine minimum inhibitory concentration (MIC) and half maximal inhibitory concentration of nanoparticles. Microscopic analyses were carried out to demonstrate intracellular uptake of nanoparticles in macrophages. Besides this, biocompatibility, specificity, and selectivity of nanoparticles were also established with respect to human cell lines. Results: Au-AgNPs exhibited highest antitubercular activity, with MIC of <2.56 mu g/mL, followed by AgNPs. AuNPs did not show such activity at concentrations of up to 100 mu g/mL. In vitro and ex vivo macrophage infection model assays revealed the inhibition of both active and dormant stage mycobacteria on exposure to Au-AgNPs. These nanoparticles were capable of entering macrophage cells and exhibited up to 45% cytotoxicity at 30 mu g/mL (ten times MIC concentration) after 48 hours. Among these, Au-AgNPs synthesized from S. cumini were found to be more specific toward mycobacteria, with their selectivity index in the range of 94-108. Conclusion: This is the first study to report the antimycobacterial activity of AuNPs, AgNPs, and Au-AgNPs synthesized from medicinal plants. Among these, Au-AgNPs from S. cumini showed profound efficiency, specificity, and selectivity to kill mycobacteria. These should be investigated further to develop novel TB nanoantibiotics.
Keywords: Antimycobacterial agent; Cytotoxicity; drug resistance; Mycobacteria; Nanoparticles; tuberculosis

Shape and size engineered cellulosic nanomaterials as broad spectrum anti-microbial compounds - Sharma, Priyanka R.; Kamble, Sunil; Sarkar, Dhiman; Anand, Amitesh; Varma, Anjanikumar (International Journal of Biological Macromolecules, 2016)
Oxidized celluloses have been used for decades as antimicrobial wound gauzes and surgical cotton. We now report the successful synthesis of a next generation narrow size range (25-35 nm) spherical shaped nanoparticles of 2,3,6-tricarboxycellulose based on cellulose I structural features, for applications as new antimicrobial materials. This study adds to our previous study of 6-carboxycellulose. A wide range of bacteria such as Escherichia coli, Staphloccocus aureus, Bacillus subtilis and Mycobacterium tuberculosis (non-pathogenic as well as pathogenic strains) were affected by these polymers in in vitro studies. Activity against Mycobacteria were noted at high concentrations (MIC99 values 250-1000 mu g/ml, as compared to anti-TB drug Isoniazid 0.3 mu g/ml). However, the broad spectrum activity of oxidized celluloses and their nanoparticles against a wide range of bacteria, including Mycobacteria, show that these materials are promising new biocompatible and biodegradable drug delivery vehicles wherein they can play the dual role of being a drug encapsulant as well as a broad spectrum anti-microbial and anti-TB drug. (C) 2016 Published by Elsevier B.V.
Keywords: Anti-microbial; cellulose; Spherical nanoparticles; Tricarboxycellulose

Synthesis and antitubercular activity of new 1,3,4-oxadiazoles bearing pyridyl and thiazolyl scaffolds - Dhumal, Sambhaji T.; Deshmukh, Amarsinh R.; Bhosle, Manisha R.; Khedkar, Vijay M.; Nawale, Laxman U.; Sarkar, Dhiman; Mane, Ramrao A. (Bioorganic & Medicinal Chemistry Letters, 2016)
In search of more potent and safe new antitubercular agents, here new 2-pyridinyl substituted thiazolyl-5-aryl-1,3,4-oxadiazoles (6a-o), have been designed and synthesized using thionicotinamide as a starting, following novel multistep synthetic route. An intermediate, pyridinyl substituted thiazolyl acid hydrazide (4) when condensed with benzoic acids/nicotinic acids (5a-o) in the presence of silica supported POCl3 yielded better to excellent yields of the title compounds. All the synthesized compounds (6a-o) and intermediate acid hydrazide (4) have been screened for their in vitro antitubercular activity against Mycobacterium tuberculosis H37Ra (MTB) and Mycobacterium bovis BCG. Amongst them, 6f, 6j, 6l and 6o have revealed promising activity against M. bovis BCG at concentrations less than 3 mu g/mL. These compounds have shown low cytotoxicity (CC50: > 100 mu g/mL) towards four human cancer cell lines. Molecular docking study has also been performed against mycobacterial enoyl reductase (InhA) enzyme to gain an insight into the binding modes of these molecules and recorded good binding affinity. The ADME properties the title products have also been analyzed. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: 1; 3; 4-Oxadiazole; Antitubercular activity; Cytotoxicity; Molecular docking; Pyridine; Thiazole

Synthesis and antitubercular activity of new benzo[b]thiophenes - Mahajan, Pravin S.; Nikam, Mukesh D.; Nawale, Laxman U.; Khedkar, Vijay M.; Sarkar, Dhiman; Gill, Charansingh H. (ACS Medicinal Chemistry Letters, 2016)
In vitro and ex vivo efficacies of four series of benzo[b]thiophene-2-carboxylic acid derivatives were studied against Mycobacterium tuberculosis H37Ra (MTB). Benzo[b]thiophenes were also tested in vitro against multidrug resistant Mycobacterium tuberculosis H37Ra (MDR-MTB), and 7b was found to be highly active against A- and DMDR-MTB/MTB (MIC ranges 2.73-22.86 mu g/mL). The activity of all benzo[b]-thiophenes against M. bovis BCG (BCG) was also assessed grown under aerobic and under conditions of oxygen depletion. Compounds 8c and 8g showed significant activity with MICs of 0.60 and 0.61 mu g/mL against dormant BCG. The low cytotoxicity and high selectivity index data against human cancer cell lines, HeLa, Panc-1, and THP-1 indicate the potential importance of the development of benzo[b]thiophene-based 1,3-diketones and flavones as lead candidates to treat mycobacterial infections. Molecular docking studies into the active site of DprE1 (Decaprenylphosphoryl-beta-n-ribose-2'-epimerase) enzyme revealed a similar binding mode to native ligand in the crystal structure thereby helping to understand the ligand protein interactions and establish a structural basis for inhibition of MTB. In summary, its good activity in in vitro and ex vivo model, as well as its activity against multidrug-resistant M. tuberculosis H37Ra in a potentially latent state, makes 7b an attractive drug candidate for the therapy of tuberculosis.
Keywords: Benzo[b]thiophene; Cytotoxicity; M. Bovis BCG; MDR-MTB; Molecular docking

Synthesis and bioactivity of novel triazole incorporated benzothiazinone derivatives as antitubercular and antioxidant agent - Shaikh, Mubarak H.; Subhedar, Dnyaneshwar D.; Arkile, Manisha A.; Khedkar, Vijay M.; Jadhav, Nandadeep J.; Sarkar, Dhiman; Shingate, Bapurao B. (Bioorganic & Medicinal Chemistry Letters, 2016)
In search of new active molecules against Mycobacterium tuberculosis (MTB) H37Ra and M. bovis BCG, a small focused library of benzothiazinone based 1,2,3-triazoles has been efficiently prepared via click chemistry approach. Several derivatives were found to be promising inhibitors of MTB and M. bovis BCG characterized by lower MIC values (27.34-29.37 mu g/mL). Among all the synthesized compounds, 6c and 6e is the most active compound against MTB and M. bovis BCG. The compounds were further tested for anti-proliferative activity against HeLa, A549 and A431 cell lines using MTT assay and showed no significant cytotoxic activity at the maximum concentration evaluated. Further, the synthesized compounds were found to have potential antioxidant activity with IC50 range = 14.14-47.11 mu g/mL. Furthermore, to rationalize the observed biological activity data, the molecular docking study also been carried out against a potential target MTB DprE1, which revealed a significant correlation between the binding score and biological activity for these compounds. The results of the in vitro and in silico study suggest that the triazole incorporated benzothiazinone may possess the ideal structural requirements for further development of novel therapeutic agents. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: 1; 2; 3-Triazole; ADME prediction; Antioxidant; Antitubercular; Docking study

Synthesis and docking studies of pyrazine-thiazolidinone hybrid scaffold targeting dormant tuberculosis - Chitre, T. S.; Asgaonkar, K. D.; Miniyar, P. B.; Dharme, A. B.; Arkile, Manisha A.; Yeware, A.; Sarkar, Dhiman; Khedkar, Vijay M.; Jha, Prakash C. (Bioorganic & Medicinal Chemistry Letters, 2016)
The persistence of Mycobacterium tuberculosis (MTB) in dormant stage assists the pathogen to develop resistance against current antimycobactrial drugs. To address this issue, we report herein the synthesis of N-(4-oxo-2 substituted thiazolidin-3yl) pyrazine-2-carbohydrazide derivatives designed by following the molecular hybridization approach using pyrazine and thiazolidenone scaffolds. The compounds were evaluated against MTB H37Ra and Mycobacterium bovis BCG in dormancy model. Most of the compounds had IC50 values in 0.3-1 mu g/ml range. The active compounds were further tested for anti-proliferative activity against THP-1, Panc-1, A549, and MCF-7 cell lines using MTT assay and exhibited no significant cytotoxicity. We also report molecular docking studies using active analogs and MTB Decaprenylphosphoryl-beta-D-ribose-2'-epimerase (DprE1) to rationalize the biological activity and to provide an insight into the probable mechanism of action and binding mode of hybridized structures. The results obtained validate the use of molecular hybridization approach and also suggest that reported compounds can provide a novel pharmacophore to synthesize lead compounds against dormat MTB. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: docking; Dormant; Hybrid design; Pyrazine; Thiazolidenone; tuberculosis

Synthesis and evaluation of thieno[2,3-d]pyrimidin-4(3H)-ones as potential antitubercular agents (vol 6, pg 2209, 2015) - Borate, Hanumant B.; Annadate, Ritesh A.; Vagh, Sandip S.; Pisal, Mahesh M.; Deokate, Sagar B.; Arkile, Manisha A.; Jadhav, Nandadeep J.; Nawale, Laxman U.; Sarkar, Dhiman (Medchemcomm, 2016)

Synthesis and tyrosinase inhibition activity of trans-stilbene derivatives - Ismail, Tabasum; Shafi, Syed; Srinivas, Jada; Sarkar, Dhiman; Qurishi, Yasrib; Khazir, Jabeena; Alam, Mohammad Sarwar; Kumar, Halmuthur Mahabalarao Sampath (Bioorganic Chemistry, 2016)
Synthesis of a focussed library of trans-stilbene compounds through Wittig and other base catalysed condensation reactions is presented. The synthesized stilbenes were screened for their inhibitory potential against murine tyrosinase activity to explore the structure activity relationship (SAR). Presence of electron withdrawing group (-CN) at the double bond and hydroxyl group or halogen atom especially at para-position on the aromatic rings was found to significantly elevate the inhibitory activity. Among all the compounds screened, compounds 2, 6, 8, 10, 11, 15 and 21 were found to exhibit appreciable inhibitory activity. Compound 21 ((E)-2,3-bis(4-Hydroxyphenyl) acryonitrile) was found to be the most active with an IC50 value of 5.06 mu M which is less than half of the value 10.78 mu M observed for resveratrol (common standard used in murine tyrosinase activity studies) under similar conditions. The results obtained from the present study reveal structural/functional group sensitivity for the tyrosinase inhibitory activity of stilbenoid moieties and are expected to be very helpful for the design and synthesis of novel, selective and effective tyrosinase inhibitors. (C) 2016 Elsevier Inc. All rights reserved.
Keywords: Electron withdrawing groups; Murine tyrosinase activity; Resveratrol; Stilbenoids; Tyrosinase inhibitors; Wittig reaction

Synthesis, biological evaluation and molecular docking of novel coumarin incorporated triazoles as antitubercular, antioxidant and antimicrobial agents - Shaikh, Mubarak H.; Subhedar, Dnyaneshwar D.; Shingate, Bapurao B.; Khan, Firoz A. Kalam; Sangshetti, Jaiprakash N.; Khedkar, Vijay M.; Nawale, Laxman; Sarkar, Dhiman; Navale, Govinda R.; Shinde, Sandip S. (Medicinal Chemistry Research, 2016)
A series of new coumarin-based 1,2,3-triazole derivatives were designed, synthesized and evaluated for their antitubercular activity in vitro against Mycobacterium tuberculosis H37Ra, antioxidant activity by DPPH radical scavenging assay, antimicrobial activity in vitro against three gram-positive bacteria (Staphylococcus aureus, Micrococcus luteus and Bacillus cereus) and three gram-negative bacteria (Escherichia coli, Pseudomonas fluorescens and Flavobacterium devorans as well as three fungi (Aspergillus niger, Penicillium chrysogenum and Curvularia lunata). The bioactive assay showed that some synthesized coumarin triazoles displayed comparable or even better antitubercular, antioxidant, antibacterial and antifungal efficacy in comparison with reference drugs. Furthermore, docking study has been performed against DprE1 enzyme of M. tuberculosis that showed good binding interactions. Moreover, the synthesized compounds were also analyzed for ADME properties and showed potential to build up as good oral drug candidates. New coumarin-based 1,2,3-triazole derivatives were designed, synthesized and evaluated for their antitubercular, antioxidant, antibacterial and antifungal activity. Some of the coumarin-based triazole derivatives displayed comparable or even better efficacy in comparison with reference drugs. Molecular docking study has been performed against DprE1 enzyme of Mycobacterium tuberculosis showed good binding interactions. [GRAPHICS] .
Keywords: 1; 2; 3-Triazole; ADME prediction; Antimicrobial; Antioxidant; Antitubercular; Click chemistry; Docking study

Synthesis, biological evaluation and molecular docking studies of N-acylheteroaryl hydrazone derivatives as antioxidant and anti-inflammatory agents - Mahajan, Pravin S.; Nikam, Mukesh D.; Khedkar, Vijay M.; Jha, Prakash C.; Sarkar, Dhiman; Gill, Charansingh H. (Research on Chemical Intermediates, 2016)
In search of new therapeutics with greater potency, three new series of 3-methyl-1-phenyl-1H-thieno[2,3-c]pyrazole-5-carbohydrazide derivatives have been synthesized and evaluated for their in vitro antioxidant and anti-inflammatory activities. The hydrazones bearing a core pyrazole, chromone and tetrazolo[1,5-a]quinoline scaffold showed promising activities. Interestingly, compounds 3a (EC50 = 06.00 +/- A 2.36) and 5c (EC50 = 07.21 +/- A 0.67) showed the most potent antioxidant activity, while compounds 3a (EC50 = 10.25 +/- A 1.08), 7b (EC50 = 10.50 +/- A 0.99) and 7c (EC50 = 11.18 +/- A 0.15) showed significant anti-inflammatory activity. Furthermore, molecular docking studies also revealed a significant correlation between the binding score and biological activity for these compounds to describe the molecular basis for the structure activity relationship (SAR) results. As these compounds are good cyclooxygenase inhibitors, isoenzyme inhibitory potency studies are warranted.
Keywords: Anti-inflammatory; Antioxidant; Docking study; N-Acylhydrazones; Structure-activity relationship

Synthesis, biological evaluation and molecular docking study of some novel indole and pyridine based 1,3,4-oxadiazole derivatives as potential antitubercular agents - Desai, N. C.; Somani, Hardik; Trivedi, Amit; Bhatt, Kandarp; Nawale, Laxman; Khedkar, Vijay M.; Jha, Prakash C.; Sarkar, Dhiman (Bioorganic & Medicinal Chemistry Letters, 2016)
A series of indole and pyridine based 1,3,4-oxadiazole derivatives 5a-t were synthesized and evaluated for their in vitro antitubercular activity against Mycobacterium tuberculosis H37Ra (MTB) and Mycobacterium bovis BCG both in active and dormant state. Compounds 5b, 5e, 5g and 5q exhibited very good antitubercular activity. All the newly synthesized compounds 5a-t were further evaluated for antiproliferative activity against HeLa, A549 and PANC-1 cell lines using modified MTT assay and found to be noncytotoxic. On the basis of cytotoxicity and MIC values against Mycobacterium bovis BCG, selectivity index (SI) of most active compounds 5b, 5e, 5g and 5q was calculated (SI = GI(50)/MIC) in active and dormant state. Compounds 5b, 5e and 5g demonstrated SI values >= 10 against all three cell lines and were found to safe for advance screening. Compounds 5a-t were further screened for their antibacterial activity against four bacteria strains to assess their selectivity towards MTB. In addition, the molecular docking studies revealed the binding modes of these compounds in active site of enoyl reductase (InhA), which in turn helped to establish a structural basis of inhibition of mycobacteria. The potency, low cytotoxicity and selectivity of these compounds make them valid lead compounds for further optimization. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: 1; 3; 4-Oxadiazole; Antitubercular activity; Cytotoxicity; Indole; Molecular docking; Pyridine

Two chitotriose-specific lectins show anti-angiogenesis, induces caspase-9-mediated apoptosis and early arrest of pancreatic tumor cell cycle - Singh, Ruby; Nawale, Laxman; Sarkar, Dhiman; Suresh, C. G. (Plos One, 2016)
The antiproliferative activity of two chito-specific agglutinins purified from Benincasa hispida (BhL) and Datura innoxia (DiL9) of different plant family origin was investigated on various cancer cell lines. Both lectins showed chitotriose specificity, by inhibiting lectin hemagglutinating activity. On further studies, it was revealed that these agglutinins caused remarkable concentration-dependent antiproliferative effect on human pancreatic cancerous cells but not on the normal human umbilical vein endothelial cells even at higher doses determined using MTT assay. The GI(50) values were approximately 8.4 mu g ml(-1) (0.247 mu M) and 142 mu g ml(-1) (14.8 mu M) for BhL and DiL9, respectively, against PANC-1 cells. The growth inhibitory effect of these lectins on pancreatic cancer cells were shown to be a consequence of lectin cell surface binding and triggering G(0)/G(1) arrest, mitochondrial membrane depolarization, sustained increase of the intracellular calcium release and the apoptotic signal is amplified by activation of caspases executing cell death. Interestingly, these lectins also showed anti-angiogenic activity by disrupting the endothelial tubulogenesis. Therefore, we report for the first time two chito-specific lectins specifically binding to tumor glycans; they can be considered to be a class of molecules with antitumor activity against pancreatic cancer cells mediated through caspase dependent mitochondrial apoptotic pathway.

Anti-proliferative effect of novel primary cetyl alcohol derived sophorolipids against human cervical cancer cells HeLa - Nawale, Laxman; Dubey, Parul; Chaudhari, Bhushan; Sarkar, Dhiman; Prabhune, Asmita (Plos One, 2017)
Sophorolipids (SLs) are glycolipid biosurfactants that have been shown to display anticancer activity. In the present study, we report anti-proliferative studies on purified forms of novel SLs synthesized using cetyl alcohol as the substrate (referred as SLCA) and their anticancer mechanism in human cervical cancer cells. Antiproliferative effect of column purified SLCA fractions (A, B, C, D, E and F) was examined in panel of human cancer cell lines as well as primary cells. Among these fractions, SLCA B and C significantly inhibited the survival of HeLa and HCT 116 cells without affecting the viability of normal human umbilical vein endothelial cells (HUVEC). The two fractions were identified as cetyl alcohol sophorolipids with non-hydroxylated tail differing in the degree of acetylation on sophorose head group. At an IC50 concentration SLCA B (16.32 mu g ml(-1)) and SLCA C (14.14 mu g ml(-1)) blocked the cell cycle progression of HeLa cells at G1/S phase in time-dependent manner. Moreover, SLCA B and SLCA C induced apoptosis in HeLa cells through an increase in intracellular Ca2+ leading to depolarization of mitochondrial membrane potential and increase in the caspase-3, -8 and -9 activity. All these findings suggest that these SLCAs could be explored for their chemopreventive potential in cervical cancer.

Carboxymethyl cellulose-grafted mesoporous silica hybrid nanogels for enhanced cellular uptake and release of curcumin - Tiwari, Neha; Nawale, Laxman U.; Sarkar, Dhiman; Badiger, Manohar V. (Gels, 2017)
Mesoporous silica nanoparticles (MSNs) with ordered pore structure have beensynthesized and used as carriers for the anticancer drug curcumin. MSNs were functionalizedwith amine groups and further attached with carboxymethyl cellulose (CMC) using 1-ethyl-3-(3-dimethylaminopropyl)-carbodiimide (EDC) coupling chemistry, which increased the hydrophilicityand biocompatibility of MSNs. The functionalized MSNs (MSN-NH2and MSN-CMC) werecharacterized using Scanning Electron Microscopy (SEM), Transmission Electron Microscopy (TEM),Dynamic Light Scattering (DLS), N2adsorption, X-Ray Diffraction (XRD), Thermo GravimetricAnalysis (TGA) and Fourier Transform Infrared Spectroscopy (FT-IR). Thein vitrorelease of curcuminfrom the –NH2and CMC functionalized MSNs (MSN-cur-NH2and MSN-cur-CMC) was performedin 0.5% aqueous solution of sodium lauryl sulphate (SLS). The effect of CMC functionalization ofMSNs towards cellular uptake was studied in the human breast cancer cell line MDA-MB-231 andwas compared with that of MSN-NH2and free curcumin (cur). Both MSN-NH2and MSN-CMCshowed good biocompatibility with the breast cancer cell line. The MTT assay study revealedthat curcumin-loaded MSN-cur-CMC showed better uptake as compared to curcumin-loadedMSN-cur-NH2. Free curcumin was used as a control and was shown to have much less internalizationas compared to the curcumin-loaded functionalized MSNs due to poor bioavailability. Fluorescencemicroscopy was used to localize the ﬂuorescent drug curcumin inside the cells. The workdemonstrates that CMC-functionalized MSNs can be used as potential carriers for loading and releaseof hydrophobic drugs that otherwise cannot be used effectively in their free form for cancer therapy.

Click-chemistry-based multicomponent condensation approach for design and synthesis of spirochromene-tethered 1,2,3-triazoles as potential antitubercular agents - Chavan, Pramod V.; Pandit, Kapil S.; Desai, Uday V.; Wadgaonkar, Prakash P.; Nawale, Laxman; Bhansali, Sujit; Sarkar, Dhiman (Research on Chemical Intermediates, 2017)

Hybrids of thienopyrimidinones and thiouracils as anti-tubercular agents: SAR and docking studies - Pisal, Mahesh M.; Nawale, Laxman U.; Patil, Manoj; Bhansali, Sujit G.; Gajbhiye, Jayant M.; Sarkar, Dhiman; Chavan, Subhash P.; Borate, Hanumant B. (European Journal of Medicinal Chemistry, 2017)
A number of hybrid molecules containing thienopyrimidinones and thiouracil moieties were designed, synthesized and tested against Mycobacterium tuberculosis H37Ra wherein it was observed that the compounds 11-1514 exhibited antitubercular activity in vitro (MIC 7.6–19.1 μg/ml, 12–35 μM) against dormant stage while compound 15 exhibited antitubercular activity in vitro against dormant (MIC 23.4 μg/ml, 41 μM) as well as active (MIC 25.4 μg/ml, 45 μM) stage. Structural modifications of compound 15 were carried out to study the structure-activity relationship and it was observed that compound 18 exhibited antitubercular activity comparable to compound 15. Cytotoxicity studies revealed that these molecules were non-toxic. The docking study of compound 15 showed that there was binding with the active site of mycobacterial pantothenate synthetase. Further docking studies led to the synthesis of the compounds 16 and 17 and the antitubercular activity screening results showed that these compounds have significant antitubercular activity. The compounds 15-18 (MIC 11–29 μg/ml, 19–51 μM) can be used as starting points for further optimization. The synthetic strategies used in the present work have potential to prepare a large number of compounds for further refinement of structures and the present results will be very useful in the development of a new class of antimycobacterial agents.

Multifunctional inulin tethered silver-graphene quantum dots nanotheranostic module for pancreatic cancer therapy - Joshi, Preeti Nigam; Agawane, Sachin; Agawane, Sachin; Agawane, Sachin; Sarkar, Dhiman; Sarkar, Dhiman (Material Science and Engineering C- Materials for Biological Application, 2017)
Cancer nanotechnology is an emerging area of cancer diagnosis and therapy. Although considerable progress has been made for targeted drug delivery systems to deliver anticancer agents to particular site of interest, new nanomaterials are frequently being developed and explored for better drug delivery efficiency. In the present work, we have explored a novel nanoformulation based on silver-graphene quantum dots (Ag-GQDs) nanocomposite for its successful implementation for pancreatic cancer specific drug delivery in wistar rats. Carboxymethyl inulin (CMI); a modified variant of natural polysaccharide inulin is tethered with the nanocomposite via carbodiimide coupling to enhance the biocompatibility of nanoformulation. Experiments are performed to investigate the cytotoxicity reduction of silver nanoparticles after inulin tethering as well as anticancer efficacy of the system using 5-Fluorouracil (5-FU) as model drug. SEM, TEM, FT-IR, UV-vis, photoluminescence and anti proliferative assays (MTT) are performed for characterisation of the nanocomposite. Hyaluronic acid (HA) is conjugated as targeting moiety for CD-44 (cancer stem cell marker) to fabricate a complete targeted drug delivery vehicle specific for pancreatic cancer. In the present work two prime objectives were achieved; mitigation the toxicity of silver nanoparticles by inulin coating and it's in vivo application for pancreatic cancer. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: acid; Dextran; Drug-delivery; graphene quantum dots; Inulin; Nanocomposite; Nanocomposites; Nanoparticles; Pancreatic Cancer; Silver nanoparticle; Strategies; Systems; Targeted Drug Delivery

New bithiazolyl hydrazones: novel synthesis, characterization and antitubercular evaluation - Bhalerao, Mahendra B.; Dhumal, Sambhaji T.; Deshmukh, Amarsinh R.; Nawale, Laxman U.; Khedkar, Vijay M.; Sarkar, Dhiman; Mane, Ramrao A. (Bioorganic & Medicinal Chemistry Letters, 2017)
New bithiazolyl hydrazones (6a–l) have been first time synthesized by carrying novel one pot cyclocondensation of 5-acyl thiazoles (1a–b), thiosemicarbazide (2) and substituted phenacyl chlorides (4a–f) in freshly prepared ionic liquid, diisopropyl ethyl ammonium acetate (DIPEAc) at room temperature. The newly synthesized compounds have been evaluated for their antitubercular activity and the compounds 3b, 6a, 6b, 6d, 6e, 6f, 6g, and 6l have displayed noticeable antitubercular activity compared to Rifampicin with tolerable cytotoxicity. All these compounds were also screened for their antibacterial activity and found that, compounds 6j and 6k have exhibited a very good antibacterial activity. Molecular docking study has shown better harmony with the evaluation trend shown by these compounds under in vitro antitubercular screening.

Quinolidene based monocarbonyl curcumin analogues as promising antimycobacterial agents: synthesis and molecular docking study - Subhedar, Dnyaneshwar D.; Shaikh, Mubarak H.; Nawale, Laxman U.; Sarkar, Dhiman; Khedkar, Vijay M.; Shingate, Bapurao B. (Bioorganic & medicinal chemistry letters, 2017)
A series of quinoline incorporated monocarbonyl curcumin analogues was efficiently synthesized using [HDBU][HSO4] as catalyst via Knoevenagel type condensation and evaluated for their in vitro antitubercular activity against Mycobacterium tuberculosis H37Ra (MTB) and Mycobacterium bovis BCG in dormant state. The analogues 3e, 3h, 4a and 4e exhibited very good antitubercular activity. The antiproliferative activity of the analogues against MCF-7, A549 and HCT-116 cell lines was evaluated using modified MTT assay and these compounds were found to be non-cytotoxic. Molecular docking study has been carried out against M. tuberculosis pantothenate synthetase (MTB PS) enzyme in an effort to enhance the understanding of their action as antitubercular agents. The potency, low cytotoxicity and selectivity of these analogues support them as valid leads for further optimization.

Quinolidene-rhodanine conjugates: facile synthesis and biological evaluation - Subhedar, Dnyaneshwar D.; Shaikh, Mubarak H.; Shingate, Bapurao B.; Nawale, Laxman; Sarkar, Dhiman; Khedkar, Vijay M.; Khan, Firoz A. Kalam; Sangshetti, Jaiprakash N. (European Journal of Medicinal Chemistry, 2017)
A series of rhodanine incorporated quinoline derivatives were efficiently synthesized using reusable DBU acetate as ionic liquid and evaluated for their in vitro antitubercular activity against Mycobacterium tuberculosis H37Ra (MTB) (ATCC 25177) and Mycobacterium bovis BCG (ATCC 35743) both in active and dormant state. Compounds 3e, 3f, 3g, 3h and 3i exhibited very good antitubercular activity. The active compounds were studied for cytotoxicity against HUVEC, THP-1, macrophages, A549, PANC-1 and HeLa cell lines using modified MTT assay and were found to be noncytotoxic. Inactivity of all these compounds against Gram positive and Gram negative bacteria indicates their specificity towards the MTB. Further, the synthesized compounds have been screened for their in vitro antifungal activity. In addition, the molecular docking studies revealed the binding modes of these compounds in active site of Zmp1 enzyme, which in turn helped to establish a structural basis of inhibition of mycobacteria. The results of present study clearly indicate the identification of some novel, selective and specific inhibitors against MTB that can be explored further for potential antitubercular drug.

Superoxide generation and its involvement in the growth of mycobacterium smegmatis - Yeware, Amar M.; Shurpali, Ketaki D.; Athalye, Meghana C.; Sarkar, Dhiman (Frontiers in Microbiology, 2017)
Superoxide generation is inevitable in aerobic organisms, most of which have developed mechanisms to detoxify superoxides. However, its significance has not been clearly understood in mycobacteria. This study demonstrates that NADH oxidase is the major source of superoxide in Mycobacterium smegmatis and elucidates the involvement of superoxide in M. smegmatis growth. The maximum inhibition of superoxide generation was observed in the presence of diphenyleneiodonium chloride (DPI), an NADH oxidase inhibitor, compared to other standard inhibitors. After incubation for 24 h, the number of colony forming units (CFUs) was reduced by 6.8 log10 compared to the untreated culture. The inhibitory effect of DPI on M. smegmatis was reversed when the same culture was supplemented with menadione and pyrogallol, which are superoxide generators. Thus, this study reports the source of superoxide generation and its involvement in the growth of M. smegmatis.

Synthesis and antimycobacterial screening of new thiazolyl-oxazole derivatives - Abhale, Yogita K.; Sasane, Amit V.; Chavan, Abhijit P.; Shekh, Saddam Husen; Deshmukh, Keshav K.; Bhansali, Sujit; Nawale, Laxman; Sarkar, Dhiman; Mhaske, Pravin C. (European Journal of Medicinal Chemistry, 2017)
In the present study a series of 4-methyl-2-aryl-5-(2-aryl/benzyl thiazol-4-yl) oxazole (4a-v) have been synthesized and evaluated for their preliminary antitubercular, antimicrobial and cytotoxicity activity. Among all the synthesized compounds, 4v reported comparable activity against dormant M. tuberculosis H37Ra and M. bovis BCG strains with respect to standard drug rifampicin. The active compounds from the antitubercular study were further tested for anti-proliferative activity against HeLa, A549 and PANC-1 cell lines using MU assay and showed no significant cytotoxic activity at the maximum concentration evaluated. Further, the synthesized compounds were found to have potential antibacterial activities with MIC range of 2.1-26.8 mu g/mL. High potency, lower cytotoxicity and promising antimycobacterial activity suggested that these compounds could serve as good leads for further optimisation and development. (C) 2017 Elsevier Masson SAS. All rights reserved.

Synthesis and antitubercular activity of new thiazolidinones with pyrazinyl and thiazolyl scaffolds - Dhumal, Sambhaji T.; Deshmukh, Amarsinh R.; Khillare, Lalit D.; Arkile, Manisha A.; Sarkar, Dhiman; Mane, Ramrao A. (Journal of Heterocyclic Chemistry, 2017)
Emergence of multidrug resistant and extensively drug resistant tuberculosis has prompted to develop new molecular entities to treat the disease. A series of new 4-thiazolidinones with pyrazinyl and thiazolyl scaffolds has been synthesized, and their antitubercular activity is reported. The title 4-thiazolidinones, N-(pyrazinyl substituted thiazoloylamino)-2-aryl-4-thiazolidinones () have been first time prepared using pyrazinamide as a starting material via five successive steps. The purity and the structures of the intermediates (carboethoxythiazole, acid hydrazide, and azomethines) and title thiazolidinones () have been confirmed by TLC and spectral analyses, respectively. An antitubercular screening of the new 4-thiazolidinones has been performed on bacterial strains, Mycobacterium tuberculosis H37Ra and Mycobacterium BCG using the solutions of different concentrations of the compounds () and the screening results are presented. Compound has displayed notable antitubercular activity.

Synthesis and biological evaluation of 1,2,4-triazole-3-thione and 1,3,4-oxadiazole-2-thione as anti-mycobacterial agents - Sonawane, Amol; Rode, Navnath D.; Nawale, Laxman U.; Joshi, Rohini R.; Joshi, Ramesh A.; Likhite, Anjali P.; Sarkar, Dhiman (Chemical Biology & Drug Design, 2017)
Resistance among dormant mycobacteria leading to multi-drug resistant (MDR) and extremely-drug resistant(XDR) tuberculosis is one of the major threats. Hence, a series of 1,2,4-triazole-3-thione and 1,3,4-oxadiazole-2-thione derivatives (4a-5c) have been synthesised and screened for their anti-tubercular activity against Mycobacterium tuberculosis H37Ra (H37Ra). Thetriazolethiones4b and 4v showed high anti-tubercular activity (both MIC and IC50) against the dormant H37Ra by in vitro and ex vivo. They were shown to have more specificity towards mycobacteria than other gram-negative and gram- positive pathogenic bacteria. The cytotoxicity was almost insignificant up to 100 μg/mL against THP-1, A549 and PANC-1 human cancer cell lines, and solubility was high in aqueous solution, indicating the potential of developing these compounds further as novel therapeutics against tuberculosis infection.

Synthesis and biological evaluation of new fluconazole β-lactam conjugates linked via 1,2,3-triazole - Divse, Jaisingh M.; Mhaske, Santosh B.; Charolkar, Chaitanya R.; Sant, Duhita G.; Tupe, Santosh G.; Deshpande, Mukund V.; Khedkar, Vijay M.; Nawale, Laxman U.; Sarkar, Dhiman; Pore, Vandana S. (New Journal of Chemistry, 2017)
Novel 1,2,3-triazole-linked β-lactam–fluconazole conjugates 12(a–l) were designed and synthesized. The compounds showed potent antifungal activity against two pathogenic Candida strains; Candida albicans ATCC 24433 and Candida albicans ATCC 10231 with MIC values in the range of 0.0625–2 μg mL−1. Compounds 12h, 12j and 12k showed promising antifungal activity against all the tested fungal pathogens except C. neoformans ATCC 34554 compared to fluconazole. Compound 12j in which the β-lactam ring was formed using para-anisidine and benzaldehyde was found to be more potent than fluconazole against all the fungal strains with an IC50 value of <0.015 μg mL−1 for Candida albicans (ATCC 24433). Mechanistic studies for active compounds revealed that the antifungal action was due to ergosterol inhibition. Compounds 12h and 12j at a concentration of 0.125 μg mL−1 caused 91.5 and 96.8% ergosterol depletion, respectively, compared to fluconazole which at the same concentration caused 49% ergosterol depletion. The molecular docking study revealed that all the fluconazole β-lactam conjugates 12(a–l) could snugly fit into the active site of lanosterol 14α-demethylase (CYP51) with varying degrees of affinities. As anticipated, the binding energy for compound 12j (−58.961 kcal mol−1) was much smaller than that for fluconazole (−52.92 kcal mol−1). The synthesized compounds have therapeutic potential for the control of candidemia.

Synthesis and cell imaging applications of fluorescent mono/di/tri-heterocycl- yl-2,6-dicyanoanilines - Pisal, Mahesh M.; Annadate, Ritesh A.; Athalye, Meghana C.; Kumar, Dipak; Chavan, Subhash P.; Sarkar, Dhiman; Borate, Hanumant B. (Bioorganic & Medicinal Chemistry Letters, 2017)
Synthesis of 3,4,5-triheterocyclyl-2,6-dicyanoanilines, starting from heterocyclic aldehydes and 1,2-diheterocycle-substituted ethanones, is described. 2,6-Dicyanoanilines with one or two heterocyclic substituents have also been synthesized. It was found that some of these molecules have selective cell-staining properties useful for cell imaging applications. The compounds 1g, 10f and 11 were found to stain cytoplasm of the cells in contact but not the nucleus while the compound 12 showed affinity to apoptotic cells resulting in blue fluorescence. The cell imaging results with compound 12 were similar to Annexin V-FITC, a known reagent containing recombinant Annexin V conjugated to green-fluorescent FITC dye, used for detection of apoptotic cells. These compounds were found to be non-cytotoxic and have potential application as cell imaging agents.

Synthesis, antimycobacterial screening and molecular docking studies of 4-aryl-4′-methyl-2′-aryl-2,5′-bisthiazole derivatives - Abhale, Yogita K.; Shinde, Abhijit D.; Deshmukh, Keshav K.; Nawale, Laxman U.; Sarkar, Dhiman; Choudhari, Prafulla B.; Kumbhar, Santosh S.; Mhaske, Pravin C. (Medicinal Chemistry Research, 2017)
A series of 4-aryl-4′-methyl-2′-aryl-2,5′-bisthia- zole derivatives (5a–o) were synthesized and screened for inhibitory activity against Mycobacterium tuberculosis H37Ra (ATCC 25177) and Mycobacterium bovis BCG (ATCC 35743) strains. Five lead compounds (5e, 5f, 5g, 5h, and 5o) were further confirmed from their dose dependent effect against MTB and Bovine–Calmette–Guerin. The most promising compounds 5f (MIC90: 11.32 μg/mL), 5h (MIC90: 11.59 μg/mL), and 5o (MIC90: 23.64 μg/mL) showed strong antitubercular activity against dormant MTB and BCG as well as almost insignificant cytotoxicity up to 100μg/mL against HeLa, A549, and PANC-1 human cancer cell lines. Further, the synthesized compounds were found to have potential antibacterial activity against Gram-negative bac- teria, Escherichia coli, Pseudomonas flurescence and Gram- positive bacteria, Staphylococcus aureus, Bacillus subtilis. Most of the synthesized compounds showed moderateactivity against fungal strain Candida albicans. Molecular docking studies of these compounds showed significant interactions with crystal structure of the cytochrome P45014α-sterol demethylase (CYP51) PDB ID: 1E9X. Hydrogen bond interactions with SER261 and VAL395 are important interactions for selective inhibition of designed inhibitors. Compounds 5f, 5h, and 5o showed significant interactions with 1E9X. All the experimental results promote us to consider this series as a starting point for the devel- opment of novel, selective and more potent antitubercular agents in the future.

Synthesis, biological evaluation, and molecular docking studies of novel 3-aryl-5-(alkyl-thio)-1H-1,2,4-triazoles derivatives targeting Mycobacterium tuberculosis - Rode, Navnath D.; Sonawane, Amol D.; Nawale, Laxman; Khedkar, Vijay M.; Joshi, Ramesh A.; Likhite, Anjali P.; Sarkar, Dhiman; Joshi, Rohini R. (Chemical Biology & Drug Design, 2017)
A small library of new 3-aryl-5-(alkyl-thio)-1H-1,2,4-triazoles was synthesized and screened for the antimycobacterial potency against Mycobacterium tuberculosis H37Ra strain and Mycobacterium bovis BCG both in active and dormant stage. Among the synthesized library, 25 compounds exhibited promising anti-TB activity in the range of IC(50)0.03-5.88g/ml for dormant stage and 20 compounds in the range of 0.03-6.96g/ml for active stage. Their lower toxicity (>100g/ml) and higher selectivity (SI=>10) against all cancer cell lines screened make them interesting compounds with potential antimycobacterial effects. Furthermore, to rationalize the observed biological activity data and to establish a structural basis for inhibition of M.tuberculosis, the molecular docking study was carried out against a potential target MTB CYP121 which revealed a significant correlation between the binding score and biological activity for these compounds. Cytotoxicity and in vivo pharmacokinetic studies suggested that 1,2,4-triazole analogues have an acceptable safety index, in vivo stability and bio-availability.

Synthesis of novel triazole-incorporated isatin derivatives as antifungal, antitubercular, and antioxidant agents and molecular docking study - Shaikh, Mubarak H.; Subhedar, Dnyaneshwar D.; Khan, Firoz A. Kalam; Sangshetti, Jaiprakash N.; Nawale, Laxman; Arkile, Manisha A.; Sarkar, Dhiman; Shingate, Bapurao B. (Journal of Heterocyclic Chemistry, 2017)
A library of 1,2,3-triazoles efficiently prepared via click chemistry and evaluated for their antifungal, antitubercular, antioxidant, cytotoxicity, molecular docking and ADME prediction.

Antibacterial and anti-TB tat-peptidomimetics with improved efficacy and half-life - Bhosle, Govind S.; Nawale, Laxman; Yeware, Amar M.; Sarkar, Dhiman; Fernandes, Moneesha (European Journal of Medicinal Chemistry, 2018)
Non-natural antimicrobial peptides are ideal as next-generation antibiotics because of their ability to circumvent the problems of drug resistance and in vivo instability. We report novel all-alpha- and alpha,gamma-mixed Tat peptide analogues as potential antibacterial and anti-TB agents. These peptides have broad spectrum antibacterial activities against Gram-positive (MICs 0.61 +/- 0.03 to 1.35 +/- 0.21 mu M with the peptide gamma TatM4) and Gram-negative (MICs 0.71 +/- 0.005 to 1.26 +/- 0.02 M with gamma TatM4) bacteria and are also effective against active and dormant forms of Mycobacterium tuberculosis, including strains that are resistant to rifampicin and isoniazid. The introduction of the non-natural amino acids of the study in the Tat peptide analogues results in increased resistance to degradation by proteolysis, significantly increasing their half-life. The peptides appear to inhibit bacteria by a membrane disruption mechanism, and have only a low cytotoxic effect on mammalian cells. (C) 2018 Elsevier Masson SAS. All rights reserved.

Conformational studies of Ant-Pro motif-incorporated cyclic peptides: gramicidin S and avellanin - Kotmale, Amol S.; Sangtani, Ekta; Gonnade, Rajesh G.; Sarkar, Dhiman; Burade, Sachin; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (New Journal of Chemistry, 2018)
This paper reports conformational changes observed in cyclic bioactive peptides such as gramicidin S and avellanin upon incorporation of a pseudo-beta (C9) Ant-(D)Pro turn motif in their structural frameworks. Solution-state studies suggested that a synthetic gramicidin S analog exhibits a beta-sheet conformation with C9 and C17 intramolecular hydrogen bonding patterns, while its truncated analog disturbs the beta-sheet conformation. Structural details were obtained using a combination of CD studies, X-ray crystal structure studies and nOe-based MD simulation studies.

Design and synthesis of 2-amino-thiophene-tethered ureidopenicillin analogs with potentantibacterial and antitubercular activity - Wagh, Mahendra A.; Baravkar, Sachin B.; Jedhe, Ganesh S.; Borkute, Rachna; Choudhari, Amit S.; Sarkar, Dhiman; Sanjayan, Gangadhar J. (ChemistrySelect, 2018)
Ureidopenicillins are a class of penicillins which are antibiotics active against gram-negative bacteria. Herein, we report the synthesis of 2-aminothiophene-tethered ureidopenicillin analogues and their in vitro antibacterial and antitubercular activity. Intriguingly, unlike the reported ureidopenicillins which are active against gram-negative bacteria, the synthesised 2-aminothiophene-tethered ureidopenicillins were significantly active against Gram-positive bacterial strains and showed moderate inhibition towards gram-negative bacterial strains. Among all the analogs, compound 1b containing 2-aminothiophene moiety with minimum inhibitory concentration (MIC): 0.29, 0.32, > 10, > 10 mg/ml for Staphylococcus aureus, Bacillus subtilis, Escherichia coli and Pseudomonas aeruginosa, respectively, showed better anti-bacterial profile as compared to cephalexin and equipotent to ampicillin and amoxicillin on gram-positive bacterial strains. All the derivatives were also screened for anti-TB activity against mycobacterium tuberculosis H37Ra. Among the series, cycloocta-thiophene-tethered cephalexin analog 3c displayed excellent antitubercular activity with MIC values 0.78 mg/ml. Low cytotoxicity and high selectivity index indicate the efficacy of 3c against mycobacterial infections. The results from present study offer a novel approach to modify the existing drug class of ureidopenicillins to yield antimicrobials with promising utility.

Design, synthesis and biological screening of novel 1,3,4-oxadiazoles as antitubercular agents - Tambe, Macchindra S.; Choudhari, Amit; Sarkar, Dhiman; Sangshetti, Jaiprakash; Patil, Rajesh; Gholap, Somnath S. (Chemistryselect, 2018)
A series of novel 2,5-disubstitued 1,3,4-oxadiazole derivatives bearing 2,2-dimethyl-2,3-dihydrobenzofuran scaffold has been synthesized and screened for antitubercular activity. All the synthesized compounds were characterized by IR, H-1 NMR, C-13-NMR and Mass spectral study. The in vitro antitubercular activity of the synthesized compounds was evaluated against Mycobacterium tuberculosis H37Ra(ATCC 25177) strain. Among the synthesized compounds, four compound displayed good antitubercular activity IC50 values in low micro-gram range (<10 mu g/mL). The antitubercular data suggested that growth inhibition MTB can be imparted by the introduction of a 4- trifluoromethyl phenyl acetylene substituent. Specificity of these compounds was checked by screening them for their anti-bacterial activity against four bacterial strains (Gram-negative strains: E. coli, S. aureus; Gram-positive strains: P. aeruginosa and B. subtilis). None of the compound displayed antibacterial activity against any of the seleted strain. Molecular docking studies were carried out on InhA (FabI/ENR) which shows that the synthesized compounds bind at the catalytic site in a most favourable manner suggesting their potential as anti-mycobacterial agents. The research presented here was found to be adventitious for the development of new therapeutic agents against Mycobacterium infection.

Design, synthesis, and pharmacological evaluation of fluorinated azoles as anti-tubercular agents - Gholap, Somnath; Tambe, Macchindra; Nawale, Laxman; Sarkar, Dhiman; Sangshetti, Jaiprakash; Damale, Manoj (Archiv Der Pharmazie, 2018)
Design, synthesis, and biological screening of 2,2-dimethyl-2,3-dihydrobenzofuran tethered 1,3,4-oxadiazole derivatives as anti-tubercular agents were described. The synthesis of the target compounds was conducted by a series of reaction schemes. All the synthesized compounds were characterized by IR, H-1 NMR, C-13 NMR, and mass spectrometry. The therapeutic potential of the synthesized compounds was confirmed by molecular docking studies. Among the synthesized compounds, 12a, 12c, 12d, 12e, 12g, and 12j were found to be more active against non-replicating than against replicating cultures of Mycobacterium tuberculosis H37Ra ex vivo and in vitro. These compounds exhibit minimum inhibitory concentration (MIC) values in the range of 2.31-23.91g/mL. The cytotoxicity study was conducted against the cell lines THP-1, A549 and PANC-1, and the compounds were observed to be non-toxic to host cells. Molecular docking was conducted with InhA (FabI/ENR) and suggested the antimycobacterial potential of the synthesized compounds. The investigation presented here was found to be adventitious for the development of new therapeutic agents against Mycobacterium infection.
Keywords: 1; 2; 2-dimethyl-2; 3; 3-dihydrobenzofuran; 4-Oxadiazole; anti-tubercular agents; Cytotoxicity; Molecular docking

Design, synthesis, docking studies and biological screening of 2-thiazolyl substituted-2,3-dihydro-1H-naphtho[1,2-e][1,3]oxazines as potent HIV-1 reverse transcriptase inhibitors - Gawali, Rakhi; Trivedi, Jay; Bhansali, Sujit; Bhosale, Raghunath; Sarkar, Dhiman; Mitra, Debashis (European Journal of Medicinal Chemistry, 2018)
1,3-oxazine nucleus and thiazolyl group features prominently in many biologically important natural products as well as bioactive molecules. A series of novel 2-thiazolyl substituted-2,3-dihydro-1H-naphtho [1,2-e][1,3]oxazine derivatives were designed and synthesized based on their structure-activity relationships (SARs) from 2-naphthol, substituted thiazolyl amines and formalin through ring closure by one-pot three component reaction. These derivatives were first evaluated for their inhibitory effect on HIV-1 Reverse Transcriptase (RT) enzyme activity. Out of 14 compounds, 4 showed potent inhibition of HIV-1 RT activity at significantly low concentration. Docking studies of these molecules revealed their high affinity binding to several amino acids of HIV-1 RT which are less sensitive to point mutations. Furthermore, anti-HIV activity of these molecules was analysed in a CD4(+) T cell-line, which indicates that Therapeutic Index (TI) of some of these compounds is better than Zidovudine and Efavirenz, known HIV-1 RT inhibitors. Taken together, our studies report for the first time some novel naphthoxazine derivatives with significant TI, which is through inhibition of HIV-1 RT activity. (C) 2018 Elsevier Masson SAS. All rights reserved.

Molecular modeling studies and in vitro screening of dihydrorugosaflavonoid and its derivatives against mycobacterium tuberculosis - Puranik, Ninad V.; Srivastava, Pratibha; Swami, Sagar; Choudhari, Amit; Sarkar, Dhiman (RSC Advances, 2018)
Novel drug regimens against tuberculosis (TB) are urgently needed and may be developed by targeting essential enzymes of Mtb that sustain the pathogenicity of tuberculosis. In the present investigation, series of compounds (5a-f and 6a-f) based on a naturally occurring rugosaflavonoid moiety were evaluated by in silico molecular modeling studies against -ketoacyl-ACP reductase (MabA) (PDB ID: IUZN) and pantothenate kinase (PanK) (PDB ID: ; 3AF3). Compounds 5a, 5c, 5d, and 6c, which had docking scores of -8.29, -8.36, -8.17 and -7.39 kcal mol(-1), respectively, displayed interactions with MabA that were better than those of isoniazid (-6.81 kcal mol(-1)). Similarly, compounds 5a, 5c, 5d, and 6c, which had docking scores of -7.55, -7.64, -7.40 and -6.7 kcal mol(-1), respectively, displayed interactions with PanK that were comparable to those of isoniazid (-7.64 kcal mol(-1)). Because of their docking scores, these compounds were screened in vitro against Mycobacterium tuberculosis H37Ra (Mtb) using an XRMA protocol. Among the screened compounds, the dihydrorugosaflavonoid derivatives 5a, 5c, and 5d had IC50 values of 12.93, 8.43 and 11.3 g mL(-1), respectively, and exhibited better inhibitory activity than the parent rugosaflavonoid derivatives. The rugosaflavonoid derivative 6c had an IC50 value of 17.57 g mL(-1). The synthesized compounds also displayed inhibitory activity against the Gram-positive bacteria Bacillus subtilis and Staphylococcus aureus. The present study will be helpful for the further development of these molecules into antitubercular lead candidates.

Novel benzylidenehydrazide-1,2,3-triazole conjugates as antitubercular agents: synthesis and molecular docking - Shaikh, Mubarak H.; Subhedar, Dnyaneshwar; Nawale, Laxman; Sarkar, Dhiman; Khan, Firoz A. Kalam; Sangshetti, Jaiprakash; Shingate, Bapurao B. (Mini Reviews in Medicinal Chemistry, 2018)
Novel 1,2,3-triazole based benzylidenehydrazide derivatives were synthesized and evaluated for antitubercular activity against Mycobacterium tuberculosis (MTB) H37Ra, M. bovis BCG and cytotoxic activity. Most of the derivatives exhibited promising in vitro potency against MTB characterized by lower MIC values. Among all the synthesized derivatives, compound 6a and 6j were the most active against active and dormant MTB H37Ra, respectively. Compound 6d was significantly active against dormant and active M. bovis BCG. The structure activity relationship has been explored on the basis of anti-tubercular activity data. The active compounds were also tested against THP-1, A549 and Panc-1 cell lines and showed no significant cytotoxicity. Further, the synthesized compounds were found to have potential antioxidant with IC50 range = 11.19-56.64 μg/mL. The molecular docking study of synthesized compounds was performed against DprE1 enzyme of MTB to understand the binding interactions. Moreover, synthesized compounds were also analysed for ADME properties and from all the experimental results, the potency of compounds indicate that, this series considered as starting point for the developement of novel and more potent anti-tubercular agents in future.

Novel red fluorescence protein based microplate assay for drug screening against dormant mycobacterium tuberculosis by using paraffin - Yeware, Amar; Sarkar, Dhiman (Tuberculosis, 2018)
The hypoxia model of dormancy is widely used in drug screening programs to identify novel inhibitors against latent Mycobacterium tuberculosis disease. In earlier reported microplate assays, hypoxia was maintained by either sealing the microplate or shifting in an anaerobic chamber to develop dormant phenotype. In these assays, inhibitors were added during inoculation, which mainly represents the active stage inhibitors instead of the dormant ones. Herein, the culture was covered with paraffin to develop hypoxia condition and consequently providing the advantage of adding compounds at any stage during incubation of 96-well plate. The stable expression of the red fluorescent protein in the bacilli under both actively growing as well as dormant conditions also facilitate the reliable estimation of growth and inhibition kinetics of bacilli in medium. Furthermore, S/N ratio and Z' factor of this assay were found to be > 27 and 0.91-0.94 respectively, which confirm the robustness of the protocol. This newly developed drug-screening assay offers an easy, inexpensive, safe and high throughput-screening tool to search novel antitubercular inhibitors against both active and dormant bacilli. The red fluorescent H37Ra strain is a suitable surrogate for the more virulent H37Rv strain, and thus this effort will help in combating latent tuberculosis.

Rational design of coumarin derivatives as antituberculosis agents - Mali, Hemlata M.; Sabale, Sandip S.; Degani, Mariam S.; Borkute, Rachana; Choudhari, Amit S.; Sarkar, Dhiman; Krishna, Vagolu Siva; Sriram, Dharmarajan (Future Medicinal Chemistry, 2018)
A series of coumarin derivatives was designed as potential antituberculosis agents. Results: The compounds were screened against active and dormant Mycobacterium tuberculosis (Mtb). Compounds 3k and 3n were found to have the most promising activity against replicating MtbH37Rv exhibiting minimum inhibitory concentration of 4.63 and 9.75 mu M respectively. The compounds were also effective against dormant MtbH37Rv exhibiting more potency than the standard drugs, isoniazid and rifampicin. The compounds were found to be non-cytotoxic against human cell lines. Conclusion: This study provides promising antituberculosis agents that are effective against replicating as well as dormant Mtb and can thus act as potential leads for further development.

Synthesis and biological evaluation of new 2-aryl-4-((4-aryl-1H-1,2,3-triazol-1-yl)methyl)thiazole derivatives - Shinde, Vikas; Mahulikar, Pramod; Mhaske, Pravin C.; Nawale, Laxman; Sarkar, Dhiman (Research on Chemical Intermediates, 2018)
A series of 2-aryl-4-((4-aryl-1H-1,2,3-triazol-1-yl)methyl)thiazole derivatives (8a-p) have been synthesized. The structure of the newly synthesized compounds was determined by spectral analysis. The title compounds were screened for their preliminary antitubercular activity against Mycobacterium tuberculosis H37Ra (MTB, ATCC 25177) and Mycobacterium bovis BCG (BCG, ATCC 35743). Further, the synthesized compounds were screened for antimicrobial activity against standard Gram-negative bacteria Escherichia coli (NCIM 2576) and Pseudomonas flurescence (NCIM 2059) and Gram-positive bacteria Staphylococcus aureus (NCIM 2602) and Bacillus subtilis (NCIM 2162). Among all the synthesized compounds, 8a-c, f-h, m exhibited good activity against dormant M. bovis BCG strain. Compounds 8h, j exhibited good activity against all tested bacterial strains. All active compounds were screened for cytotoxicity and found inactive. Their high potency and promising antimycobacterial activity suggest that these compounds could serve as good leads for further optimization and development.
Keywords: 1; 2; 3-Triazole; antibacterial activity; Antitubercular activity; Thiazole

Synthesis and biological evaluation of novel triazole-biscoumarin conjugates as potential antitubercular and anti-oxidant agents - Danne, Ashruba B. (Research on Chemical Intermediates, 2018)
The synthesis of a new series of triazole-biscoumarin conjugates by using a molecular hybridization approach is described. The newly synthesized compounds 6a–k were evaluated for their in vitro antitubercular activity against active and dormant Mtb H37Ra and anti-oxidant activity against DPPH radical scavenging. Molecular docking simulations for the antitubercular activity showed that the conjugates 6a–k bind in the pocket of the DprE1 enzyme. Most of the conjugates displayed good antitubercular activity against both the active and dormant Mtb H37Ra strain. The compound 6h displayed very good antitubercular activity against dormant Mtb H37Ra with an IC50 value of 1.44 μg/mL. Most of the synthesized conjugates exhibit excellent anti-oxidant activity with an IC50 of less than the standard BHT. Compound 6b is the most active among all the conjugates with an IC50 value of 08.17 ± 0.11 μg/mL. The molecular docking study shows good agreement between the observed antitubercular activity and the binding affinity.
Keywords: 1; 2; 3-triazoles; Anti-oxidant activity; Antitubercular activity; Biscoumarins; Molecular docking

Synthesis and biological evaluation of some bicyclic [2-(2,4-dimethylphenylthio)phenyl] aniline and its amide derivatives as potential antitubercular agents - Patil, Yogesh; Shingare, Ramesh (Journal of Chemical Sciences, 2018)
In the present investigation, a series of bicyclic [2-(2,4-dimethylphenylthio)phenyl] aniline analogues were synthesized and characterized by IR, NMR (1H and 13C) and mass spectra. All newly synthesized 15 compounds were inspected for their in vitro antitubercular activity against Mycobacterium tuberculosis (MTB) H37Ra in both active and dormant state using an established XTT Reduction Menadione assay (XRMA). The titled compounds exhibited minimum inhibitory concentration (MIC90) ranging from 0.05 to >30 (μg/mL). The potent four compounds were further evaluated in THP-1 infection model where they demonstrated significant antitubercular activity. All the ex vivo active were further evaluated for cytotoxic activity against THP-1, MCK7 and HeLa cell lines in order to check selectivity index. All compounds were further screened against four different bacteria to assess their selectivity towards MTB. These derivatives could be considered as a precursor structure for further design of antituberculosis agent.
Keywords: 4-dimethylphenylthio)phenyl] aniline; antituberculosis activity; Cytotoxicity; [2-(2

Synthesis and biological evaluation of some new tricyclic pyrrolo[3,2-e]tetrazolo[1,5-c]pyrimidine derivatives as potential antitubercular agents - Patil, Yogesh; Shingare, Ramesh; Choudhari, Amit; Borkute, Rachana; Sarkar, Dhiman; Madje, Balaji R. (Archiv Der Pharmazie, 2018)
A series of new tricyclic pyrrolo[3,2-e]tetrazolo[1,5-c]pyrimidines 8a-l were synthesized and characterized by IR, NMR (H-1 and C-13), and mass spectral analysis. The newly synthesized compounds 8a-l were inspected for their in vitro antitubercular activity against Mycobacterium tuberculosis (MTB) H37Ra using an established XTT reduction menadione assay (XRMA). The title compounds exhibited minimum inhibitory concentrations (MIC90) ranging from 0.09 to >30g/mL. Five compounds (8c, 8i-l) were further confirmed for their dose-dependent effect against MTB. These compounds were evaluated in the THP-1 infection model, where 8i (MIC90=0.35g/mL), 8j (MIC90=1.17g/mL), 8k (MIC90=2.38g/mL), and 8l (MIC90=1.17g/mL) demonstrated significant antitubercular activity. All the ex vivo active compounds showed insignificant cytotoxicity against the human cancer cell lines, HeLa, MCF-7, and THP-1. Inactivity of all these compounds against Gram positive and Gram negative bacteria indicates their specificity. Molecular docking studies in the active site of the sterol 14alpha-demethylase (CYP51) enzyme revealed a similar binding mode to the native ligand in the crystal structure, thereby helping to understand the ligand-protein interactions and to establish a structural basis for inhibition of MTB. The results suggest novel pharmacophores as selective and specific inhibitors against MTB that can be explored further to synthesize lead compounds against tuberculosis. In summary, the results clearly indicate the identification of some novel, selective, and specific inhibitors against MTB that can be explored further for potential antitubercular drugs.
Keywords: 2-e]tetrazolo[1; 5-c]pyrimidine; Antituberculosis; Cytotoxicity; Molecular docking; tricyclic pyrrolo[3

Synthesis, biological evaluation, and molecular docking study of pyridine clubbed 1,3,4-oxadiazoles as potential antituberculars - Desai, N. C. (Synthetic Communications, 2018)
A series of pyridine clubbed 1,3,4-oxadiazole derivatives were efficiently synthesized, characterized by standard spectral techniques and evaluated for their in vitro antitubercular activity against Mycobacterium tuberculosis (MTB) H37Ra and Mycobacterium bovis BCG in active and dormant state using an established methods. Compounds 5a, 5m, and 5t were identified as the most active compounds against MTB. Molecular docking was performed against MTB enoyl-ACP (CoA) reductase (FabI/ENR/InhA) enzyme to predict the binding modes and affinity. The theoretical predictions from molecular docking could establish a link between the observed biological activity and the binding affinity shedding light into specific bonded and non-bonded interactions influencing the activity. The active compounds were studied for cytotoxicity against three cell lines and were found to be non-cytotoxic. Specificity of these compounds was checked by screening them for their antibacterial activity against four bacterial strains.
Keywords: antibacterial activity; antituberculosis activity; cytotoxicity activity

Triazole-diindolylmethane conjugates as new antitubercular agents: synthesis, bioevaluation, and molecular docking - Danne, Ashruba B.; Choudhari, Amit S.; Chakraborty, Shakti; Sarkar, Dhiman; Khedkar, Vijay M.; Shingate, Bapurao B. (MedChemComm, 2018)
We describe the synthesis of novel triazole-incorporated diindolylmethanes (DIMs) using a molecular hybridization approach. The in vitro antitubercular activity of the DIMs against Mycobacterium tuberculosis H37Ra (ATCC 25177) was tested in the active and dormant state. Among all the synthesized conjugates, the compounds 6b, 6f, 6l, 6n, 6q, 6r, and 6s displayed good antitubercular activity against both the active and dormant Mtb H37Ra strain. The compound 6l exhibited good antitubercular activity against dormant Mtb H37Ra with an IC50 value of 1 g mL(-1) and IC90 (MIC) value of 3 g mL(-1). The compounds 6b, 6l, and 6r displayed good antitubercular activity against active Mtb H37Ra with IC50 values of 2.19, 1.52, and 0.22 g mL(-1), respectively. The compounds 6b, 6h, 6l, and 6s displayed more than 70% inhibition against the Gram-positive Bacillus subtilus strain at 3 g mL(-1). The molecular docking study showed the binding modes of the titled compounds in the active site of the DprE1 enzyme and assisted with elucidating a structural basis for the inhibition of Mycobacteria.

Ultrasound assisted synthesis of 4-(Benzyloxy)-N-(3-chloro-2-(substitutedphenyl)-4-oxoazetidin-1-yl) benzamide as challenging anti-tubercular scaffold - Nimbalkar, Urja D.; Seijas, Julio A.; Borkute, Rachna; Damale, Manoj G.; Sangshetti, Jaiprakash N.; Sarkar, Dhiman; Nikalje, Anna Pratima G. (Molecules, 2018)
A series of ten novel derivatives of 4-(benzyloxy)-N-(3-chloro-2-(substituted phenyl)-4-oxoazetidin-1-yl) benzamide 6a-j were synthesized in good yield from the key compound 4-(benzyloxy)-N-(substituted benzylidene) benzo hydrazide, called Schiff `s bases 5a-j, by Staudinger reaction ([2 + 2] ketene-imine cycloaddition reaction) with chloro acetyl chloride in the presence of catalyst tri ethylamine and solvent dimethyl formamide (DMF), by using ultra-sonication as one of the green chemistry tools. All the synthesised compounds were evaluated for in vitro anti-tubercular activity against Mycobacterium tuberculosis (MTB) and most of them showed promising activity with an IC50 value of less than 1 mu g/mL. To establish the safety, all the synthesized compounds were further tested for cytotoxicity against the human cancer cell line HeLa and all 6a-j compounds were found to be non-cytotoxic in nature. The molecular docking study was carried out with essential enzyme InhA (FabI/ENR) of Mycobacterium responsible for cell wall synthesis which suggests that 6a and 6e are the most active derivatives of the series. The theoretical evaluation of cell permeability based on Lipinski's rule of five has helped to rationalize the biological results and hence the synthesized azetidinone derivatives 6a-j were also analyzed for physicochemical evaluation that is, absorption, distribution, metabolism, excretion, and toxicity (ADMET) properties and the results showed that all the derivatives could comply with essential features required for a potential lead in the anti-tubercular drug discovery process.
Keywords: ADMET study; anti-tubercular screening; azetidinone; cytotoxicity study; green chemistry; Molecular docking; ultra-sonication

Click chemistry based multicomponent approach in the synthesis of spirochromenocarbazole tethered 1,2,3-triazoles as potential anticancer agents - Chavan, V, Pramod; Desai, V, Uday; Wadgaonkar, Prakash P.; Tapase, Savita R.; Kodam, Kisan M.; Choudhari, Amit; Sarkar, Dhiman (Bioorganic Chemistry, 2019)
A series of spirochromenocarbazole tethered 1,2,3-triazoles were synthesized via click chemistry based one-pot, five component reaction between N-propargyl isatins, malononitrile, 4-hydroxycarbazole, aralkyl halides and sodium azide using cellulose supported CuI nanoparticles (Cell-CuI NPs) as the heterogeneous catalyst. Antiproliferative activity of all the synthesized compounds was investigated against panel of cancer cell lines such as MCF-7, MDA-MB-231, HeLa, PANG-1, A-549, and THP-1. Many of the synthesized compounds exhibited good anti-proliferative activity against breast (MCF-7 and MDA-MB-231) and cervical (HeLa) cancer cells with IC50 values less than 10 mu M. In case of MCF-7 cells, among the nine compounds that showed good anti-proliferative activity, compounds 6f and 6j were found to be highly potent (IC50 , = 2.13 mu M and 4.80 mu M, respectively). In case of MDA-MB-231, three compounds (6k, 6j and 6s) showed antiproliferative activity amongst which 6k was the most potent one (IC50 = 3.78 mu M). On the other hand, in cervical cancer HeLa cells, compounds 6b, 6g, 6s and 6u showed excellent antiproliferative activity (IC50 = 4.05, 3.54, 3.83, 3.35 mu M, respectively). All the compounds were found to be nontoxic to the human umbilical vein endothelial cells (HUVECs). AO and EtBr staining and fluorescence microscopy studies of the active compounds (IC50 < 5 mu M) suggested that these compounds induce cell death by apoptosis.
Keywords: 1; 2; 3-Triazolylspirochromenocarbazole; Anticancer; Apoptotic assay; Click chemistry; Cytotoxicity; heterogeneous catalysis; Multicomponent synthesis

Design and synthesis of 2-amino-thiophene-proline-conjugates and their anti-tubercular activity against mycobacterium tuberculosis H37Ra - Baravkar, Sachin B.; Wagh, Mahendra A.; Nawale, Laxman U.; Choudhari, Amit S.; Bhansali, Sujit; Sarkar, Dhiman; Sanjayan, Gangadhar J. (ChemistrySelect, 2019)
The emergence of extensively drug resistant tuberculosis (XDRTB) and multi-drug resistant tuberculosis (MDR-TB) has necessitated the development of new drugs with short chemotherapy treatment regime and cost effectiveness. To overcome these challenges, we are reporting the synthesis of a series of 2-amino-thiophene-proline-conjugates which show potent invino and ex-vivo anti-tubercular (anti-TB) activity against mycobacterium tuberculosis (rntb) H37Ra. The synthesis of these 2-amino-thiophene-proline-conjugates was carried out via solution phase peptide coupling reactions using methyl-2aminothiophene-3-carboxylate 8 as an intermediate obtained by modified gewald reaction. Intermediate 8 was coupled with different amino acids to obtain dipeptides 3, 4, 5, 6a and 7. Priliminary anti-TB assay data encoureaged us to synthesize modified proline derivatives 6b-6k via formation of a benzoxazinone intermediate 16. Most of these conjugates are active against mtb H37Ra in both active (A) and dormant (D) strains. They are also active against drug resistant mtb H37Ra strains. A trifluoroethyl ester analog, 6i was the most potent among the series [MIC 1 mu g/mL] along with 6f and 6g [MIC 2-6 mu g/mL]. Cytotoxicity studies suggested that, these compounds are less cytotoxic to human cell lines HeLa, MCF-7, HUVEC and hence possess high selectivity index (SI). Docking studies revealed that the binding mode of most active compounds 6i, 6g and 6f is in accordance with their bioactivity studies having docking score 8.969, 8.446 and 7.865, respectively. More- over, in sllico ADME properties suggest that all the compounds possess drug like properties.
Keywords: 2-aminothiophene; Anti-tubercular; docking studies; Inh A gene; selectivity index

Design, synthesis and biological evaluation of (E)-5-styryl-1,2,4-oxadiazoles as anti-tubercular agents - Upare, Abhay Atmaram; Gadekar, Pradip K.; Sivaramakrishnan, H.; Naik, Nishigandha; Khedkar, Vijay M.; Sarkar, Dhiman; Choudhari, Amit; Roopan, S. Mohana (Bioorganic Chemistry, 2019)
Cinnamic acid and its derivatives are known for anti-tubercular activity. The present study reports the synthesis of cinnamic acid derivatives via bioisosteric replacement of terminal carboxylic acid with ``oxadiazole''. A series of cinnamic acid derivatives (styryl oxadiazoles) were designed and synthesized in good yields by reaction of substituted cinnamic acids (2, 15a-15s) with amidoximes. The synthesized styryl oxadiazoles were evaluated in vitro for anti-tubercular activity against Mycobacterium tuberculosis (Mtb) H37Ra strain. The structure-activity relationship (SAR) study has identified several compounds with mixed anti-tubercular profiles. The compound 32 displayed potent anti-tubercular activity (IC50= 0.045 mu g/mL). Molecular docking studies on mycobacterial enoyl-ACP reductase enzyme corroborated well with the experimental findings providing a platform for structure based hit-to-lead development.
Keywords: 1; 2; 4-Oxadiazole; Anti-tubercular; Bioisosteres; Cinnamic acid; Molecular docking

Evidence of nitrite acting as a stable and robust inducer of non-cultivability in Mycobacterium tuberculosis with physiological relevance - Gample, Suwarna P.; Agrawal, Sonia; Sarkar, Dhiman (Scientific Reports, 2019)
Tuberculosis (TB) is the ninth leading cause of death worldwide, ranking above human immunodeficiency virus. Latency is the major obstacle in the eradication of this disease. How the physiology of the pathogen changes in transition to the latent stage needs to be understood. The latent bacteria extracted from animal hosts exist in a nonculturable (NC) phase, whereas bacteria extracted from most in vitro models are culture-positive. In the present study, we observed that nitrite, up to a concentration of 5 mM, shows the growth of Mycobacterium tuberculosis (MTB) in liquid media, but this effect starts reversing at higher concentrations. At a concentration of 10 mM, nitrite induces rapid nonculturability of MTB at the aerobic stage. This noncultivable dormancy was confirmed by analyzing the characteristics of NC bacteria. Further differential gene expression analyses clearly supported the formation of a dormancy phenotype. This study will be helpful for the use of this bacillus as a dormancy model in future studies on TB latency.

High content screening assay for identifying inhibitors against active and dormant state intracellular Mycobacterium tuberculosis - Yeware, Amar; Agrawal, Sonia; Sarkar, Dhiman (Journal of Microbiological Methods, 2019)
The antitubercular drug development pipeline could start with an in vitro investigation of several compounds to examine their effect on active and dormant state Mycobacterium tuberculosis (Mtb). However, in vitro screening of dormant state bacilli cannot provide enough information on the simultaneous effect of a compound on the host. Therefore, we developed a live cell fluorescence based screening protocol by utilizing the high content system for determining the effect of inhibitors against active and dormant state intracellular mycobacteria. THP-1 macrophages infected with an actively growing and hypoxia derived dormant Mtb culture were standardized to develop the screening protocol. The signal to noise ratio and the Z' factor of this assay were found to be 7.5-29 and 0.6-0.8, respectively, which confirm the robustness of the protocol. The protocol was then validated with standard inhibitors. This newly developed drug screening assay offers an easy, safe, image based high content screening tool to search for novel antitubercular inhibitors against both active and dormant state intracellular mycobacteria. Therefore, this assay could fill in the gap between in vitro and in vivo latent tuberculosis drug screening programs.

Non nucleoside reverse transcriptase inhibitors, molecular docking studies and antitubercular activity of thiazolidin-4-one derivatives - Chitre, Trupti S.; Patil, Shital M.; Sujalegaonkar, Anagha G.; Asgaonkar, Kalyani D.; Khedkar, Vijay M.; Garud, Dinesh R.; Jha, Prakash C.; Gaikwad, Sharddha Y.; Kulkarni, Smita; Choudhari, Amit; Sarkar, Dhiman (Current Computer-Aided Drug Design, 2019)
Background: Management of Co-existence of Acquired immunodeficiency syndrome and Tuberculosis has become a global challenge due to the emergence of resistant strains and pill burden. Objective: Hence the aim of the present work was to design and evaluate compounds for their dual activity on HIV-1 and Tuberculosis (TB). Methods: A series of seven, novel Thiazolidin-4-one derivatives were synthesized and evaluated for their anti-HIV and anti-tubercular activity along with Molecular docking studies. All the seven compounds displayed promising activity against the replication of HIV-1 in cell-based assays. The four most active compounds were further evaluated against X4 tropic HIV-1(UG)(070) and R5 tropic HIV-1(vB59) primary isolates. The binding affinity of all the designed compounds for HIV-RT and Mycobacterium tuberculosis Enol Reductase (MTB InhA) was gauged by molecular docking studies which revealed crucial thermodynamic interactions governing their binding. Results: The CC50 values for the test compounds were in the range of, 15.08-34.9 mu g/ml, while the IC50 values were in the range of 16.1-27.13(UG(070); X4) and 12.03-23.64 (VB59; R5) mu g/ml. The control drug Nevirapine (NVP) exhibited CC50 value of 77.13 mu g/ml and IC50 value of 0.03 mu g/ml. Amongst all these compounds, compound number 3 showed significant activity with a TI value of 2.167 and 2.678 against the HIV-1 X4 and the R5 tropic virus respectively. In anti-mycobacterial screening, the compounds proved effective in inhibiting the growth of both log phase and starved MTB cultures. Conclusion: Compound 3 has been found to be active against HIV-1 as well as MTB.
Keywords: anti-HIV-1 activity; Antitubercular activity; human immunodeficiency virus-1; Molecular docking; Non nucleoside reverse transcriptase; thiazolidin-4-ones

Recursive partitioning analysis and anti-tubercular screening of 3-aminopyrazine-2-carbohydrazide derivatives - Miniyar, Pankaj; Mahajan, Anand; Anuse, Dattatray; Kumar, Ashish; Barmade, Mahesh; Sarkar, Dhiman; Arkile, Manisha; Khedkar, Vijay (Letters in Drug Design & Discovery, 2019)
Background: Treating tuberculosis is a challenge due to the development of drug resistance. Hence, it is imperative to develop novel leads having high potency and efficacy to curb drug resistance. Methods: The present research work is focused on microwave-assisted synthesis of novel twenty-six 3-amino-N'-benzylidenepyrazine-2-carbohydrazide derivatives (3a-z), where, lyophilization technique was used for isolation of the major intermediate, 3-aminopyrazin-2-carbohydrazide. All synthesized compounds were subjected for anti-tubercular screening against Mycobacterium tuberculosis H37Ra by using XTT Reduction Menadione Assay (XRMA) protocol. Results: Out of 26 synthesized compounds, four N'-substitutedbenzaldehyde-3-amino-pyrazine-2-carbohydrazide derivatives viz. 3i, 3j 3v and 3z showed significant activity against M. tuberculosis H37Ra. The compounds 3i, 3j, 3v and 3z showed 99, 98, 92 and 87 % inhibition respectively as compared to 94% inhibition shown by the standard drug rifampicin. The MIC and IC50 values were in the range of 24.3-110 and 5.9-20.8 mu g/ml respectively. Conclusion: A classification model called Recursive Partitioning (RP) based on binary Quantitative Structure-Activity Relationship (QSAR) was derived for the establishment of structure-activity relationship (SAR). The predictions derived on the basis of RP model were found to be in agreement with anti-tubercular screening data.
Keywords: 3-aminopyrazine; anti-tubercular activity; Carbohydrazide; lyophilization; QSAR; recursive partitioning

Synthesis and antimycobacterial evaluation of new 5-(1-benzyl-1H-1,2,3-triazol-4-yl)-4-methyl-2-arylthiazole derivatives - Shinde, Vikas; Mahulikar, Pramod; Mhaske, Pravin C.; Chakraborty, Shakti; Choudhari, Amit; Phalle, Siddharth; Choudhari, Prafulla; Sarkar, Dhiman (Medicinal Chemistry Research, 2019)
A new series of 5-(1-benzyl-1H-1,2,3-triazol-4-yl)-4-methyl-2-arylthiazole derivatives, 6a-w have been synthesized by click reaction of substituted benzylazide, 5a-d with 5-ethynyl-4-methyl-2-substituted phenylthiazole, 4a-f. The starting compounds 4-ethynyl-2-substituted phenylthiazole (4a-f) were synthesized from the corresponding thiazole aldehyde by using the Ohira-Bestmann reagent. The structure of the synthesized compounds was determined by spectral analysis. All the synthesized compounds were screened for their preliminary antitubercular activity against Mycobacterium tuberculosis H37Ra (MTB, ATCC 25177). Most of the synthesized compounds reported good activity against M. tuberculosis H37Ra strain with IC50 range of 0.58-8.23 mu g/mL. Compounds 6g and 6k reported good antitubercular activity with MIC90 values of 4.71 and 2.22 mu g/mL, respectively. Potential antimycobacterial activity suggested that these compounds could serve as good lead compounds for further optimization and development of a newer antitubercular candidate. [GRAPHICS] .
Keywords: 1; 2; 3-Triazole; Antitubercular activity; Molecular docking; Ohira-Bestmann reagent; Thiazole

Synthesis and biological evaluation of 2,4,5-trisubstituted thiazoles as antituberculosis agents effective against drug-resistant tuberculosis - Karale, Uttam B.; Krishna, Vagolu Siva; Krishna, E. Vamshi; Choudhari, Amit S.; Shukla, Manjulika; Gaikwad, Vikas R.; Mahizhaveni, B.; Chopra, Sidharth; Misra, Sunil; Sarkar, Dhiman; Sriram, Dharmarajan; Dusthackeer, V. N. Azger; et al. (European Journal of Medicinal Chemistry, 2019)
The dormant and resistant form of Mycobacterium tuberculosis presents a challenge in developing new anti-tubercular drugs. Herein, we report the synthesis and evaluation of trisubstituted thiazoles as antituberculosis agents. The SAR study has identified a requirement of hydrophobic substituent at C2, ester functionality at C4, and various groups with hydrogen bond acceptor character at C5 of thiazole scaffold. This has led to the identification of 13h and 13p as lead compounds. These compounds inhibited the dormant Mycobacterium tuberculosis H37Ra strain and M. tuberculosis H37Rv selectively. Importantly, 13h and 13p were non-toxic to CHO cells. The 13p showed activity against multidrug-resistant tuberculosis isolates. (C) 2019 Elsevier Masson SAS. All rights reserved.

Synthesis and biological evaluation of new 4-(4-(1-benzyl-1H-1,2,3-triazol-4-yl)phenyl)-2-phenylthiazole derivatives - Shinde, Vikas; Mhaske, Pravin C.; Singh, Aakriti; Sarkar, Dhiman; Mahulikar, Pramod (Journal of Heterocyclic Chemistry, 2019)
A novel series of 4-(4-(1-benzyl-1H-1,2,3-triazol-4-yl)phenyl)-2-substitutedthiazole derivatives (8a-l) have been synthesized by [3 + 2] cycloaddition reaction of 4-(4-ethynylphenyl)-2-substitutedthiazole with substituted benzyl azide in aqueous DMF. Starting compounds 4-(4-ethynylphenyl)-2-substitutedthiazole (6a-d) were synthesized by reaction of 4-(2-substitutedthiazol-4-yl)benzaldehyde with Ohira-Bestmann reagent in methanol. The structures of these novel triazole-thiazole clubbed derivatives were confirmed by the spectral analysis. The title compounds (8a-l) were tested for antimycobacterial activity against Mycobacterium tuberculosis H37Ra active and dormant (MTB, ATCC 25177) and antimicrobial activity against standard Gram-positive bacteria, Staphylococcus aureus (NCIM 2602) and Bacillus subtilis (NCIM 2162), and Gram-negative bacteria, Escherichia coli (NCIM 2576) and Pseudomonas flurescence (NCIM 2059). Compounds 8a, 8b, 8c, and 8h reported good activity against B subtilis, compounds 8a, 8b, and 8c showed good activity against S aureus, and compound 8b showed good activity against dormant M tuberculosis H37Rv strain. Compounds 8b and 8c found more potent against Gram positive and dormant M tuberculosis H37Rv strains. These novel triazole-thiazole clubbed analogues found to be a capable leads for further optimization and development.

Synthesis of new 1,3,4-oxadiazole and benzothiazolylthioether derivatives of 4-arylmethylidene-3-substituted-isoxazol-5(4H)-one as potential antimycobacterial agents - Chavan, Abhijit P.; Deshpande, Rujuta R.; Borade, Nandkumar A.; Shinde, Abhijit; Mhaske, Pravin C.; Sarkar, Dhiman; Bobade, Vivek D. (Medicinal Chemistry Research, 2019)
A new series of 4-[(substituted benzylidene)-3-[(5-(pyridine-4-yl)-1,3,4-oxadiazole-2-ylthio)-methyl]i soxazol-5(4H)-one (6a-g) and 4-(substituted benzylidene)-3-((benzo[d]thiazol-2-ylthio)methyl)isoxazol-5(4H)-one (8a-g) was synthesized. All the synthesized compounds were screened for antitubercular activity against Mycobacterium tuberculosis H37Ra (ATCC 25177) and Mycobacterium bovis BCG (ATCC 35743) and antibacterial activity against Escherichia coli (NCIM 2576), Pseudomonas flurescence (NCIM 2059), Staphylococcus aureus (NCIM 2602), Bacillus subtilis (NCIM 2162). Amongst the synthesized 1,3,4-oxadiazole and benzothiazoyl thioether derivatives, compounds 6b and 8b showed excellent antimycobacterial activity and compounds 6b, 8a, 8b, and 8d showed excellent antibacterial activity against all tested antibacterial strains. The synthesized compounds were further evaluated for their cytotoxic activity against the HCT 116 and HeLa cancer cell lines. The 1,3,4-oxadiazole and benzothiazoyl thioether derivatives 6a-g and 8a-g did not show cytotoxicity.
Keywords: 1; 3; 4-Oxadiazole; antibacterial activity; Antitubercular activity; Benzothiazol; Isoxazol-5(4H)-one; Thioeteher

Thiazolyl-pyrazole derivatives as potential antimycobacterial agents - Takate, Sushma J.; Shinde, Abhijit D.; Karale, Bhausaheb K.; Akolkar, Hemant; Nawale, Laxman; Sarkar, Dhiman; Mhaske, Pravin C. (Bioorganic & Medicinal Chemistry Letters, 2019)
Mycobacterium tuberculosis (Mtb) is an obligate aerobe that is capable of long-term persistence under conditions of low oxygen tension. A series of thiazolyl-pyrazole derivatives (6a-f, 7a-f, 8c, 8e) were screened for antimycobacterial activity against dormant M. tuberculosis H37Ra (D-MTB) and M. bovis BCG (D-BCG). Nine thiazolyl- pyrazole analogs, 6c, 6e, 7a, 7b, 7c, 7e, 7f, 8c and 8e exhibited promissing minimum inhibitory concentration (MIC) values (0.20-28.25 mu g/mL) against D-MTB and D-BCG strains of Mtb. Importantly, six compounds (7a, 7b, 7e, 7f, 8c and 8e) exhibited excellent antimycobacterial activity and low cytotoxicity at the maximum evaluated concentration of > 250 mu g/mL. Finally, the promising antimycobacterial activity and lower cytotoxicity profile suggested that, these compounds could be further subjected for optimization and development as a lead, which could have the potential to treat tuberculosis.
Keywords: antimycobacterial activity; Cytotoxicity; Pyrazole; thiazoles

Using diphenyleneiodonium to induce a viable but non-culturable phenotype in Mycobacterium tuberculosis and its metabolomics analysis - Yeware, Amar; Gample, Suwarna; Agrawal, Sonia; Sarkar, Dhiman (Plos One, 2019)
Depletion of oxygen levels is a well-accepted model for induction of non-replicating, persistent states in mycobacteria. Increasing the stress levels in mycobacterium bacilli facilitates their entry into a non-cultivable, dormant state. In this study, it was shown that diphenyleneiodonium, an inhibitor of NADH oxidase, induced a viable, but non-culturable state in mycobacteria, having similar features to dormant bacilli, like loss of acid-fastness, upregulation of stress-regulated genes and decreased superoxide levels as compared to actively growing bacilli. Comprehensive, untargeted metabolic profiling also confirmed a decrease in biogenesis of amino acids, NAD, unsaturated fatty acids and nucleotides. Additionally, an increase in the level of lactate, fumarate, succinate and pentose phosphate pathways along with increased mycothiol and sulfate metabolites, similar to dormant bacilli, was observed in the granuloma. These non-cultivable bacilli were resuscitated by supplementation of fetal bovine serum, regaining their culturability in liquid as well as on agar medium. This study focused on the effect of diphenyleneiodonium treatment in causing mycobacteria to rapidly transition from an active state into a viable, but non-cultivable state, and comparing their characteristics with dormant phenotypes.

Anticancer potential of AgNPs synthesized using acinetobacter sp. and curcuma aromatica against HeLa cell lines: a comparative study - Nadhe, Shradhda B.; Tawre, Madhumita S.; Agrawal, Sonia; Chopade, Balu A.; Sarkar, Dhiman; Pardesi, Karishma (Journal of Trace Elements in Medicine and Biology, 2020)
Background: Biogenic nanoparticles are gaining attention due to their low toxicity and numerous biomedical applications. Present study aimed to compare the potential anticancer activity of two biogenic silver nanoparticles (bAgNPs and pAgNPs) against human cervical cancer cell lines (HeLa). Methods: bAgNPs were synthesized using Acinetobacter sp. whereas pAgNPs were synthesized using aqueous root extract of Curcuma aromatica. Effect of these nanoparticles on HeLa cells viability was studied using MTT assay and colony formation assay. Anticancer potential was determined using fluorescence microscopy and flow cytometry studies. Bio-compatibility studies were performed against peripheral blood mononuclear cells (PBMCs). Results: Both the nanoparticles showed 50 % viability of peripheral blood mononuclear cells (PBMCs) when used at high concentration (200 mu g/mL). IC50 for bAgNPs and pAgNPs against HeLa cells were 17.4 and 14 mu g/mL respectively. Colony formation ability of Hela cells was reduced on treatment with both nanoparticles. Acridine orange and ethidium bromide staining demonstrated that bAgNPs were cytostatic whereas pAgNPs were apoptotic. JC-1 dye staining revealed that the mitochondrial membrane potential was affected on treatment with pAgNPs while it remained unchanged on bAgNPs treatment. Flow cytometry confirmed cell cycle arrest in HeLa cells on treatment with nanoparticles further leading to apoptosis in case of pAgNPs. About 77 and 58 % HeLa cells were found in subG1 phase on treatment with bAgNPs and pAgNPs respectively. bAgNPs showed cytostatic effect on HeLa cells arresting the cell growth in subG1 phase, whereas, pAgNPs triggered death of HeLa cells through mitochondrial membrane potential impairment and apoptosis. Conclusion: Overall, bAgNPs and pAgNPs could be safe and showed potential to be used as anticancer nanoantibiotics against human cervical cancer cells.
Keywords: Acinetobacter sp.; AgNPs; Anticancer; Curcuma aromatica; HeLa cells; PBMCs

Exploring the pharmacological potentials of biosurfactant derived from planococcus maritimus SAMP MCC 3013 - Waghmode, Samadhan; Swami, Sagar; Sarkar, Dhiman; Suryavanshi, Mangesh; Roachlani, Sneha; Choudhari, Prafulla; Satpute, Surekha (Current Microbiology, 2020)
Therapeutic potential of biosurfactant (BS) has been improved in recent years. Our present study deals with production of BS from Planococcus maritimus SAMP MCC 3013 in a mineral salt medium (MSM) supplemented with glucose (1.5% w/v). Further, BS has been purified and partially characterized as glycolipid type through our previous publication. Current research article aimed to evaluate biological potential of BS against Mycobacterium tuberculosis, Plasmodium falciparum and cancerous cell lines. Planococcus derived glycolipid BS was found to be a promising inhibitor of M. tuberculosis (MTB) H37Ra at IC50 64.11 +/- 1.64 mu g/mL and MIC at 160.8 +/- 1.64 mu g/mL. BS also showed growth inhibition of P. falciparum at EC50 34.56 +/- 0.26 mu M. Additionally, BS also displayed the cytotoxicity against HeLa (IC50 41.41 +/- 4.21 mu g/mL), MCF-7 (IC50 42.79 +/- 6.07 mu g/mL) and HCT (IC50 31.233 +/- 5.08 mu g/mL) cell lines. Molecular docking analysis was carried for the most popular glycolipid type BS namely Rhamnolipid (RHL) aiming to interpret the possible binding interaction for anti-tubercular and anti-cancer activity. This analysis revealed the involvement of RHL binding with enoyl reductase (InhA) of M. tuberculosis. Docking studies of RHL with tubulin directed several hydrophobic and Vander Waal interactions to exhibit anti-cancer potential. The present study will be helpful for further development of marine bioactive molecules for therapeutic applications. Their anti-tubercular, anti-plasmodial and cytotoxic activities make BS molecules as a noteworthy candidate to combat several diseases. To the best of our knowledge, this is the first report on projecting the pharmacological potential of Planococcus derived BS. Graphic

Synthesis and antimycobacterial screening of new 4-(4-(1-benzyl-1H-1,2,3-triazol-4-yl)-1-phenyl-1H-pyrazol-3-yl)quinoline derivatives - Thakare, Prashant P.; Walunj, Yogesh; Chavan, Abhijit; Bobade, Vivek D.; Sarkar, Dhiman; Mhaske, Pravin C. (Journal of Heterocyclic Chemistry, 2020)
A new series of 4-(4-(1-benzyl-1H-1,2,3-triazol-4-yl)-1-phenyl-1H-pyrazol-3-yl)quinoline (6a-t) have been synthesized by a click reaction of 4-(4-ethynyl-1-phenyl-1H-pyrazol-3-yl)quinoline (4a-d) with a substituted benzyl azide (5a-e). The starting alkyne derivatives4a-dare obtained from Bestmann-Ohira reaction of 1-phenyl-3-(quinolin-4-yl)-1H-pyrazole-4-carbaldehyde and dimethyl(1-diazo-2-oxopropyl)phosphonate. The newly synthesized compounds are screened againstM. tuberculosisH37Ra dormant and active,Escherichia coli,Pseudomonas fluorescence,Staphylococcus aureusandBacillus subtilisstrains at 30 mu g/mL concentration. Most of the screened compounds showed good to moderate antibacterial activity againstS. aureus,B. subtilis, andMycobacterium tuberculosisH37Ra strains. The synthesized derivatives of quinolinyl-pyrazole-4-carbaldehyde and quinolinyl-pyrazole-4-ethyne reportd good to moderate activity against both strains ofM. tuberculosisH37Ra. Ten derivatives of quinolinyl-pyrazole presented good activity againstB. subtilis. These results suggested that further optimization and development of quinolinyl-pyrazolyl-1,2,3-triazole moeity could serve as lead compounds for antimycobacterial activity.

2D-QSAR modeling and two-fold classification of 1,2,4-triazole derivatives for antitubercular potency against the dormant stage of Mycobacterium tuberculosis - Aher, Rahul Balasaheb; Sarkar, Dhiman (Molecular Diversity, 2021)
The dormant or latent form of Mycobacterium tuberculosis (MTB) is not killed by the conventional antitubercular drugs. The treatment of latent TB is essential to reduce the period of treatment as well as incidences of drug resistance. In this background, we have made an attempt to develop the quantitative structure-activity relationship models (QSAR: regression and classification based) against the dormant form of MTB and later used the developed classifier models (linear discriminant analysis (LDA) and random forest (RF)) for the two-fold classifications. The logic of applying this concept of two-fold classification for the MTB modeling is to increase the confidence of correct classification. The 2D-QSAR modeling suggested the contribution of burden eigen, edge adjacency, van der Waals (vdW) surface area, topological charge, and pharmacophoric indices in predicting the antitubercular activity against the dormant MTB. The prediction qualities of the training and test sets were found to be moderate and good, according to the mean absolute error (MAE)-based criteria's. The LDA and RF models unveiled the importance of burden eigen, edge adjacency, Geary autocorrelation, and drug-like indices as discriminating features to differentiate the antitubercular compounds into higher and lower active groups. The LDA model showed the classification accuracies of 85.14% and 87.10% for the training and test sets, while the RF model exhibited the accuracies of 100.00% and 80.65% for both the sets. The descriptors selected in the final models are only two-dimensional (2D), which are easy to compute and does not require computationally expensive steps of structure conversion, optimization, and energy minimization mandatorily needed before the computation of 3D descriptors. These models could be used for identifying and selection of higher active compounds against the dormant form of the MTB.
Keywords: Classification models; Dormant TB; Linear discriminant analysis (LDA); Mycobacterium tuberculosis (MTB); Nonlinear modeling; QSAR; Random forest (RF)

In silico studies, synthesis and antitubercular activity of some novel quinoline - azitidinone derivatives - Chitre, Trupti S.; Asgaonkar, Kalyani D.; Vikhe, Amrut B.; Patil, Shital M.; Garud, Dinesh R.; Khedkar, Vijay M.; Sarkar, Dhiman; Nawale, Laxman U.; Yeware, Amar (Current Computer-Aided Drug Design, 2021)
Background: Diarylquinolines like Bedaquiline have shown promising antitubercular activity by their action of Mycobacterial ATPase. Objective: The structural features necessary for a good antitubercular activity for a series of quinoline derivatives were explored through computational chemistry tools like QSAR and combinatorial library generation. In the current study, 3-Chloro-4-(2-mercaptoquinoline-3-yl)-1-substitutedphenylazitidin-2-one derivatives have been designed and synthesized based on molecular modeling studies as anti-tubercular agents. Methods: 2D and 3D QSAR analyses were used to designed compounds having a quinoline scaffold. The synthesized compounds were evaluated against active and dormant strains of Mycobacterium tuberculosis (MTB) H37 Ra and Mycobacterium bovis BCG. The compounds were also tested for cytotoxicity against MCF-7, A549 and Panc-1 cell lines using MTT assay. The binding affinity of designed compounds was gauged by molecular docking studies. Results: Statistically significant QSAR models generated by the SA-MLR method for 2D QSAR exhibited r(2) = 0.852, q(2) = 0.811, whereas 3D QSAR with SA-kNN showed q(2) = 0.77. The synthesized compounds exhibited MIC in the range of 1.38-14.59(mu g/ml). These compounds showed some crucial interaction with MTB ATPase. Conclusion: The present study has shown some promising results which can be further explored for lead generation.
Keywords: combilib; Molecular docking; mycobacterial ATPase; QSAR; Quinoline

In vitro antitubercular screening and in silico study of germacradienolide from blainvillea latifolia - Honmore, Varsha; Kalyankar, Vidya; Natu, Arun; Khedkar, Vijay; Sarkar, Dhiman; Rojatkar, Supada (Asian Journal of Chemistry, 2021)
Bioassay-guided isolation from acetone extract of Blainvillea latifolia yielded one compound. The acetone extract, fractions and the compound 1 were investigated for antitubercular activity against Mycobacterium tuberculosis H37Ra. Compound 1 showed the activity with IC50 and MIC values at 8.9 and >100 μg/mL. However, the acetone extract of Blainvillea latifolia was inactive against two Gram negative (E. coli, P. flurescence) and two Gram-positive (S. aureus, B. subtilis) bacterial strains. Hence, it was concluded that the extract and the compound 1 are specifically active against MTB and not against bacterial strains. Molecular docking study was performed against crucial mycobacterial target MtInhA to gain an insight into the binding mode and the thermodynamic interactions governing the binding affinity of this molecule.

Novel gene similar to nitrite reductase (NO forming) plays potentially important role in the latency of tuberculosis - Agrawal, Sonia; Gample, Suwarna; Yeware, Amar; Sarkar, Dhiman (Scientific Reports, 2021)
The development of the latent phenotype of Mycobacterium tuberculosis (Mtb) in the human lungs is the major hurdle to eradicate Tuberculosis. We recently reported that exposure to nitrite (10 mM) for six days under in vitro aerobic conditions completely transforms the bacilli into a viable but non-cultivable phenotype. Herein, we show that nitrite (beyond 5 mM) treated Mtb produces nitric oxide (NO) within the cell in a dose-dependent manner. Our search for the conserved sequence of NO synthesizing enzyme in the bacterial system identified MRA2164 and MRA0854 genes, of which the former was found to be significantly up regulated after nitrite exposure. In addition, the purified recombinant MRA2164 protein shows significant nitrite dependent NO synthesizing activity. The knockdown of the MRA2164 gene at mRNA level expression resulted in a significantly reduced NO level compared to the wild type bacilli with a simultaneous return of its replicative capability. Therefore, this study first time reports that nitrite induces dormancy in Mtb cells through induced expression of the MRA2164 gene and productions of NO as a mechanism for maintaining non-replicative stage in Mtb. This observation could help to control the Tuberculosis disease, especially the latent phenotype of the bacilli.

Online tools and antiviral databases for the development of drugs against coronaviruses - Aher, Rahul Balasaheb; Sarkar, Dhiman (In Silico Modeling of Drugs Against Coronaviruses: Computational Tools and Protocols, 2021)
The current crisis of coronavirus pandemic has created an urgent need for readily available scientific information to the researchers, students, professionals, and journalists. The scientific information for the research is costly, and most of the universities and research institutes cannot afford to subscribe to all the coronavirus-related journals/articles during this crisis time. In order to expedite the process of vaccine development and discovery of anti-COVID drugs, most of the pharmaceutical companies, research institutes and publishers are playing a key role and working on war footing to get either a vaccine or an anti-COVID drug as early as possible. The collective efforts are required from everyone in this testing time of the corona crisis. To provide our contribution to the scientific community, we have made here an attempt to give an overview of some of the tools and resources freely available that probably provide some insights in data mining and screening of novel lead molecules toward coronavirus. We have collected and compiled the information of open access online tools and antiviral databases essential for the discovery and development of corona vaccine and anti-COVID drugs. The open access tools include Open Educational Resources (OERs), Google cloud, online prediction server, web-based viewer, etc., while the antiviral databases include libraries of synthetic and untested compounds, antiviral drug databases, antiviral peptides, etc. The information presented in this chapter will help the researchers to use them directly in their projects of coronavirus drug discovery.

Pharmacophore modeling of pretomanid (PA-824) derivatives for antitubercular potency against replicating and non-replicating Mycobacterium tuberculosis - Aher, Rahul Balasaheb; Sarkar, Dhiman (Journal of Biomolecular Structure & Dynamics, 2021)
Pretomanid (PA-824) is the recently (2019) approved drug for the treatment of extensively drug-resistant (XDR) TB and the multidrug-resistant (MDR) TB by US FDA. The experimental data of antitubercular activity of 543 pretomanid derivatives (total 6 datasets) against replicating (active) and non-replicating (dormant) forms of Mycobacterium tuberculosis (strain H37Rv) are available in the literature. Such vast experimental data of pretomanid derivatives against both of these endpoints, and recent approval of pretomanid molecule as a drug encouraged us to utilize this existing experimental information for the development of the 3D-pharmacophore models. The developed model (Hypo-1, MABA) showed the three physicochemical features namely, the oxygen atom of nitro group (HBA_1), fused pyran ring of imidazopyran heterocycle (HYAl_2) and the 4-fluorophenyl moiety (HYAr_3) are crucial for the antitubercular activity against replicating M. tb. Subsequently, the pharmacophore model (Hypo-1, LORA) developed against the non-replicating form of M. tb also showed the contribution of three physicochemical features namely, the 4-tri-fluoromethyl group (HYAl_2) and both the phenyl groups (HYAr_3, HYAr_4) of biaryl moiety in increasing the antitubercular activity. Both the pharmacophoric classifier models showed the classification accuracies of 82.98 and 74.42% for the training set compounds, and 63.91 and 61.60% for the test set compounds respectively, for labelling the compounds into higher and lower active classes. Both the models were also found to be retaining the higher active compounds in top 1.00% of the total number of compounds (decoys and actives), after performing the decoy set screening. Communicated by Ramaswamy H. Sarma
Keywords: LORA assay; MABA assay; Mycobacterium tuberculosis; non-replicating M; pharmacophore modeling; pretomanid derivatives; replicating M; tuberculosis; virtual screening

Synthesis and cell imaging applications of fluorescent mono/di/tri-heterocyclyl-2,6-dicyanoanilines (vol 27, pg 979, 2017) - Pisal, Mahesh M.; Annadate, Ritesh A.; Athalye, Meghana C.; Kumar, Deepak; Chavan, Subhash P.; Sarkar, Dhiman; Borate, Hanumant B. (Bioorganic & Medicinal Chemistry Letters, 2021)

Synthesis of new 2-(thiazol-4-yl)thiazolidin-4-one derivatives as potential anti-mycobacterial agents - Abhale, Yogita K.; Shinde, Abhijit; Shelke, Monika; Nawale, Laxman; Sarkar, Dhiman; Mhaske, Pravin C. (Bioorganic Chemistry, 2021)
To search for potent antimycobacterial lead compounds, a new series of 3-substituted phenyl-2-(2-(substituted phenyl)thiazol-4-yl) thiazolidin-4-one (5a-t) derivatives have been synthesized by the condensation of 2 substituted phenyl thiazole-4-carbaldehyde with aromatic amine followed by cyclocondensation with thioglycolic acid. The structure of the newly synthesized 2-(thiazol-4-yl)thiazolidin-4-one derivatives were characterized by the spectroscopic analysis. The synthesized compounds were screened for antimycobacterial activity against Mycobacterium tuberculosis H37Ra (MTB) (ATCC 25177) and Mycobacterium bovis BCG (BCG, ATCC 35743). Most of the 2-(thiazol-4-yl)thiazolidin-4-one derivatives showed good to excellent antimycobacterial activity against both the Mtb strains. Nine derivatives 5c, 5g, 5j, 5m, 5n, 5o, 5p, 5s, and 5t showed excellent activity against M. bovis BCG with MIC 4.43 to 24.04 mu M were further evaluated for the cytotoxicity activity against HeLa A549, and HCT-116 cell lines and showed no significant cytotoxic activity at the maximum concentration evaluated. The potential antimycobacterial activities enforced that the thiazolyl-thiazolidin-4-one derivatives could lead to compounds that could treat tuberculosis.
Keywords: Cytotoxicity; Mycobacterium tuberculosis; Thiazole; Thiazolidin-4-one

Amide-linked monocarbonyl curcumin analogues: efficient synthesis, antitubercular activity and molecular docking study - Subhedar, Dnyaneshwar D.; Shaikh, Mubarak H.; Nagargoje, Amol A.; Akolkar, V. Satish; Bhansali, Sujit G.; Sarkar, Dhiman; Shingate, Bapurao B. (Polycyclic Aromatic Compounds, 2022)
An approach toward the synthesis of novel conjugates of 3,5-bis (arylidene)-4-piperidones (DAP) pharmacophore with amide-linkage has been developed via one-pot multicomponent reaction of aryl aldehydes, piperidinone and 2-chloro-N-phenylacetamide using [Et3NH][HSO4] as a catalyst/medium. Both substitutions on arylidene rings and piperidinone nitrogen (substituted 2-chloro-N-phenylacetamide) were varied. The synthesized conjugates were evaluated for their in vitro antitubercular activity against M. tuberculosis H37Ra (MTB) and M. bovis BCG strains. Among the series, compounds 4f, 4g, 4i and 4j showed remarkable broad spectrum antitubercular activity with low IC50 values. Furthermore, computer docking simulations, for the most active conjugates were performed with the active site of mycobacterial enoyl-acyl carrier protein reductase (InhA) support the antitubercular activity. Lower cytotoxicity, high potency and promising activity against MTB and M. Bovis BCG suggest that amide linked DAP could serve as good leads for further modifications and development.
Keywords: antimycobacterial activity; Bis (arylidene)-4-piperidones; Cytotoxicity; Ionic liquid; Molecular docking Study

Conventional and microwave-assisted organic synthesis of novel antimycobacterial agents bearing furan and pyridine hybrids - Desai, Nisheeth C.; Bhatt, Kandarp; Jadeja, Dharmpalsinh J.; Mehta, Harsh K.; Khedkar, Vijay M.; Sarkar, Dhiman (Drug Development Research, 2022)
Drug resistance in tuberculosis poses a serious threat to humanity because currently available antitubercular drugs are ineffective against Mycobacterium tuberculosis (M. tuberculosis). As a result, the approval of Bedaquiline and Delamanid for the treatment of drug-resistant tuberculosis was accelerated. Still, there is an urgent need to search for new antitubercular drugs with novel mechanisms of action (MoA). Due to this, we have designed a synthetic strategy by utilizing microwave-assisted organic synthesis. We have compared our method with the conventional procedure, and the data show that our procedure is more effective in the preparation of title compounds. A unique series of 1-(2-(furan-2-yl)-5-(pyridin-4-yl)-1,3,4-oxadiazol-3(2H)-yl)-3-(aryl)-pr op-2-en-1-ones (5a-o) was synthesized utilizing conventional and microwave-assisted techniques. Synthetic compounds were investigated for antitubercular activity against Mycobacterium TB H37Ra and Mycobacterium bovis (M. bovis). Compound 5b was reported to be the most effective against M. tuberculosis H37Ra (97.69 percent inhibition at 30 mu g/ml) and M. bovis (97.09 percent inhibition at 30 mu g/ml). An in silico binding affinity study of mycobacterial enoyl-acyl carrier protein reductase (InhA) reveals the binding mechanism and thermodynamic interactions that determine these molecule's binding affinity. Compound 5b had a high glide score of -8.991 and low glide energy of -49.893 kcal/mol.
Keywords: Antitubercular activity; microwave-assisted organic synthesis; Molecular docking

[DBUH][OAc]-catalyzed domino synthesis of novel benzimidazole incorporated 3,5-Bis (Arylidene)-4-piperidones as potential antitubercular agents - Subhedar, Dnyaneshwar D.; Shaikh, Mubarak H.; Nagargoje, Amol A.; Sarkar, Dhiman; Khedkar, Vijay M.; Shingate, Bapurao B. (Polycyclic Aromatic Compounds, 2022)
A series of new benzimidazole incorporated 3,5-bis (arylidene)-4-piperidones were synthesized by using aryl aldehydes, piperidinone, 2-(chloromethyl)-benzimidazole and DBU acetate [DBUH][OAc] act as a catalyst under solvent free condition in excellent yields. The synthesized compounds were screened for their in vitro antimycobacterial activity against M. tuberculosis H37Ra (MTB) and M. bovis BCG strains. The compounds 4a, 4b, 4e, 4i, 4k and 4l are highly potent against both the strains. Most of the active compounds are non-cytotoxic against MCF-7, A549, HCT 116 and THP-1 cell lines. Furthermore, a molecular docking study of these compounds was carried out to investigate their binding pattern with the target, active site of mycobacterial enoyl-acyl carrier protein reductase (Inh A). Therefore, these compounds can be subjected for further optimization and drug development which could give promising chemical leads for treatment of TB.
Keywords: Antitubercular activity; curcumin; Cytotoxicity; Ionic liquid; multicomponent reactions

Detection of a target protein (GroEl2) in Mycobacterium tuberculosis using a derivative of 1,2,4-triazolethiols - Sarkar, Sampa; Swami, Sagar; Soni, Sarvesh Kumar; Holien, Jessica K.; Khan, Arshad; Korwar, Arvind M.; Likhite, Anjali P.; Joshi, Ramesh A.; Joshi, Rohini R.; Sarkar, Dhiman (Molecular Diversity, 2022)
Herein, we identified a potent lead compound RRA2, within a series of 54 derivatives of 1,2,4-triazolethiols (exhibit good potency as an anti-mycobacterial agents) against intracellular Mycobacterium tuberculosis (Mtb). Compound RRA2 showed significant mycobactericidal activity against active stage Mycobacterium bovis BCG and Mtb with minimum inhibitory concentration (MIC) values of 2.3 and 2.0 mu g/mL, respectively. At MIC value, RRA2 compound yielded 0.82 log reduction of colony-forming unit (cfu) against non-replicating Mtb. Furthermore, RRA2 compound was selected for further target identification due to the presence of alkyne group, showing higher selectivity index (> 66.66 +/- 0.22, in non-replicating stage). Using ``click'' chemistry, we synthesized the biotin linker-RRA2 conjugate, purified with HPLC method and confirmed the conjugation of biotin linker-RRA2 complex by HR-MS analysis. Furthermore, we successfully pulled down and identified a specific target protein GroEl2, from Mtb whole-cell extract. Furthermore, computational molecular modeling indicated RRA2 could interact with GroEl2, which explains the structure-activity relationship observed in this study.
Keywords: 1; 2; 4-triazolethiols; GroEl2; Mycobactericidal activity; Mycobacterium bovis BCG; Mycobacterium tuberculosis

DNA binding, antitubercular, antibacterial and anticancer studies of newly designed piano-stool ruthenium(ii) complexes - Navale, Govinda; Singh, Sain; Agrawal, Sonia; Ghosh, Chandrachur; Choudhury, Angshuman Roy; Roy, Partha; Sarkar, Dhiman; Ghosh, Kaushik (Dalton Transactions, 2022)
The chemotherapeutic potential of ruthenium(ii) complexes has recently attracted researchers' interest as antibacterial and anticancer agents. In this study, two novel half-sandwich imine-based Ru complexes ([Ru(p-cymene)Cl(L-1)][PF6] (Ru-1) and [Ru(p-cymene)Cl(L-2)][PF6] (Ru-2)) were reported for their deoxyribonucleic acid (DNA) binding and antitubercular, antibacterial, and anticancer activities. The molecular structure of Ru-2 was obtained by single-crystal X-ray crystallography. DNA interaction studies were conducted by UV-Vis absorbance and fluorescence spectral titration which gave rise to DNA binding constants (K-b) of 1.32 x 10(6) and 1.82 x 10(6) for Ru-1 and Ru-2, respectively and the Stern-Volmer binding constant (K-SV) values for Ru-1 and Ru-2 were 1.7763 x 10(4) M-1 and 7.6 x 10(3) M-1, respectively. The in vitro antitubercular activity was evaluated against Mycobacterium tuberculosis H37Ra. The antibacterial potential of both the Ru-complexes was examined against Gram-negative (Escherichia coli and Pseudomonas aeruginosa) and Gram-positive (Staphylococcus aureus and Bacillus subtilis) bacteria. The half-maximal inhibitory concentration (IC50) values for the antitubercular activity of Ru-1 and Ru-2 were 4.87 +/- 1.32 mu M and 5.78 +/- 0.54 mu M, respectively. A cytotoxic study of these complexes was performed against the human breast cancer cell line (MCF-7) and the human embryonic kidney cell line (HEK293) (normal cells). The study revealed meaningful activity of the Ru-1 complex against (cancer) MCF-7 cells, while the viability of HEK293 (normal) cells in the presence of Ru-2 was higher as compared to a reference drug 5FU. We suggest that these kinds of Ru-complexes could have potential for application in metallopharmaceuticals.

Probes and techniques used in active and the hypoxia-based dormant state of an antitubercular drug screening assay - Yeware, Amar; Akhtar, Shamim; Sarkar, Dhiman (Medicine in Drug Discovery, 2022)
Current antitubercular drug therapy requires more than six months and is unable to kill latent or dormant forms of tuberculosis. Thus, it is a need of new drug therapy to fight against dormant tuberculosis. However, the major obstacle in the development of novel drugs for dormant tuberculosis is the lack of relevant screening systems and using reliable probes to measure growth inhibition. Until now, several probes used in active state assays are significantly determining the inhibitory effect against the active state of mycobacteria. The dormant condition assays are based on hypoxia-derived dormancy which include resazurin reduction assay, nitrite reductase assay, XTT reduction menadione assay and low oxygen recovery assay. Major probes used in those assays are colorimetric/fluorescent dyes, enzymatic activity, and reporter genes include luciferase and fluorescent proteins. Although these dormant assays are based on hypoxia-induced features and difficult to maintain for a longer duration. Also, they further complicated by growth detection and pursuit of high throughput screening criteria. Here we reviewed complications of probes and assay techniques used for anti-dormant drug screening programs of tuberculosis. This will provide the knowledge to design better alternative drug screening method for the anti-dormant form of tuberculosis.
Keywords: Active and dormant states; and; Drug screening assay; Probes; tuberculosis

Synthesis and antimycobacterial screening of a novel series of alpha-amino acids containing thiazole linker - Nalawade, Jitendra L.; Mhaske, Pravin C.; Shinde, Abhijit D.; Chavan, Abhijit P.; Abhale, Yogita K.; Sarkar, Dhiman; Bobade, Vivek D. (ARKIVOC, 2022)
A small focused library of uncommon (S)-2-amino-3-(4-(((4-methyl-2-arylthiazol-5-yl)methyl)amino)phenyl) propanoic acid (5a-e) and (S)-2-amino-3-(4-(((2-arylthiazol-4-yl)methyl)amino)phenyl)propanoic acid (9a-d) derivatives have been efficiently synthesized by employing molecular simplification. The title compounds were screened for inhibitory activity against Mycobacterium tuberculosis H37Ra (MTB) and Mycobacterium bovis (BCG) strains. The cytotoxicity study was conducted against primary Human Umbilical Vein Endothelial Cells (HUVECs), on two different human tumor cells HeLa, and HCT 116 and was observed non-toxic to host cells.
Keywords: Amino acid; antibacterial activity; Cytotoxicity; Mycobacterium tuberculosis; synthesis; Thiazole

Synthesis of new thiazole and pyrazole clubbed 1,2,3-triazol derivatives as potential antimycobacterial and antibacterial agents - Jagadale, Shivaji M.; Abhale, Yogita K.; Pawar, Hari R.; Shinde, Abhijit; Bobade, Vivek D.; Chavan, Abhijit P.; Sarkar, Dhiman; Mhaske, Pravin C. (Polycyclic Aromatic Compounds, 2022)
New series of 4-methyl-2-(4-substituted phenyl)-5-(4-((4-(4-substituted phenyl)-1H-1,2,3-triazol-1-yl)methyl)-1-phenyl-1H-pyrazol-3-yl)thiazole, 6a-t and 4-(1,3-diphenyl-1H-pyrazol-4-yl)-1-((1,3-diphenyl-1H-pyrazol-4-yl)methyl )-1H-1,2,3-triazole, 11a-o derivatives have been synthesized by applying copper-catalyzed [3 + 2] cycloaddition reaction. The newly synthesized 1,3-thiazolyl-pyrazolyl-1,2,3-triazole (6a-t) and bis-pyrazolyl-1,2,3-triazole (11a-o) derivatives were screened for in vitro antimycobacterial activity against M. Tuberculosis H37Ra dormant and active and antibacterial activity against four pathogenic bacteria, E. coli (NCIM 2576), P. flurescence (NCIM 2059), S. aureus (NCIM 2602) and B. subtilis (NCIM 2162). Compounds 6a, 6f, 6j, 11e and 11m showed good activity against M tuberculosis H37Ra Active strain, also compounds 6g, 6h, 11f, 11n and 11o showed good activity against M tuberculosis H37Ra Dormant strain. Compounds 6b, 6i, 6l, 6o, 6r, 11k, 11l and 11m showed good activity against B. subtilis with IC50 1.99-2.96 mu g/mL. The antibacterial activity of thiazolyl-pyrazolyl-1,2,3-triazole and bis-pyrazolyl-1,2,3-triazole derivatives suggested that, these derivatives could lead to new compounds for treatment against bacterial infection.
Keywords: 123-Triazole; antibacterial activity; antimycobacterial activity; Pyrazole; Thiazole

Tetrazoloquinoline-1,2,3-triazole derivatives as antimicrobial agents: synthesis, biological evaluation and molecular docking study - Shaikh, Mubarak H.; Subhedar, Dnyaneshwar D.; Akolkar, Satish V.; Nagargoje, Amol A.; Khedkar, Vijay M.; Sarkar, Dhiman; Shingate, Bapurao B. (Polycyclic Aromatic Compounds, 2022)
In search of new active molecules, a small focused library of tetrazoloquinoline-based 1,2,3-triazoles has been efficiently preparedviaclick chemistry approach. Several derivatives were found to be exhibiting promising antimicrobial and antioxidant activity characterized by their lower minimum inhibitory concentration values. All the synthesized compounds exhibited excellent antibacterial activity against Gram negative bacteriaE. coliandF. devoransand antifungal activity againstC. albicansandA. niger. Further, these compounds were tested for their antitubercular activity against dormantMTB H37Raand dormantM. bovis BCGusing XRMA assay protocol and showed no significant activity. Also, the synthesized compounds were found to have potential antioxidant activity with IC(50)range = 12.48-50.20 mu g/mL. Furthermore, to rationalize the observed biological activity data, the molecular docking study also been carried out against the active site of fungalC. albicansenzyme P450 cytochrome lanosterol 14 alpha-demethylase, which revealed a significant correlation between the binding score and biological activity for these compounds. The results of thein vitroandin silicostudy suggest that the triazole-incorporated tetrazoloquinolines may possess the ideal structural requirements for further development of novel therapeutic agents.
Keywords: 1; 2; 3-Triazole; ADME prediction; Antimicrobial; Antioxidant; Docking study

Two antibacterial spiro compounds from the roots of Artemisia pallens wall: evidence from molecular docking - Honmore, Varsha S.; Natu, Arun D.; Khedkar, Vijay M.; Arkile, Manisha A.; Sarkar, Dhiman; Rojatkar, Supada R. (Natural Product Research, 2022)
Bioassay-guided isolation from acetone extract of the roots of Artemisia pallens Wall yielded two spiro compounds (1 and 2). The structures of these compounds were determined on the basis of spectroscopic techniques such as IR, MS, 1 D and 2 D- NMR. The acetone extract, fractions and the isolated two compounds were investigated for their antibacterial activity against two gram negative (E. coli, P. aeruginosa) and two gram positive (S. aureus, B. subtilis) bacterial strains. Compound (2) showed the best spectra of activity with IC50 and MIC values between 2.48-3.08 and 12.78 - 21.77 mu M and Compound (1) with 2.57-3.69 and 38.17 - 80.57 mu M, respectively, for the four bacterial strains, whereas inactive against Mycobacterium tuberculosis. Molecular docking study could further help in understanding the various interactions between these compounds and DNA gyrase active site in detail and thereby could provide valuable insight into the mechanism of action.
Keywords: antibacterial activity; antimycobacterial activity; Artemisia pallens; Asteraceae; Molecular docking; spiro compound

Design and synthesis of piano-stool ruthenium(II) complexes and their studies on the inhibition of amyloid ? (1-42) peptide aggregation - Singh, Sain; Navale, Govinda R.; Agrawal, Sonia; Singh, Haobam Kisan; Singla, Labhini; Sarkar, Dhiman; Sarma, Manabendra; Choudhury, Anghuman Roy; Ghosh, Kaushik (International Journal of Biological Macromolecules, 2023)
Misfolding , protein aggregation have been linked to numerous human neurodegenerative disorders such as Alzheimer's, prion , Parkinson's diseases. Ruthenium (Ru) complexes have received considerable attention in studying protein aggregation due to their interesting photophysical and photo properties. In this study, we have synthesized the novel Ru complexes ([Ru(p-cymene)Cl(L-1)][PF6](Ru-1), and [Ru(p-cymene)Cl(L-2)][PF6](Ru-2)) and investigated their inhibitory activity against the bovine serum albumin (BSA) aggregation and the A beta 1-42 peptides amyloid formation. Several spectroscopic methods were used to characterize these complexes, and the molecular structure of the complex was determined by X-ray crystallography. Amyloid aggregation and inhi-bition activities were examined using the Thioflavin-T (ThT) assay, and the secondary structures of the protein were analyzed by circular dichroism (CD) spectroscopy and transmission electron microscopy (TEM). The cell viability assay was carried out on the neuroblastoma cell line, revealing that the complex Ru-2 showed better protective effects against A beta 1-42 peptide toxicity on neuro-2a cells than the complex Ru-1. Molecular docking studies elucidate the binding sites and interactions between the Ru-complexes and A beta 1-42 peptides. The exper-imental studies revealed that these complexes significantly inhibited the BSA aggregation and A beta 1-42 amyloid fibril formation at 1:3 and 1:1 molar concentrations, respectively. Antioxidant assays demonstrated that these complexes act as antioxidants, protecting from amyloid-induced oxidative stress. Molecular docking studies with the monomeric A beta 1-42 (PDB: 1IYT) show hydrophobic interaction, and both complexes bind preferably in the central region of the peptide and coordinate with two binding sites of the peptide. Hence, we suggest that the Ru-based complexes could be applied as a potential agent in metallopharmaceutical research against Alzheimer's disease.
Keywords: Aggregation; Amyloid ?(1-42) peptide; DFT computation; Fibrillization; Molecular docking; Ruthenium complexes

Design, synthesis, and in vitro biological evaluation of ROS-generating phenanthridin-trione-epoxide conjugates as agents against mycobacterium tuberculosis - Mamgain, Ritu; Swami, Sagar; Sarkar, Dhiman; Srivastava, Pratibha (ChemistrySelect, 2023)
Tuberculosis (TB) is one of the devasting infectious diseases and continues to spread among people despite having several specific drugs. Total eradication of TB is one of the shared interests of both the World Health Organization (WHO) and India globally. A library of antitubercular 6-((1-(aryl/heteroaryl)-1H-1,2,3-triazol-4-yl)methyl)oxireno[2,3-b] phenanthridine-5,7,9(6H,7aH,8aH)-trione (6 a-e) has been prepared in five steps including click chemistry and tested against active and dormant strains of Mycobacterium tuberculosis H37Ra using XRMA protocol. The result showed the inhibitory potential of 6 d IC50 at 0.74 & mu;g/mL concentration against active strain and at 0.9 & mu;g/mL against the dormant strain of Mtb. ROS generating ability of the compounds has been confirmed by luminol, H2O2, and glutathione assays. The molecular docking with the thioredoxin protein of Mtb showed a docking score of -9.6 Kcal/mol. To understand the mechanism with the thioredoxin protein of Mtb, the adduct formation of compounds with cystine was confirmed with HPLC. The involvement of lead molecules with existing drugs can be helpful in the eradication of tuberculosis.
Keywords: antimycobacterial agents; Computational docking; Cystine adduct; Epoxy-Phenanthridinone-triazoles; ROS generation

Inhibition of amyloid β1-42 peptide aggregation by newly designed cyclometallated palladium complexes - Saini, Rahul; Navale, Govinda R.; Singh, Sain; Singh, Haobam Kisan; Chauhan, Rahul; Agrawal, Sonia; Sarkar, Dhiman; Sarma, Manabendra; Ghosh, Kaushik (International Journal of Biological Macromolecules, 2023)
Uncontrolled amyloid aggregation is a frequent cause of neurodegenerative disorders such as prions and Alzheimer's disease (AD). As a result, many drug development approaches focus on evaluating novel molecules that can alter self-recognition pathways. Herein, we designed and synthesized the cyclometallated pyrene (Pd-1 and Pd-3) and anthracene (Pd-2) based palladium complexes ([Pd((L-1)Cl] Pd-1, [Pd(L-2)Cl](Pd-2), and [Pd(L-3)Cl] (Pd-3)). This study explores the effect of these complexes on the aggregation, fibrillation, and amyloid formation of bovine serum albumin (BSA) and A beta(1-42) peptide. Several spectroscopic methods were used to characterize all the Pd-complexes, and the molecular structure of Pd -3 was determined by X-ray crystallography. The secondary structures were studied using circular dichroism (CD) and transmission electron microscopy (TEM), while am-yloid aggregation and inhibitory activities were investigated using the Thioflavin-T (ThT) fluorescence assay. Molecular docking of the Pd-complex (Pd-3) was done using fibril (PDB: 2BEG) and monomeric (PDB: 1IYT) peptides using Auto-dock Vina. As a result, the hydrogen bonding and hydrophobic interaction between the aromatic rings of the Pd-complexes and the amino acids of amyloid-beta peptides significantly reduced the pro-duction of ordered beta-sheets of amyloid fibrils and protein aggregation in the presence of Pd-2 and Pd-3 complexes.
Keywords: A beta(1-42) peptide; Aggregation and molecular docking; Palladium complex

Total synthesis, structure elucidation and expanded bioactivity of icosalide A: effect of lipophilicity and ester to amide substitution on its bioactivity - Dangi, Abha; Pande, Bharat; Agrawal, Sonia; Sarkar, Dhiman; Vamkudoth, Koteswara Rao; Marelli, Udaya Kiran (Organic & Biomolecular Chemistry, 2023)
The first total synthesis of icosalide A, an antibacterial depsipeptide that is unique in that it contains two lipophilic beta-hydroxy acids, has been achieved by following Fmoc solid-phase peptide synthesis in combination with solution-phase synthesis. The ambiguity in the absolute stereochemistry of icosalide A has been resolved by synthesizing the reported structures and other relevant diastereomers of icosalides and comparing their NMR data. NMR-based structure elucidation of icosalide A revealed a well-folded structure with cross-strand hydrogen bonds similar to the anti-parallel beta-sheet conformation in peptides and displayed a synergistic juxtaposition of the aliphatic sidechains. 12 analogues of icosalide A were synthesized by varying the constituent lipophilic beta-hydroxy acid residues, and their biological activities against Bacillus thuringiensis and Paenibacillus dendritiformis were explored. Most of these icosalide analogues showed an MIC of 12.5 & mu;g mL(-1) against both bacteria. Swarming inhibition by icosalides was least in B. thuringiensis (8.3%) compared to that in P. dendritiformis (33%). Furthermore, this is the first report of icosalides showing assured inhibitory action (MIC between 2 and 10 & mu;g mL(-1)) against the active stage of Mycobacterium tuberculosis and cancer cell lines such as HeLa and ThP1. This study could help optimize icosalides for anti-TB, antibacterial, and anti-cancer activities.

Synthesis and antimicrobial evaluation of novel 2'-aryl-4-aryl-2,4'-Bisthiazole and 2'-aryl-4-Pyridyl-2,4'-bisthiazole derivatives as potential antibacterial agents - Nalawade, Jitendra; Shinde, Abhijit; Abhale, Yogita K.; Nandurkar, Yogesh; Bobade, Vivek D.; Sarkar, Dhiman; Mhaske, Pravin C. (Polycyclic Aromatic Compound, 2024)
In continuation of our research work to explore bisthiazole derivatives as potential antimicrobial agents, herein we reported the synthesis of a series of novel 2'-aryl-4-aryl-2,4'-bisthiazole (7a-t) and 2'-aryl-4-pyridyl-2,4'-bisthiazole (9a-l) by cyclocondensation of 2-aryl thiazole-4-carbothioamide 5a-d with 2-bromo-1-arylethanone (6a-e) and bromo-1-(pyridin-2/3/4-yl)ethanone (8a-c), respectively. These novel candidates were evaluated in vitro for their antibacterial potential against four pathogenic bacteria, Escherichia coli (NCIM 2576), Pseudomonas flurescence (NCIM 2059), Staphylococcus aureus (NCIM 2602), and Bacillus subtilis (NCIM 2162). The synthesized compounds were also screened for their in vitro antifungal activity against Candida albicans (NCIM 3100). Among them, compounds 7b, 9d, 9 g, 9i, and 9 l exhibited excellent antibacterial activity with MIC 2.1 to 12.3 mu g/mL against all tested strains. Most of the compounds reported moderate antifungal activity. The pyridine ring-substituted bisthiazole reported good to excellent antibacterial activity as compared to phenyl ring-substituted bisthiazole. The potential antibacterial activity suggested that bisthiazole derivatives could assist in the development of lead compounds to treat microbial infections.
Keywords: 24'-bisthiazole; antibacterial activity; Antifungal activity; cyclocondensation

Coumarin hybrids: dual-target candidates for future antimicrobial and antitubercular therapies - Bavishi, Abhay; Vala, Hardev; Thakrar, Shailesh; Swami, Sagar; Sarkar, Dhiman; Shukla, Rushit; Kamdar, Jignesh; Shah, Anamik (Future Medicinal Chemistry, 2025)
Aims: This study aimed to synthesize, characterize, and evaluate the antimicrobial and antitubercular activities of two novel series of coumarin-based derivatives (Series 5 and Series 9), focusing on their structure-activity relationship (SAR) and molecular docking interactions with key bacterial enzymes. Materials & methods: Series 5 (5a-5j) and Series 9 (9a-9t) compounds were synthesized and characterized using spectroscopic techniques. Their antimicrobial and antitubercular activities were evaluated against Mycobacterium tuberculosis, Staphylococcus aureus, Bacillus subtilis, and E. coli. IC50 values were determined, and molecular docking studies were conducted to assess binding interactions with M. tuberculosis enoyl-ACP reductase (InhA) and E. coli DNA gyrase B. Results: Series 5 compounds exhibited moderate activity, with 5f, 5 g, 5i, and 5j showing notable inhibition. Series 9 derivatives displayed superior dual-target inhibition, with 9t, 9c, 9a, 9b, and 9p achieving >90% inhibition against S. aureus and B. subtilis. The lowest IC50 against M. tuberculosis was observed for 9c (1.50 mu g/mL), followed by 9a (2.84 mu g/mL) and 9b (2.73 mu g/mL). Molecular docking confirmed strong binding interactions, correlating with observed biological activities. Conclusions: Series 9 compounds, particularly 9t, 9c, and 9a, demonstrate high potential as dual-target antimicrobial drug candidates. Further optimization may enhance their therapeutic efficacy. [GRAPHICS]
Keywords: Antimicrobial activity; antitubercular agents; Coumarin derivatives; Molecular docking studies; structure-activity relationship (SAR); thiophene-based compounds

[DBUH][HSO4]-catalyzed solvent-free synthesis of 1,5-benzodiazepine derivatives: bioevaluation and in silico molecular docking study - Subhedar, Dnyaneshwar D.; Shaikh, Mubarak H.; Nagargoje, Amol A.; Sarkar, Dhiman; Khedkar, Vijay M.; Shingate, Bapurao B. (Current Organic Chemistry, 2025)
Here, we report the solvent-free one-pot multicomponent synthesis of 4-substituted-1,5-benzodiazepine derivatives from O-phenylenediamine, aromatic aldehydes, and dimedone using [DBUH][HSO4] as a catalyst in excellent yields. This process was carried out in search of a reusable, easily accessible, affordable, and efficient catalyst. 1,5-Benzodiazepines demonstrate a new family of good inhibitors with potent anti-mycobacterial properties. The most promising compounds in the present series are 4c, 4i, and 4l which showed excellent activity and inhibited the growth of both MTB H37Ra and M. bovis BCG strains with lower MICs. The most active compounds were further studied for their cytotoxicity against cell lines MCF-7, A549, HCT116, and THP-1 by MTT assays and the compounds were found to be non-toxic. The fact that none of these compounds work against either Gram-positive or Gram-negative bacteria suggests that they are only effective against MTB. The in silico docking of the molecules against mycobacterial enoyl reductase, InhA enzyme could provide well-clustered solutions and have given valuable insights into the thermodynamic elements governing the binding affinities. The findings of this investigation unmistakably point to the discovery of extremely specific and selective MTB inhibitors, which can now be investigated further in search of possible anti-tubercular drugs.
Keywords: 1; 5-benzodiazepine; Antitubercular activity; Molecular docking; multicomponent reactions; [DBUH][HSO4]

Regio selective synthesis of pyrazole derivatives of 5-chloro-2-methoxy phenyl hydrazide and their biological evaluation - Bavishi, Abhay; Vala, Hardev; Swami, Sagar; Thakrar, Shailesh; Shah, Anamik; Sarkar, Dhiman (Journal of Heterocyclic Chemistry, 2025)
Present study involves synthesis of derivatives of (5-chloro-2-methoxyphenyl) (5-alkyl-3-(substituted) (phenyl/alkyl)-1H-pyrazol-1-yl) methanones. Structural elucidation of the synthesized compounds was depicted by the data of 1H and 13C NMR, IR, and Mass spectral analysis. The newly synthesized compounds 1a-1d and 2a-2i were screened in vitro against Mycobacterium tuberculosis H37Ra using an established XRMA protocol. Among the screened compounds, 2d, 2f, and 2h showed good percent inhibition against the active stage of M. tuberculosis H37Ra 80.77, 55.70, and 79.54, respectively, at 30 mu g/mL of inhibitor concentration. Further in secondary screening, compound 2d exhibited significant antitubercular activity on the active stage of M. tuberculosis H37Ra with IC50 of 0.208 mu g/mL. The synthesized compounds were also screened for antibacterial activity and found no significant activity against Gram-positive Bacteria Bacillus subtitles and Staphylococcus aureus and Gram negative bacteria Pseudomonas aeruginosa and Escherichia coli at 30 mu g/mL, which confirms the specificity of inhibitory activity against M. tuberculosis and more selectively against the active stage. The present study will be helpful for the further development of these molecules into antitubercular lead candidates.
Keywords: 5-chloro-2-methoxy phenyl hydrazide; antibacterial activity; Antitubercular activity; Biological evaluation; H37Ra; hydrazide; Pyrazole

Synthesis, biological screening, and molecular docking of hybrid pyrazole scaffolds for antitubercular and antimicrobial activity - Bavishi, Abhay; Vala, Hardev; Radadiya, Ashish; Swami, Sagar; Thakrar, Shailesh; Sarkar, Dhiman; Shah, Anamik (ChemistrySelect, 2025)
This study reports the synthesis, characterization, and docking analysis of 21 novel compounds, including asymmetric dihydropyridines (4a-4o) and chalcones (6a-6f), derived from coupling 1,3-(substituted)-diphenyl-1H-pyrazole-4-carbaldehyde with active methylene compounds and 3-acetyl-4-hydroxycoumarin, respectively. Structural confirmation was achieved through 1H and 13C NMR, IR, and mass spectrometry. Biological screening against mycobacterium tuberculosis H37Ra identified compounds 4b, 4d, 4f, 4g , 4i, 4k, 6e, and 6f as significant antitubercular agents. Antibacterial evaluation at 30 mu g/mL showed selective inhibition of gram-positive bacteria, with compound 6e active against Staphylococcus aureus and Bacillus subtilis, and 6f showing activity specifically against S. aureus. Docking studies indicated effective InhA binding (Delta G = -3.52 to -7.27 kcal/mol) and inhibition constants ranging from 2640 to 4.71 mu M. Key binding interactions with residues TYR156 and ILE192 were observed, enhancing affinity, particularly for compound 6e. The SAR analysis emphasized the enhanced antitubercular potency of 2-chloroacetyl and 2,4-dichlorobenzoyl substitutions in the dihydropyridine series, while in the chalcone series, specific substitutions, such as the 3-nitro substitution in 6e, enhance antitubercular and antimicrobial potency due to stronger hydrogen bonding and increased polar surface area, while the 4-fluoro substitution in 6f confers selective activity against S. aureus.
Keywords: 1; 4-dihydropyridine; 4-hydroxy coumarin; Biological activity; In silco studies; Pyrazole